Cage-based mariculture as a vector of antibiotic dissemination: Evidence from seasonal and multi-compartment surveillance in a coastal mariculture bay - Xiaohan Yin; Keju Zhou; Yuxuan Huang; Shenghan Xie; Zhiyuan Dou; Xixi Chen; Yongyu Li; Zulin Zhang; Xinhong Wang (Marine Pollution Bulletin, 2026)

Examining how the physical morphology of watersheds affects connectivity and hydrological pathways - Mahdis Amiri; Mehdi Gheisari; Mojgansadat Azimi; Ergin Ulutas; Jie Dou; Shuisen Chen; Huxiong Li; Xiuqing Wang; Zhengzong Wang (Journal of African Earth Sciences, 2026)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Investigation on the combustion kinetic mechanism of polyoxymethylene dimethyl ether 3 (PODE3) and diesel with hydrogen addition - Qimin Song; Huiquan Duan; Huajie Wang; Changhai Ma; Zhancheng Dou; Shuzhan Bai; Guoxiang Li; Xiaoxiao Zeng (Fuel, 2026)

Biodiversity effects on aboveground biomass shift from structural to species diversity across vertical strata in desert riparian forests - Houji Liu; Chunxia Wei; Ziwei Dou; Jie Wang; Juntuan Zhai; Zhikun Yang; Lijun Zhu; Zhijun Li (Forest Ecology and Management, 2026)

Initiation sequence of competing instabilities during high-pressure CO2 injection in overpressured reservoirs: fault shear reactivation, caprock tensile fracture initiation, and delayed pressure-relief feedback from blind faults - Yihang Luo; Xianzhe Duan; Nan Li; Kaituo Shi; Wenzhou Xiao; Jiale Dou; Jiawei Wang; Bingqing Shao; Huan Huang; Liping Shu; Hafiza Tasneem Nazish (Computers and Geotechnics, 2026)

Soil types, developmental age, and climatic background of modern soils in the Zoige Basin, northeastern Tibetan Plateau - Jiangli Pang; Dou Chen; Yali Zhou; Xiaochun Zha; Yuqin Li; Yuzhu Zhang; Ruiqi Huang; Meihui Zhang; Xinran Fan (CATENA, 2026)

L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Perillaldehyde reduces mitochondrial oxidative stress damage by regulating KCNT2/NR1D1 protein activity in vascular dementia rats - Qian-qian Wang; Hong-dou Zhang; Pei-yao Liu; Chun-rui Zhang; Bao-yue Cui; Xi-yue Li; Meng-yao zhao; Jin-he Yang; Peng Li; Ya-ling Yin; Xue-yu Sun (Molecular Biology Reports, 2026)

Age-specific optimization of ovarian superstimulation, oocyte maturation, and somatic cell nuclear transfer in juvenile and adult goats - Jinwang Liu; Yanbing Liu; Hongxing Han; Zhiyi Shen; Jie Li; Yingang Guo; Meiyun Lv; Yiming Dou; Shipeng Lv; Hongyu Liu; Jing Jiang; Xiaoyan Sun; et al. (Animal Reproduction Science, 2026)

Pyraclostrobin resistance in tobacco anthracnose pathogens: Risk assessment and molecular mechanism - Jiakai Wang; Ziyang Zhang; Tingou Li; Mengzhen Wang; Mengyao Dou; Liyuan Wang; Yiqiang Cai; Jie Zhang; Maofeng Jing; Yabing Duan (Pesticide Biochemistry and Physiology, 2026)

Temperature sensitivity of pyrrhotite-driven metavanadate bioreduction in groundwater - Yang Tang; Song Wang; Dou Wang; Jinqiu Li; Wenyue Yan (Environmental Research, 2026)

Thermal imaging with instance segmentation for quantifying sleep thermally adaptive quilt coverage behavior - Nan Zhang; Wenhao Wang; Tianqi Xu; Musitapa Alipu; Xiangyu Wang; Zhiyang Dou; Xiaojing Zhang; Jianong Li (Energy and Buildings, 2026)

Interlayer-ordered COF/TiVCTx MXene films with enhanced ion transport for wearable electronics - Zhemin Li; Hai Xu; Derong Luo; Shaoxiong Li; Yinghong Xu; Hui Dou; Xiaogang Zhang (Chemical Engineering Journal, 2026)

Hydrogen substitution regulating reaction pathways at active sites of amine-based deep eutectic solvents for enhancing CO2 absorption - Shaoyu Wang; Yueying Li; Haoran Pan; Hua Li; Xinhui Ma; Xingxing Chen; Jinxiao Dou; Jianglong Yu (Chemical Engineering Journal, 2026)

Oxygen vacancies and lattice distortion: Competing effects in regulating electrochemical behavior of Na3V2(PO4)2F3 - Yutian Chen; Xianghu Dou; Hao Zhao; Benyi Zhao; Hongzhi Zhao; Yuxiao Wang; Jianwei Li; Zhiming Liu (Chemical Engineering Journal, 2026)

A dual-functional heterosalt additive enables synergistic interphase-bulk engineering for advanced nickel-rich cathodes - Dongni Zhao; Jing Luo; Zixiang Su; Hongzeng Dou; Jingzuo He; Junwei Zhang; Yanjun Zhao; Xinfang Xu; Peng Wang; Ningshuang Zhang; Xiaoling Cui; Shiyou Li (Chemical Engineering Journal, 2026)

A facile tannic acid/gentamicin-loaded biodegradable silk fibroin lifting thread with robust mechanical and antibacterial properties - Yuejie Dou; Shihao Song; Xuchen Wang; Fanlei Yang; Yan Du; Xiaoyu Zhang; Zibo Chen; Jia Yu; Gang Li (Bioresource Technology, 2026)

The safety evaluation of the pVAX-ROP27 DNA vaccine against Eimeria tenella - Xiaoling Lv; Baojie Li; Xuan Chang; Wenrui Zhao; Menggang Li; Jiaqi Zhao; Kewei Dou; Zhibin Niu; Rui Bai; Li Zhang; Xiaozhen Cui (Veterinary Immunology and Immunopathology, 2026)

Integrating machine learning with Raman spectroscopy for microplastic identification and classification: Method construction and application - Kaibo Jin; Yanyan Dou; Yang Li; Jingjing Lv; Xuejun Duan; Xudong Chen; Xishu Liang; Tianyu Ao; Keyi Lu; Shoukai Chen (Journal of Water Process Engineering, 2026)

A systematic Meta-analysis of breed, regional, and production determinants of pork quality - Weidong Hu; Md. Abul Kalam Azad; Bo Song; Qian Zhu; Zhihua Li; Haoran Wang; Yang Xu; Mengyin Dou; Jia Li; Wenxi Zhang; Binghua Qin; Xiangfeng Kong (Food Research International, 2026)

The acid polysaccharides extracted from Moringa leaf improve DSS-induced ulcerative colitis by targeting intestinal microbiota metabolism - Wen Lang; Xinyun Qin; Yizhe Dou; Keyi Nong; Ruixue Cao; Tingyu Chen; Wanyan Chen; Bin Zhang; Zheng Yang; Bowen Tian; Jijun Wang; Lianbin Li; et al. (Food Research International, 2026)

Dual signal-enhanced immunochromatographic test strip based on Au@PtNPs: From sensitive detection of thiamethoxam to multiplex pesticide screening in vegetables - Zhengtao Li; Lingjun Geng; Jiashuai Sun; Jingcheng Huang; Rui Xu; Zhen Guo; Shouyi Dou; Liying Zhang; Fangling Du; Yemin Guo; Xia Sun; Nortoji A. Khujamshukurov (Food Chemistry, 2026)

The dynamic complexity of critical mineral supply chains reveals the paradox of energy transition - Junhui Li; Yongguang Zhu; Shiquan Dou; Qian Zhang; Saleem H. Ali; Gang Liu; Yanqiong Zhao; Na Zhou; Jinhua Cheng; Deyi Xu (Ecological Economics, 2026)

Comparisons analyses of three compaction methods on mesoscopic characteristics of Gobi gravels using DEM method - Ning Li; Guangwei Pang; Jinxiang Chen; Hengyuan Dou; Qian Wang; Wei Si (Computers and Geotechnics, 2026)

High and thermally stable dielectric energy storage via synergistic disordered polarization and ordered oxygen octahedral tilting - Zhimin Huang; Xinhen Li; Yongjian Li; Yujun Wu; Xinliang Qiu; Xintong Qin; Dou Zhang; Zhifang Zhou; Xuefan Zhou (Chemical Engineering Journal, 2026)

An inulin from Asparagus cochinchinensis relieves slow transit constipation associated with Akkermansia muciniphila enrichment, kynurenic acid restoration, and NLRP3 attenuation - Fangxu Yin; ZiYing Jiang; Chong Hou; Jie Gao; Wenqiang Li; Wei Sun; Yikui Tian; Dina Xie; Mingyue Wang; Bo Wang; Wenyue Ma; Xiaohui Dou; et al. (Carbohydrate Polymers, 2026)

Role of SIRT3-mediated IDH2 deacetylation in energy metabolism disorders and necroptosis of chondrocytes induced by T-2 Toxin - Fang-Fang Yu; Yan-Jie Dou; Tong-Tong Sha; Huan-Xia Zhang; Yao Li; Qian Li; Zai-Chao Dong; Guang-Ning Kou (Chemico-Biological Interactions, 2026)

Multi-pathway environmental and health impacts of volatile compound emissions from waste-to-energy plants in China - Guiying You; Hefan Liu; Xiaoya Dou; Rui Sun; Jing Li; Shaodong Xie (Atmospheric Environment, 2026)

Straw return regimes improve mollisol quality by reshaping microbial composition and metabolic profiles - Xinyuan Li; Yanhui Dou; Tingting Cui; Jing Xu; Yuxian Wang; Junqiang Wang; Rong Jiang; Shumin Sun; Guanghui Hu; Wanrong Gu (Applied Soil Ecology, 2026)

Rational modulation of probe electrophilicity, hydrazine nucleophilicity and product fluorescence for accurate sensing of hydrazine - Zhuo Liu; Luyan Yang; Yingxing Li; Jinhui Yang; Xincun Dou; Baiyi Zu (Analytica Chimica Acta, 2026)

Spatiotemporal dynamics of vegetation cover and its responses to drought in arid northwestern China - Xiuxia Zhang; Linyan Gao; Lisha Han; Zaoliang Gao; Aixia Dou; Heng Du; Wangping Li; Zhaoye Zhou; Xiaoxian Wang (Environmental Monitoring and Assessment, 2026)

Application and advances of hybridization chain reaction-based aptasensors in food safety detection - Mengyue Liu; Shouyi Dou; Mingyang Lv; Shuhua Wei; Yongcun Yan; Xinxin Li; Yemin Guo; Xia Sun; Shicai Xu (Trends in Food Science & Technology, 2026)

Association of exposure to household pesticides with concentration of serum sex steroid hormones in general U.S. population: A cross-sectional study - Yun Zheng; Shizhi Wang; Haohan Liu; Yiran Lu; Jianrui Dou; Xiuting Li; Xin Zhou (Reproductive Toxicology, 2026)

Aeolian sedimentary records of aeolian activity and climatic evolution after the retreat of the Zoige Paleolake in the northeastern Tibetan Plateau, China - Jiangli Pang; Dou Chen; Yali Zhou; Xiaochun Zha; Yuqin Li; Yuzhu Zhang; Meihui Zhang; Ruiqi Huang; Xinran Fan (Quaternary International, 2026)

Cenozoic basin-range coupling in the western Qaidam Basin: Constraints from detrital biotite 40Ar/39Ar geochronology - Jizhou Liu; Weimin Li; Sihua Yuan; Yongjiang Liu; Qianqian Wang; Tongjun Liu; Ziqian Dou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Significant role of intermittent PMS backwash in mitigating irreversible fouling in MnTiO3 catalytic ceramic membranes - Guangxu Zhang; Jin Wang; Wubin Wang; Yadong Hu; Mengmeng Dou; Chao Han; Xinyu Li; Kaibo Wang; Yaxuan Liu; Yuting Ma (Journal of Water Process Engineering, 2026)

Role of macrophage NLRP3 inflammasome activation in real-ambient particulate matter-induced abnormal hepatic glucose metabolism - Dong Wu; Zhen Zhang; Sixin Chen; Haoran Chen; Daochuan Li; Shuxin Zhang; Junjie Dou; Yuanyuan Ma; Rong Zhang; Lianhua Cui (Journal of Environmental Sciences, 2026)

Toxic gas removal using deep eutectic solvents: A review of fundamentals and applications - Jinxiao Dou; Shaoyu Wang; Yueying Li; Hua Li; Xingxing Chen; Jianglong Yu (Fuel, 2026)

A method for predicting the thermal strength of coke based on feature interaction and nonlinear optimization - Kemeng Yang; Yiming Wang; Yanqing Dou; Weijie Li; Jin Li; Liangyu Chen; Shoujun Liu; Yadong Bai; Song Yang (Fuel, 2026)

Key aroma-active compounds and machine learning classification of chestnut baijiu revealed by molecular sensory, docking, and pathway analyses - Dan Li; Xinyue Zhang; Xiaohui Dou; Yujia Li; Yuchen Hou; Fumin Ma; Cuicui Duan; Xiaolei Li (Food Research International, 2026)

Early pregnancy exposure to organophosphate esters and risk of infant atopic dermatitis: Sex-Specific association analyses in a community-based birth cohort - Limin Dou; Zhiyuan Du; Youping Tian; Huaqing Zhong; Haisheng Huang; Rongqi Xiang; Yingying Ni; Xiaohua Zhang; Weili Yan; Ming Li; Weiwei Zheng; Ying Ye (Environmental Pollution, 2026)

Microscopic horizontal heterogeneity of shale: Quantitative characterization based on NMR spatial spectra and its control on multi-phase fluid behavior during CO₂ injection - Zhuoying Dou; Zhengming Yang; Haibo Li; Xinliang Chen; Lvshuai Yang; Chenyu Han (Engineering Geology, 2026)

Two-way coupled Euler-Lagrange modelling of finite-size effects in bubble columns: Role of volume displacement and undisturbed velocity - Changjun Wang; Zhongqiu Liu; Baokuan Li; Zhihe Dou (Chemical Engineering Journal, 2026)

Nanostructured Fe2(MoO4)3 cathodes: Enhancing ion and electron kinetics for high-rate and low-temperature sodium-ion batteries - Ting Zhao; Hang Liu; Gacao Dou; Dongting Zhang; Junqiang Qiao; Juan Yang; Pengjun Ma; Cuiying Lu; Hongxia Li; Hongruo Ma; Kunjie Wang; Bingjun Yang (Chemical Engineering Journal, 2026)

Research progress on genomic selection breeding technology for crops - Qiufei Wu; Yajing Dou; Haseeb Ahmad; Zongming Li; Lixia Zhou (Protoplasma, 2026)

Multi-Scale Structural MRI Features Reveal Task-Based Functional Connectivity and Its Alterations in Psychiatric Disorders: A Collaborative Graph Attention Network Approach - Qingchuan Zhang; Zhenqiao Liu; Wenjie Dou; Ruizhe Zhong; Zihan Li; Huan Jiang (Brain Topography, 2026)

Microplastic type influences soil phosphorus availability independently of long-term cropping systems and fertilization regimes - Xuechen Yang; Lin Han; Raúl Ochoa-Hueso; Jingjie Dou; Peng He; Yakov Kuzyakov; Wenzheng Song; Xiaowei Wei; Yueyu Sui; Xiangxiang Hao; Lu-Jun Li (Agriculture, Ecosystems & Environment, 2026)

Spatial and temporal evolution of the groundwater depth and indirect effects during the spring irrigation period in the Hetao Irrigation District - Yi Zhao; Haibin Shi; Xianyue Li; Shuya Yang; Haoqi Han; Yunlei Dong; Qingfeng Miao; Jianwen Yan; Cong Hou; Xu Dou (Irrigation Science, 2026)

Wind products from the first operational dual-frequency scatterometer WindRAD: retrieval and performance assessment - Fangli Dou; Zhixiong Wang; Xiaochun Zhai; Zhen Li; Jian Shang; Chengli Qi; Na Xu; Xiuqing Hu; Peng Zhang (Acta Oceanologica Sinica, 2026)

The Protective Effect of Astragalus Polysaccharides Against Cisplatin‑Induced Pulmonary Epithelial Cell Injury: An Integrated Network Toxicology and In Vitro Validation - Yan Liu; Liyan Ma; Lei Zhang; Liangding Dou; Ninghui Yang; Junrong Li; Kun Zhang (Cell Biochemistry and Biophysics, 2026)

Selenium Nanoparticles Alleviate Intestinal Epithelial Barrier Dysfunction by Coordinating Mitochondria-lysosome Communication under Dual Organelle Stress - Jiajing Chang; Xiaonan Zeng; Runan Zhang; Tiantian Li; Qianqian Gao; Xina Dou; Chunlan Xu (Biological Trace Element Research, 2026)

Integrating multi-geometry InSAR and explainable machine learning for mapping potential landslide areas in reservoir regions - Ke Xing; Suju Li; Jie Dou; Fang Chen; Lizhe Wang; Aonan Dong; Hamza Daud; Lele Zhang (Remote Sensing of Environment, 2026)

PlantPTM: A deep learning framework integrating protein language models with multi-view features for predicting diverse post-translational modification sites in plants - Gensheng Dou; Kaiyuan Wang; Zhaohui Qin; Min Zhang; Wentian Zhang; Chunbo Miao; Junzhou Li; Zhen Chen (Molecular Plant, 2026)

Enhanced water level fluctuations reduced the competitive advantage of cyanobacteria - Yan Chen; Rui Xia; Ruining Jia; Junde Ming; Kai Zhang; Jinghui Dou; Tianxiang Zhao; Xiang Li; Qin Zhang; Qi Zhang (Journal of Hydrology, 2026)

Visible-light-induced phase transformation of ferrihydrite for enhanced uranium immobilization: Mechanisms and stability - Xixian Huang; Chunyi Liu; Ye Dou; Hao Guo; Yang Li; Yang Ding (Journal of Environmental Chemical Engineering, 2026)

Prevalence, genetic diversity, and drug-resistance of Listeria monocytogenes ST8 in enoki mushrooms: Comparative genomic and phenotypic analysis with meat and clinical ST8 isolates - Jingci Lyu; Biyao Xu; Xin Dou; Binru Gao; Linfeng Li; Yangtai Liu; George-John Nychas; Chunhong Yuan; Xiang Wang; Qingli Dong; Zhuosi Li (International Journal of Food Microbiology, 2026)

Association study on the regulation of muscle development-related genes, proteins, and metabolites in different tissues by gastrointestinal flora during various developmental stages of Liaoning cashmere goats - Yinggang Sun; Xingtang Dou; Qingyu Yuan; Ran Duan; Qiying Zhan; Taiyu Hui; Yanjun Qiao; Jiaqi Li; Wangshu Li; Yunlong Guo; Dakun Lyu; Jiaqi Ge; et al. (Food Chemistry, 2026)

A Synergistic Botanical Compound Preparation of Ganoderma lucidum, Lycium ruthenicum, and Red Ginseng Alleviates Exercise-Induced Fatigue via Coordinated Regulation of Energy Metabolism, Oxidative Stress, and Gut Microbiota in Mice - Tao Liu; Mengmin Li; Wanyun Xu; Zhenhao Li; Yuanxiang Jin; Ting Luo; Tao Ma; Jintao Cheng; Shiyu Li; Qingchi Wang; Kan Shao; Yi Yang; et al. (Food Bioscience, 2026)

Association between residential greenness exposure and excessive gestational weight gain: A dual-center birth cohort study - Xuejin Li; Yanshen Zhang; Yijun Liu; Xiuping Dou; Man He; Yao Huang; Yang Su; Bingying Zhang; Weidong Luo; Qingmei Lin; Yongjun Shi; Boyi Yang; et al. (Environmental Research, 2026)

A synergistic metal ion–silane strategy enables fire-safe, water-repellent, and mold-resistant flattened bamboo board - Longchao Ma; Genmiao Wan; Yan Wang; Chenkai Dou; Danhe Liu; Yue Jiao; Hao Sun; Xinzhou Wang; Yi Chen; Qiliang Fu; Yanjun Li (Chemical Engineering Journal, 2026)

Effect of MWCNTs-Modified Anode on the Performance of SMFCs Contaminated Aviation Fuel Soil - Jinmei Bai; Yulei Song; Junbo Yao; Yuan Li; Haiying Guo; Xiangji Dou (Water, Air, & Soil Pollution, 2026)

Efficacy and Mechanisms of Combined Central-Peripheral Magnetic Stimulation on Prefrontal-Sensorimotor Cortex Connectivity in Post-Stroke Dysphagia after Supratentorial Stroke: A Randomized, Single-Blind, Parallel-Controlled Trial - Zirui Luo; Zhiying Zhu; Yujue Wang; Na Su; Yajing Xue; Wanqi Zhang; Wei Liao; Yaoyao You; Lin Ling; Mei Li; Junjie Liang; Zulin Dou; et al. (Translational Stroke Research, 2026)

Inflammatory response involved in cartilage degeneration induced by T-2 toxin: systematic review - Qian Li; Yikai Hu; Juan Zuo; Zaichao Dong; Tongtong Sha; Kangting Luo; Miao Wang; Huanxia Zhang; Yanjie Dou; Shuiyuan Yu; Fang-fang Yu (Mycotoxin Research, 2026)

Intermittent aeration-driven iron cycling for the remediation of waste pit-sealing mud: metabolic mechanisms and model evaluation - Xiangshan Zeng; Xinyi Wu; Dandan Yan; Changhui Hu; Jinlai Yuan; Ruiqi Li; Yan Wang; Ming Dou; Yafei Yang (Environmental Geochemistry and Health, 2026)

Ephedplics E-I: three lignans and two benzofuran-type compounds from the roots of Ephedra sinica Stapf and their neuroprotective activity - Yunlong Dou; Bowen Zhang; Meng Li; Xiaolan Wang; Shuyan Liu; Yanjun Sun; Xiaoke Zheng; Weisheng Feng (Journal of Natural Medicines, 2026)

Development of a Monthly Meteorological Drought Forecasting Model for Yunnan Using Machine Learning and Increment Method - Jianqin Zhou; Zizhen Dong; Yun Tao; Meng Li; Xiaodong Dou; Wei He; Mengying Pang (International Journal of Climatology, 2026)
Accurate prediction of meteorological drought can effectively reduce drought disaster risks and provide scientific support for disaster prevention and mitigation. Based on the 1‐month scale Standardized Precipitation Evapotranspiration Index (SPEI‐1) and 114 atmospheric circulation and sea surface temperature indices, this study employed three machine learning methods, including the Classification and Regression Tree (CART), Random Forest (RF) and Neural Network (NN), combined with a prediction increment method, to construct monthly meteorological drought prediction models for 125 meteorological stations in Yunnan Province, Southwest China. The main conclusions are as follows: (1) Time series validation indicates that the CART and NN models demonstrate predictive capability for monthly variations at approximately half of the stations and for meteorological drought occurrence at over 60% of the stations. The RF model achieves accuracies exceeding 60% and 75% for monthly variations and drought occurrence, respectively. The correlation coefficients between the predicted and observed SPEI‐1 values for the CART, RF and NN models are 0.53, 0.77 and 0.59, respectively, all significant at the 0.01 level, which can provide a reference for drought disaster prevention in Yunnan. (2) All three models perform best in predicting the no‐drought category, with 10‐year average accuracies exceeding 60%. The extreme drought category ranks second, with an average accuracy above 45%. The prediction accuracies for mild, moderate and severe drought are only approximately 19%. This is partly related to the sample sizes of these categories. More importantly, however, there exist relatively large mean absolute errors between the predicted and observed SPEI‐1 values, which should be the priority for future model improvement. (3) Spatial distribution validation shows that the RF model achieves same‐sign rates of predicted increments and meteorological drought accuracies above 65% and 70%, respectively, while the CART and NN models achieve rates above 50% and 60%, respectively. Regions with higher accuracies for all three models are mainly distributed in the dry‐hot valleys of the Jinsha River in central‐northern Yunnan and in southwestern regions that are significantly influenced by the Indian monsoon. (4) The CART and NN models achieve a probability of detection (POD) of 50% for province‐wide meteorological drought events during 2014–2024, while the RF model achieves 57%. All three models achieve POD above 60% for the spatial distribution of drought events, with higher POD regions located in central‐western Yunnan where drought events occur frequently and persist for longer durations. (5) Leave‐one‐out cross‐validation demonstrates that all three models can reasonably reproduce typical meteorological drought processes since 1971. The temporal and spatial correlation coefficients between the predicted and observed SPEI‐1 values are close to or exceed 0.50, all significant at the 0.01 level. (6) Overall, the RF model outperforms the CART and NN models in predicting 1‐month scale meteorological drought in Yunnan.

Adaptive fusion of acceleration and velocity records using machine learning for improved ground motion modeling - Mianshui Rong; Qingxu Zhao; Bin Zhang; Aixia Dou; Jixin Wang; Xiaoshan Kong; Xiaojun Li (Soil Dynamics and Earthquake Engineering, 2026)

Numerical study on the VIV response of a deep-sea mining riser considering time-varying axial tension and the combined effects of internal and external flows - Yan Li; Wenhua Li; Xingkun Zhou; Yaning Dou; Xiantao Zhang (Ocean Engineering, 2026)

Pulmonary effect of 2D MXenes in mice: Immune cell responses and disrupted hematopoiesis - Gang Tang; Min Li; Jiexia Cheng; Ziniu Wang; Guangxuan Wang; Jianbo Shi; Jonathan W.C. Wong; Jie Gao; Dou Wang; Guohao Zhang; Li Zeng; Yanhua Wang; et al. (NanoImpact, 2026)

Long-term biocrust restoration enhances microbial carbon use efficiency but shifts soil organic carbon sequestration pathways - Weiqiang Dou; Xinrong Li (Journal of Environmental Management, 2026)

Characteristics of VOCs and sulfur-containing compounds: Environmental and health implications in odor complaint hotspots of Chengdu, China - Guiying You; Liqiu Huang; Hefan Liu; Xiaoya Dou; Rui Sun; Jiaxin Wei; Jing Li (Journal of Environmental Sciences, 2026)

Chronology, chemical weathering intensity, and environmental implications of Aeolian deposits on the Yellow River terrace, Northeastern Tibetan Plateau - Dou Chen; Jiangli Pang; Chunchang Huang; Yili Zhou; Xiaochun Zha; Yuqin Li; Yuzhu Zhang; Xiaokang Zhao; Xinyu Wang (Journal of Asian Earth Sciences, 2026)

Experimental study on combustion characteristics in a low-pressure direct-injection hydrogen engine - Tong Ge; Jinguang Li; Minghao Zhu; Fulai Zhao; Zhancheng Dou; Haiqiao Wei; Jiaying Pan (Fuel, 2026)

Surface charge engineering improves the alkaline resistance of Pseudoalteromonas tetraodonis κ-carrageenase for application in hydrolysis of κ-carrageenan industrial waste residues - Yu Su; Qingsong Hu; Zuman Dou; Tao Hong; Mingjing Zheng; Zhipeng Li; Lijun Li; Zedong Jiang; Hui Ni; Yanbing Zhu (Food Research International, 2026)

InSAR analysis of landslide evolution in the Baihetan Reservoir: Impoundment effects and response to combined reservoir–rainfall forcing - Lele Zhang; Jie Dou; Changdong Li; Yiwen Yang; Aonan Dong; Zilin Xiang; Ke Xing (Engineering Geology, 2026)

The pore structure regulation targeting the co-enhanced kinetics and mass transfer for improving electrochemical oxidation performance - Xiang Wang; Jinjie Dou; Zejun Deng; Guoling Peng; Kechao Zhou; Qiuping Wei; Li Ma (Chemical Engineering Journal, 2026)

Transcriptomics and network pharmacology reveal that baicalin alleviates acute lung injury induced by H1N1 via targeting STAT1 - Wenxiang He; Yufeng Dou; Hui Ji; Xia Li; Pengbo Liang; Xiaoli Liu (Archives of Microbiology, 2026)

Prenatal Chromium Exposure and Gestational Diabetes Mellitus: Integrating Genetic and Epigenetic Regulation of LPCAT1 from a Phospholipid Remodeling Perspective - Yuxin Tian; Lu Yao; Jiaqi Zhang; Meng Zhou; Yue Dou; Bole Zhang; Yulin Li; Yongliang Feng; Yawei Zhang; Suping Wang; Weiwei Wu (Biological Trace Element Research, 2026)

Coupled Petrophysical Response and Flow Process in Tight Sandstone: During Massive Liquid Injection - Zhuoying Dou; Zhengming Yang; Haibo Li; Hang Yuan; Chenyu Han (Rock Mechanics and Rock Engineering, 2026)

E-Syt1 recruits PI4KA to endoplasmic reticulum-plasma membrane junctions to enhance PI4P synthesis - Chunfang Tong; Ranran Mao; Dou Wang; Jing Xi; Min Su; Wenfeng Fu; Dong Li; Jia-Jia Liu (Science China Life Sciences, 2026)

Highland Barley's future: Processing innovation empowers emerging opportunities in global health foods and sustainable agriculture - Xinlai Dou; Luman Sang; Liangxing Zhao; Yiqing Zhu; Shumin Shu; Yan Zhang; Jing Ou; Hongying Hua; Ge Li; Yong Xue; Qingyu Zhao; Chao Wang; et al. (Trends in Food Science & Technology, 2026)

Aloperine alleviates lung ischemia-reperfusion injury by modulating ferroptosis via the STAT-1 pathway - Junshen Xiao; Shichao Wei; Dou Huang; Yan Cheng; Huan Li; Hangxue Cao; Zhaoyang Hu (Toxicology and Applied Pharmacology, 2026)

Rapid bactericidal and nematicidal activity of a ternary quaternary ammonium formulation via membrane disruption in bacteria and cuticle damage in Bursaphelenchus xylophilus - Mengyao Li; Yuewen Dou; Yongchao Zheng; Lingce Kong; Yan Cui; Likun Chen; Bin Wu; Kai Guo; Chonglin Zhao; Shaojie Han (Pesticide Biochemistry and Physiology, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

MnTiO3 catalytic ceramic membrane built and enhance PMS oxidation capacity: Experimental and theoretical calculation - Guangxu Zhang; Jin Wang; Mengmeng Dou; Wubin Wang; Chao Han; Yadong Hu; Xinyu Li; Kaibo Wang; Yaxuan Liu; Yuting Ma; Xin Zhang (Journal of Water Process Engineering, 2026)

Synergistic effect in Pr-doped MnOx for chlorobenzene oxidation: Tuning oxygen vacancies and Mn valency - Zebing Li; Zhongxian Song; Yanli Mao; Yanyan Dou; Xuejun Zhang; Yanhui Yang; Zhenzhen Huang; Xuejun Duan (Journal of Environmental Chemical Engineering, 2026)

Point defects as a control on the viscosity jump in the lower mantle - Peixue Dou; John Brodholt; Lidunka Vočadlo; Yunguo Li; Huaiwei Ni (Earth and Planetary Science Letters, 2026)

From AC to DC droplet energy systems: Evolution of energy transfer mechanisms enables high-efficiency self-powered energy-sensing microsystem - Zilong Dou; Lili Zhu; Yuexiao Hu; Jianxi Ren; Zichuan Xu; Lichun Zhang; Meishan Wang; Kuiliang Gong; Weimin Li; Gang Ma; Hengyu Guo; Renyun Zhang; et al. (Chemical Engineering Journal, 2026)

New mesoporous UiO-66-OH framework with in-situ grown CsPbBr3 perovskite nanocrystals as a multifunctional sensor for the discrimination and instrument-free detection of three natural food additives - Hou-Qun Yuan; Qian-Wen Yang; Ling-Yi Guo; Yao-Hong Wang; Guan-Qun Li; Qiong-Yue Cui; Zhen-Chong Dou; Zhi-Qiang Cai; Yi-Fan Xia; Guang-Ming Bao (Chemical Engineering Journal, 2026)

Improving sweet sorghum bagasse silage quality by adding Lactobacillus plantarum and Pichia anomala: Insights from multi-omics analysis - Haiwei Ren; Yongpeng Du; Jucai Dou; Xiaopeng Guo; Yi Zhao; Jinping Li; Yu Wang; Dong Lu; Yi Zheng (Biomass and Bioenergy, 2026)

When to pair surrogate species: A cost-scaling rule for conservation efficiency - Minyi Kau; Lingyun Xiao; Xueyang Li; Yanlin Liu; Sheng Li; Lu Zhang; Yuehan Dou; Daiying Jin; Zhi Lu; Juan Li (Biological Conservation, 2026)

Correction: Preclinical Evaluation of AAV8-R338L Gene Therapy for Hemophilia: Efficacy, Pharmacokinetics, Distribution, Excretion and Toxicity in Mouse Models and Non-human Primates - Dehu Dou; Jing Lu; Deli Li; Fengxia He; Xi Zhu; Xuefeng Zhang; Xijing Chen (Pharmaceutical Research, 2026)

Adverse event profiles of fenofibrate and gemfibrozil: a retrospective comparative study and literature synthesis - Jing Song; Chong-Yang Dou; Xiao-Min Chen; Jie Hu; Feng Xu; Liu-Cheng Li; Jiang Li; Qiu Jiang; Wei Zheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Immune Checkpoint Inhibitor–Associated Cardiovascular Toxicity: Mechanisms, Clinical Manifestations, and Clinical Impact - Zhengyu Chen; Meijie Zheng; Yuxuan Li; Xiwu Zhang; Jinjin Dou (Cardiovascular Toxicology, 2026)

Comparative Analyses of Growth and Survival of ‘Haida No. 1’ and Wild Crassostrea gigas Pacific Oysters and Their Hybrids - Kunyin Jiang; Fangjian Dou; Chengxun Xu; Haijun Liu; Qi Li (Journal of Ocean University of China, 2026)

Enhanced heatwaves exacerbate survival risks for vulnerable populations - Yan Dou; Jialei Zhu; Xi Zhao; Lehui Cui; Hao Liu; Yixin Huang; Li Yang (Anthropocene, 2026)

The GHK-Cu delays aging in Caenorhabditis elegans via coordinated regulation of mitochondrial function and activation of DAF-16/SKN-1 pathways - Huijun Wen; Keshu Zhao; Xiangjian Luo; Jian Pu; Yixin Li; Yi Dou; Jie He; Xinyu Nie; Yuan Ke; Wenhui Zhou (Biogerontology, 2026)

Petrogenesis and geodynamic mechanism of Indosinian magmatism in South China Block: Insights from the Neihan–Deqing–Hetai Granitic Belt, western Guangdong - Jianrong Wang; Zhipeng Xie; Wenchang Li; Chuandong Xue; Lei Dou; Hongwei Zhao; Wei Wang; Xingwang Song (Acta Geochimica, 2026)

Mass and Energy Balance-Oriented Allocation Mechanism for Petrochemical Product Carbon Footprint - Lili Sun; Hongju Chen; Hetian Zhu; Xiaotong Li; Jiaming Gu; Yinghui Han; Guofei Shen; Yunhu Gao; Baojuan Dou; Chong Wei; Qun Shen; Wei Wei (Aerosol Science and Engineering, 2026)

Effects of dietary chitosan oligosaccharide on juvenile grass carp: Insight from the intestinal microbiota and metabolism - Yong Dou; Liuyang Cheng; Guihai Yu; Peize Li; Hongxu Cao; Xiangdong Bi; Wenli Zhou (Journal of Fish Biology, 2026)
Nowadays, chitosan oligosaccharide (COS) served as a feed additive has been gradually applied to aquaculture. In aims to reveal the effects of COS on the growth intestinal microbiota and metabolism of Grass carp, this experiment using the feed with 3% COS supplement was conducted. The results indicated that the growth indicators (WGR and SGR) of Grass carp were promoted significantly ( p Cetobacterium , Plesiomonas and Brevinema were enriched in the COS treatment, and the intestinal microbiota profile was improved through increasing the abundance of beneficial bacteria ( Cetobacterium ). Besides, a series of lysophosphatidylcholine (LPC) (LPC 16:2, LPC 14:0, LPC 19:2, LPC 19:1, LPC O‐16:2), lysophosphatidylethanolamine (LPE) (LPE 16:2 and LPE O‐16:2) and a butanoic acid derivative named 3‐[4‐methyl‐1‐(2‐methylpropanoyl)‐3‐oxocyclohexyl]butanoic acid were up‐regulated, and two long chain fatty acyl‐CoA (LPG) (LPG 20:2 and LPG 18:0) and LPS 20:3 belonging to lipopolysaccharide (LPS) down‐regulated in the COS treatment. Therefore the result implied that the intestinal health of Grass carp would be protected via reducing the LPS induced the intestinal oxidative stress and inflammatory injury in fish. The metabolic pathways enriched in the profile between the COS treatment and control were mainly concentrated on lipid and derivative metabolism, amino acid metabolism, carbohydrate metabolism and ones associated to the signal transduction. Based on the correlation analysis, butanoic acid was identified as the metabolic marker related to Cetobacterium and Plesiomonas , while LPC O‐16:2 was determined as the biomarker associated to Brevinema. Therefore, the application of COS gives promising results and will be a green feed additive in aquaculture.

The dual role and mechanism of insoluble humic substances governing the fate of Cu in sediments: Rapid accumulation and long-term stabilization - Weifang Huang; Luming Dou; Xueting Pu; Meng Chen; Yi Chen; Longguo Li; Jun Li; Naiwen Li; Chao Liu; Bo Lai (Water Research, 2026)

Chemically converted volume-resilience interface enables high-capacity zinc anode - Mingzhu Li; Xinyue Dou; Zhexuan Liu; Yaping Wang; Shuquan Liang; Guozhao Fang (Science Bulletin, 2026)

Extreme rainfall intensifies nitrogen responses through baseflow in arid and semi-arid river basins - Jinghui Dou; Rui Xia; Zixuan Tang; Zhen Huang; Xiaohui Jiang; Kai Zhang; Lina Li; Chao Yan (Journal of Hydrology, 2026)

Divergent response of vegetation structure to land-atmosphere droughts across aridity gradients in the Northern Hemisphere - Bingxin Ma; Longhui Li; Yue Zhang; Yueyue Dou; Lin Yu (Global and Planetary Change, 2026)

Nano-confinement effect on multi-mechanistic CO2-CH4 transport in coal: Upscaling from molecular dynamics to core experiments - Wenfeng Guang; Xiaoqian Liu; Zhenyu Zhang; Yunpeng Lu; Haoran Dou; Dayong Li; Hang Li (Gas Science and Engineering, 2026)

Partial NaCl replacement with arginine during brining influences apoptosis and post-brining quality of grass carp fillets - Xin Xiong; Qing Li; Peipei Dou; Tianzhuo Huang; Shuai Zhuang; Yuqing Tan; Huawei Ma; Hui Hong; Yongkang Luo (Food Chemistry, 2026)

Heteroaptamer recognition mediated strand displacement amplification for efficient electrochemical analysis of beta-2-microglobulin in breast milk - Yaqin Tang; Tingting He; Linwei Pan; Yanni Wang; Xiaolong Li; Xia Zhao; Daxiu Li; Baoting Dou (Food Chemistry, 2026)

Dietary xylo-oligosaccharides improve lamb meat quality by modulating nutritional and volatile profiles - Jiaxin Yang; Xueru Dou; Wanhang Jia; Binglei Zhang; Saiyi Sun; Qiujue Wu; Yuanxiao Li; Wenfeng Ma; Xiaoyin Zhang; Guoyan Ren; Tianlong Guo; Yuqin Wang (Food and Humanity, 2026)

HOPO-functionalized MXene self-supporting membrane for highly efficient and selective uranium extraction from radioactive wastewater - Jiaxin Li; Yinlu Dong; Yu Wang; Xiangcao Chang; Jicui Wen; Yuhang Zhang; Wenhua Zhu; Lichan Xiao; Ruohan Guo; Chaoran Li; Zhiyun Meng; Ruolan Gu; et al. (Chemical Engineering Journal, 2026)

Unraveling the stepwise mechanism of SO4•−–Initiated oxidative degradation of HFPO oligomers: A Theoretical and experimental study - Xu Liu; Xuan Dou; Deyan Li; Boxue Pang; Hui Li; Yang Wu; Delin Qi; Wei Wang (Chemical Engineering Journal, 2026)

Fe-Ni-MOF-derived NiFe2O4/NiO heterostructure for detection of 2-CEES at ppb level - Duo Zhang; Ying-Nan Dou; Rui Gao; Xian-Fa Zhang; Hui Zhao; Xiao-Li Cheng; Shan Gao; Ying-Ming Xu; Li-Hua Huo (Chemical Engineering Journal, 2026)

Scalable dry-processing of ceramic-polymer composite flexible passive daytime radiative cooling films - Zhongyin Tian; Kai Zhang; Xiangyu Tong; Sheng Lu; Yongchao Yu; Yiqian Zhou; Hsiang-Shun Chang; Yan Feng; Yunzhi Li; Xiaowen Chen; Guangyu Yang; Shihang Li; et al. (Chemical Engineering Journal, 2026)

miR-133a-3p promotes T-2 toxin-induced chondrocyte damage via targeting IGF1R - Kangting Luo; Lingyu Wang; Zhengyan Zhang; Yikai Hu; Chengyu Zhao; Shuiyuan Yu; Qian Li; Zaichao Dong; Tongtong Sha; Miao Wang; Juan Zuo; Yanjie Dou; et al. (Chemico-Biological Interactions, 2026)

Preparation, Characteristics, Antioxidant and Anti-Inflammatory Activity of SeNPs and ZnO-enriched Limosilactobacillus reuteri LR1 - Runan Zhang; Shanyao Pi; Jiajing Chang; Xiaonan Zeng; Hui Shen; Tiantian Li; Qianqian Gao; Xina Dou; Chunlan Xu (Probiotics and Antimicrobial Proteins, 2026)

Mechanism and movement process of the '2.8' rock avalanche in Junlian County, Southwest China - Yongjian Bai; Yueping Yin; Dou Hongjie; Linfeng Gong; Xiaohui Xiong; Xu Wei; Yanchao Gao; Yongbo Tie; Qi Li; Sainan Zhu; Xue Huang (Landslides, 2026)

From Failure Mechanisms to Interpretable Assessment: Stability Degradation of Deep Excavations Near Existing Buildings - Zheng Liu; Ting Yu; Wei Li; Jie Dou; Shuoliangyuan Liu; Luqiang Ding (Geotechnical and Geological Engineering, 2026)

MoS2 nanosheets assembly on Sb-SnO2 modified kaolinite nanoflakes for efficient catalytic hydrogenation - Xiaoyu Li; Wenqing Zhang; Kang Peng; Zheng Zhou; Yewei Dou; Jianguo Feng (Applied Clay Science, 2026)

Functional Breakdown of Temporoparietal Junction Interaction in High-depression Individuals: Evidence from Multi-Metric Connectomics - Xiaotong Wen; Yao Fengge; Bin Han; Guodong Wei; Yuehan Gao; Yuying Chen; Ziyu Hao; Huanhuan Li; Fengyu Dou (Brain Structure and Function, 2026)

17β-Estradiol alleviates cognitive deficits by modulating fear memory reconsolidation in a PTSD rat model - Han Wang; Han Lin; Zilong Zhong; Baoying Jiang; Siyi Li; Jiahao Tang; Xiaoping Zhou; Guohui Zhu; Yang Liu; Wenhao Han; Jinhua Dou; Lin Sun (Psychopharmacology, 2026)

Targeting angiopoietin-like protein 3 and interleukin-1β alleviated liver and kidney injury through attenuation of lipotoxicity and regulation of glycolipid metabolism in db/db mice - Shuwen Xu; Longfei Wang; Zihan Dou; Xiaozhi Hu; Zhonglian Cao; Yuanzhen Zhang; Xianhan Jiang; Tao Wu; Zhuojin Li; Yanyang Nan; An Zhu; Yu Bai; et al. (Inflammation Research, 2026)

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Sentinel-2-Based monitoring of abandoned croplands and spatial heterogeneity analysis in arid Northwest China: a Case study of the Hexi Corridor, Gansu Province - Xiuxia Zhang; Aixia Dou; Lingzhi Deng; Heng Du; Wangping Li; Zhaoye Zhou; Linyan Gao; Zaoliang Gao (International Journal of Remote Sensing, 2026)

A novel method for cleaning molten copper slag and efficiently recovering copper resources through reduction modification - Biao Kuang; Cao Tan; Feifei Li; Jianhang Hu; Zhihe Dou; Yong Yu; Huimin Gao; Hua Wang (Process Safety and Environmental Protection, 2026)

Scour mechanism and efficiency contrast between under-expanded and expanded air jets in underwater - Yaohui Qiang; Yanchong Duan; Liekai Cao; Dejun Zhu; Jian Jiao; Lei Ding; Xiping Dou; Danxun Li (Ocean Engineering, 2026)

Comparative assessment of reproductive and intergenerational toxicity of perfluorooctanoic acid and hexafluoropropylene oxide trimer acid in zebrafish (Danio rerio) - Shenggan Wu; Xuehua An; Ting Xu; Dou Wang; Zhenlan Xu; Yuanxiang Jin; Xinquan Wang; Yun Li; Yanhua Wang (Journal of Hazardous Materials, 2026)

Nanoarchitectonics of atomically dispersed Ag-anchored g-C3N4 nanosheets for visual photosensitization sensing of chlorophenols at ng level - Zhongyuan Wang; Yang Qu; Binhong Qu; Zhijun Li; Tianwei Dou; Zhiyu Ren; Liqiang Jing (Journal of Environmental Chemical Engineering, 2026)

Optimal scheduling of mixed conventional and modular autonomous bus fleets for sustainable urban transit - Xueping Dou; Ran Dong; Yuqi Lin; Tongfei Li (Journal of Cleaner Production, 2026)

Analysis of the “South-High North-Low” phenomenon of aerosol distribution and its characteristics in the Beijing plain area - Jie Su; Ju Li; Jingjiang Zhang; Junxia Dou; Youjun Dou; Shaoying Shi; Yaoting Wang; Yao Wang; Zhigang Cheng; Wenlong Zhang (Atmospheric Pollution Research, 2026)

MnO2/CNT-Modified Anode Microbial Fuel Cells for Removing Varying Amounts of Cu2+ from Wastewater - Jiahui Zhu; Lingling Li; Jun Zhou; Nasha Dou; Lei Gong; Mingjing Li; Hui Tan; Ping Yang; Wenfeng Wang (Water, Air, & Soil Pollution, 2026)

Positive shrub-soil feedbacks enhance growth of alpine juniper shrubs in the central Himalayas - Jayram Pandey; Shalik Ram Sigdel; Dou Li; Xiaoming Lu; J. Julio Camarero; Eryuan Liang (Plant and Soil, 2026)

Non-covalent proteasome inhibitor PI1840 suppresses osteoclastogenesis and prevents LPS-induced osteolysis in mice - Yehua Xia; Fuli Zhao; Cheng Dang; Jiayi Bai; Yueqiang Li; Jiaxue Yang; Qiuyi You; Qiang Tang; Wenwen Dou; Mei Liu (Inflammopharmacology, 2026)

Unveiling the adsorptive/catalytic roles of micro-carbon sphere materials in antibiotic removal: Current status and perspectives - Ning Wang; Wang-mi Chen; Qi Zhou; Yu Dong; Ming-xiao Li; Bei-dou Xi; Jia-qi Hou; Zhen-tao Cui (Water Research, 2026)

Unraveling the distribution and stability of deep soil organic carbon after long-term conservation tillage practices - Jianye Li; Yong Zhu; Na Li; Yunying Fang; Xiaolin Dou; Yuanyuan Lu; Xingyi Zhang; Bojie Fu; Chunlong Liu; Shuguang Liu; Xinqiang Liang (Soil and Tillage Research, 2026)

Taurine modulates gut microbiota and attenuates inﬂammation in a rotenone-induced mouse model of Parkinson's disease - Yunbo Zhu; Shuo Wang; Shuang Zhao; Yujia Zeng; Jing Li; Pingyue Wang; Zhijie Dou; Tianjun Wang (NeuroToxicology, 2026)

Deformation evolution of the rifting and positive inversion in the Central African Shear Zone: Insights from Analogue Modelling - Lirong Dou; Xinshun Zhang; Chuanbo Shen; Yebo Du; Li Wang; Xiang Ge; Huahua Gao; Yu Yang (Journal of Structural Geology, 2026)

Tuning crystal structures of Mn nanomaterials on Enteromorpha prolifera biochar to enhance seawater purification - Guiping Jiang; Yingchao Li; Xianshuai Niu; Hanqi Liu; Xiaobo Wang; Kunpeng Dou; Jun Wang; Peng Ju (Journal of Environmental Management, 2026)

The different responses and their underlying mechanisms of the O3 concentrations during the Hangzhou Asian Games - Ningning Yao; Xuedan Dou; Yanfei Liu; Lang Chen; Zhe Song; Huan Xi; Zhengnan Cen; Jian Li; Zhenyu Gu; Pengfei Li; Shaocai Yu (Journal of Environmental Sciences, 2026)

A novel transformer-based CO2 retrieval framework incorporating prior constraint and hierarchical features injection: assessment of transferability for Tansat-2 - Lingfeng Zhang; Lu Zhang; Xingying Zhang; Tiantao Cheng; Xifeng Cao; Tongwen Li; Dongdong Liu; Yang Zhang; Yuhan Jiang; Ruohua Hu; Haiyang Dou; Lin Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Study on the mechanism evolution of carbon structure during blending coal coking - Hanwen Zhu; Peng Yu; Xinni Zhao; Lu Tian; Hua Li; Xingxing Chen; Jinxiao Dou; Jianglong Yu (Fuel, 2026)

Pyrolysis behavior of solvent-extracted group components from coking coal: Insights into volatile release and source contributions to coke formation - Tingting Zhang; Xingjin Zhang; Haoyu Dou; Shujun Wang; Zongqing Bai; Jin Bai; Wen Li (Fuel, 2026)

New insight into the structural factors affecting retrogradation of potato starch and Chinese yam polysaccharide blend using asymmetrical flow field-flow fractionation coupled with multidetector - Mu Wang; Liu Yang; Tinghui Yin; Yao Huang; Zihan Zhang; Yueqiu Li; Haiyang Dou (Food Hydrocolloids, 2026)

Cellulose nanocrystals engineered TiVCTx MXene film for ultrafast energy-sensing systems - Zhemin Li; Dewei Xiao; Yinghong Xu; Hai Xu; Lanxin Yan; Hui Dou; Xiaogang Zhang (Chemical Engineering Journal, 2026)

Electronic structure tuning of Mn-based high-entropy spinel boosts benzene catalytic oxidation - Jiarui Chen; Xiaotong Li; Junjie Feng; Linlin Deng; Mingtai Li; Baojuan Dou; Feng Bin (Chemical Engineering Journal, 2026)

Polysaccharides from Syzygium aromaticum binding to 3CLpro contain glycoproteins interacting with RdRp against SARS-CoV-2 - Can Jin; Bo Feng; Pengfei Dou; Yuan Zhou; Tingting Guo; Yuxuan Liu; Yaqi Ding; Meixia Li; Xia Chen; Zhenyun Du; Chunfan Huang; Xuan Li; et al. (Carbohydrate Polymers, 2026)

Multiple-stage evolution of the Cenozoic ductile deformation in the Tethyan orogenic belt constrained via single-grain mica Rb Sr isochron ages - Weiyong Li; Dongyang Huo; Shuhao Tang; Chengzhang Dou; Jun He; Fukun Chen (Chemical Geology, 2026)

Response of maize yield to soil management practices: a global meta-analysis - Mekuannet Belay; Changlu Hu; Victor Sadras; Zhaodong Wang; Wenning Wang; Ye Zhang; Liurong Li; Chunyu Dou; Yanfei Xue; Xueyun Yang; Juanni He; Shulan Zhang (Plant and Soil, 2026)

PK/PD study of ceftazidime/avibactam in patients with severe intra-abdominal infections treated by continuous veno–venous hemofiltration - Sai Tian; Yong Chen; Mingjie Qiu; Wenqi Wu; Liuqing Dou; Jiajie Wang; Li Xu; Zhitao Zhou; Meilin Wu; Jiayang Li; Xiuwen Wu; Jianan Ren (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Mechanism of liver fibrosis induced by life-long triclosan exposure in offspring rats: an adverse outcome pathway framework validated by in vivo and in vitro experiments - Fu Liu; Jianing Shang; Linlin Zheng; Xiaoyu Zhang; Anqi Cui; Xue Dou; Yunwei Li; Jieyu Liu (Archives of Toxicology, 2026)

The impact of seasonal environmental changes on coral restoration’s improvement of biological and carbonate carbon pumps - He Zhao; Yicheng Liu; Pei Yang; Wanze Dou; Xiangbo Liu; Wentao Zhu; Aimin Wang; Xiubao Li (Acta Oceanologica Sinica, 2026)

Reinforcement-Learning-Based Adaptive PID Depth Control for Underwater Vehicles Against Buoyancy Variations - Jian Wang; Shuxue Yan; Honghao Bao; Cong Chen; Deyong Yu; Jixu Li; Xi Chen; Rui Dou; Yuangui Tang; Shuo Li (Journal of Marine Science and Engineering, 2026)
Underwater vehicles performing sampling tasks often encounter significant buoyancy variations due to payload adjustments and environmental changes, which severely challenge the stability and accuracy of controllers. To address this issue, this paper proposes a hybrid control framework that integrates Proximal Policy Optimization (PPO) with adaptive PID tuning. The framework employs PPO to dynamically adjust PID parameters online while incorporating output saturation, stepwise quantization, and dead zone filtering to ensure control safety and actuator longevity. A dual-error state representation—combining instantaneous error and its derivative—along with actuator command buffering is introduced to compensate for system lag and inertia. Comparative simulations and experimental tests demonstrate that the proposed method achieves faster convergence, lower steady-state error, and smoother control signals compared to both conventional PID and pure PPO-based control. The framework is validated through pool tests and field trials, confirming its robustness under realistic hydrodynamic disturbances. This work provides a practical and safe solution for adaptive depth control of sampling-capable AUVs operating in dynamic underwater environments.

Precision variable-rate fertilizer application method based on real-time field soil electrical conductivity sensing - Hanjie Dou; Lina Hu; Yanlong Zhang; Changyuan Zhai; Si Li; Liping Chen (Computers and Electronics in Agriculture, 2026)

TBL2 modulates glioblastoma progression by inducing autophagy through by the AMPK/mTOR signaling pathway - Shan Wang; Hang Meng; Xia Dou; Lingyu Kong; Wenjing Wang; Mengnan Hou; Yan Yan; Bin Li; Tianbo Jin (Tissue and Cell, 2026)

Microplastics enhance soil nitrogen availability by stimulating nitrogen-acquiring enzyme activity over three decades-long fertilization regimes - Lin Han; Jingjie Dou; Kai Zhu; Lu-Jun Li; Peng He; Xiaowei Wei; Xiaojing Hu; Yueyu Sui; Xiangxiang Hao; Xuechen Yang (Soil and Tillage Research, 2026)

How international trade shapes critical material demand in electric vehicle batteries - Zhenyu Dong; Han Hao; Xin Sun; Boyu Liu; Hao Dou; Haoyang Li; Ming Liu; Fuquan Zhao; Zongwei Liu (Resources, Conservation and Recycling, 2026)

Ethylene-induced postharvest ‘Guifei’ mango peel coloration: Activation of the MiPAL1 promoter by MiERF5 and the MiERF5-MiMYB7 complex - Xin Wang; Yaqi Dou; Yu Wang; Pan Guo; Yuanhui Gao; Jinhe Li; Yuanzhi Shao; Wen Li (Postharvest Biology and Technology, 2026)

Photochemical release characteristics of particle-bound mercury in the atmosphere and its influencing factors - Yuting Liu; Dou Li; Yan Wang; Yuqing Zhang; Yahui Qiu; Fengzhu Zhou; Yuejiao Li; Ruhai Liu (Journal of Hazardous Materials, 2026)

Constructing Ce–O–C covalent-bridged S-scheme heterojunction via molten-salt transformation of Ce-MOF for photocatalytic overall H2O2 synthesis - Ziying Feng; Pengjia Li; Dou Yang; Jingyi Yu; Yunyun Gui; Shao-Chuan Li; Yuan Lin; Junhua Zou; Lijun Liu (Journal of Environmental Chemical Engineering, 2026)

Advanced composting simulation technologies: A systematic review of methodological frameworks and applications - Ming-xiao Li; Ning Wang; Yuan-yuan Xie; Mei-ying Ye; Bei-dou Xi; Wang-mi Chen; Qi Zhou; Jian-long Hu; Jia-qi Hou (Journal of Environmental Management, 2026)

Electron localization assisted by hexagonal tube stacked structure of P-g-C3N4 targeting to achieve defluorination reaction: The reduction of excitation energy and stability of pollutants - Mengmeng Dou; Guangxu Zhang; Jin Wang; Boru Gao; Xin Zhang; Xinyu Li; Yadong Hu; Kaibo Wang; Yuqi Liu; Meng Luo; Yuhao Wang (Journal of Environmental Chemical Engineering, 2026)

Polyetheramine-derived hydrophobic di-cationic ionic liquids for moisture tolerant and selective SF₆ recovery - Yi Pan; Fengyu Fu; Yu Dou; Bin He; Zhiyan Ma; Panpan Mi; Ping He; Wei Kou; Changli Li; Lixin Xia (Journal of Environmental Chemical Engineering, 2026)

Confining pressure effects on mining-induced unloading failure characteristics along a rough fault: Experimental and numerical investigations - Minghe Ju; Han Zhu; Liyuan Yu; Yang Zou; Xin Peng; Linming Dou; Qiang Zhang; Xiaofeng Li (International Journal of Rock Mechanics and Mining Sciences, 2026)

Molecular insight into the structure and formation mechanism of fluid phase in the classical coking theory - Bo Gong; Jie-Ping Wang; Hao-Dong Liu; Rui Guo; Jin-Xiao Dou; Guang-Yue Li; Ying-Hua Liang (Fuel, 2026)

Dibutyl phthalate (DBP) induces cervical injury and promotes malignant transformation of cervical epithelial cells - Xue Chen; Shizhi Wang; Bo Ding; Yamei Nie; Fengying Liu; Xing Zhang; Bingjia Yu; Xiuting Li; Jianrui Dou; Wei Sun; Xin Zhou (Food and Chemical Toxicology, 2026)

Graphene-interfaced h-BN memristor for reliable computing and secure encryption - Ruoyao Sun; Chao Dou; Yan Wang; Haoyue Lu; Xuan Deng; Yueying Li; Liefeng Feng; Jing Liu (Chemical Engineering Journal, 2026)

Vertical layered double hydroxide array-assisted bidirectional regulation of high-performance polyamide nanofiltration membrane - Zeya Yang; Tianyong Liu; Biao Li; Yibo Dou; Xin Zhang; Jingbin Han (Chemical Engineering Journal, 2026)

Engineering the cathode: Key to unlocking the potential of potassium-ion batteries - Yu Dong; Ning Wang; Wang-mi Chen; Qi Zhou; Ming-xiao Li; Zhen-tao Cui; Jia-qi Hou; Wen-lin Ruan; Bei-dou Xi (Chemical Engineering Journal, 2026)

Vapor pretreatment-mediated crystal quality optimization for all-vacuum-processed monolithic perovskite/silicon tandem solar cells - Yichen Dou; Changyu Duan; Shenghan Hu; Xinyu Deng; Yuanyuan Chen; Anqi Kong; Yong Peng; Xiong Li; Zhiliang Ku (Chemical Engineering Journal, 2026)

A high-sensitivity and wide-range SAW humidity sensor based on graphene oxide/chitosan composite film for real-time respiratory and skin monitoring - Honghao Wang; Cuiping Li; Dan Li; Lirong Qian; Yawen Dou; Haisheng Tong; Baozeng Zhou; Huiyan Li; Litian Wang; Mingji Li; Hongji Li (Chemical Engineering Journal, 2026)

Characterization of an AA10 lytic polysaccharide monooxygenase from Micromonospora aurantiaca and its synergistic mechanism with chitinase in boosting chitin conversion - Hanzhong Guo; Dou Wang; Lifan Zhu; Yongcheng Li; Guanghua Xia; Xueying Zhang (Carbohydrate Polymers, 2026)

Sequential oxygen intervention drives novel AOB-DGAOs interaction network enabling advanced nitrogen removal in simultaneous partial nitrification and endogenous denitrification (SPNED) process - Li Zhang; Yiqing Zhang; Yu-You Li; Quanhao Dou; Yongzhen Peng (Bioresource Technology, 2026)

Herder cooperatives vs. independent herders in Inner Mongolia: A comparative analysis of multi-dimensional efficiency - Jiuzhou Jin; Ruiyao Zhang; Pengpeng Dou; Rong Zhi; Ping Li (Agricultural Systems, 2026)

SETD2 inhibited T-cell acute lymphocytic leukemia invasion and infiltration by inhibiting the JAK/STAT pathway - Ling Qiu; Shihui Ren; Mengjiao Li; Baitao Dou; Dan Chen; Nan Zhang; Jiao Cai; Hao Yao; Fangyi Fan (Molecular and Cellular Biochemistry, 2026)

Microplastics and nanoplastics, emerging pollutants, increased the risk of pulmonary fibrosis in vivo and in vitro: A comparative evaluation of their potential toxicity effects with different polymers and size - Jia-Yi Dou; Sen Liu; Chen-Yu Wang; Xu Dai; Li-Hua Lian; Zhen-Yu Cui; Ji-Xing Nan; Yan-Ling Wu (Toxicology, 2026)

Resilience of soil organic carbon under precipitation variability: Insights from carbon-nitrogen dynamics in semi-arid grasslands - Na Li; Baorong Wang; Qian Huang; Zhaolong Zhu; Yanxing Dou; Feng Jiao; Shaoshan An (Soil and Tillage Research, 2026)

Streetlight density and quantity estimation using glimmer images from SDGSAT-1 - Ziqi Yin; Mingquan Wu; Zheng Niu; Li Wang; Changyong Dou (Remote Sensing of Environment, 2026)

Interpretable machine learning model based on floc images for monitoring the coagulation process - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Peng Guo; Chuanchuan Dou; Wangben Zhao (Process Safety and Environmental Protection, 2026)

Nonlinear microbial nutrient limitation responses to biodegradable vs. conventional microplastics under long-term agricultural management - Jingjie Dou; Lin Han; Xiaojing Hu; Lu-Jun Li; Peng He; Junhui Wang; Xiangxiang Hao; Yueyu Sui; Wei Sun; Xuechen Yang (Journal of Hazardous Materials, 2026)

Petrophysical responses to different CO2 injection methods in shale: Insights from flow and geological sequestration - Zhuoying Dou; Ming Zhao; Haibo Li; Wei Guan; Chenyu Han; Zhengming Yang (Journal of Cleaner Production, 2026)

FeCu bimetallic active sites construction via hexagonal boron nitride electron regulation for high-performance electro-Fenton degradation of Rhodamine B - Jiaxin He; Haoran Pan; Hanxiao Liu; Xinning Huang; Jianglong Yu; Guangyue Li; Jinxiao Dou; Xingxing Chen (Journal of Environmental Management, 2026)

D-allulose alleviates DSS-induced colitis via regulating gut microbiota and bile acid metabolism - Gaoqi Ye; Na Xi; Genying Li; Ziyuan Wang; Zhaofeng Li; Tongcheng Xu; Fangling Du; Guangpeng Dou; Yiman Zhang; Jie Liu (Food Research International, 2026)

A fluorescence biosensor based on upconversion nanoparticles and metal organic frameworks for multiresidue detection and enrichment of neonicotinoid pesticides - Huan Yun; Honglin Li; Zijie Dou; YuHao Zhang; Ting Guo; Ying Zhou; Hongyuan Zhou; Liang Ma; Xiaozhu Liu (Food Chemistry, 2026)

Scalable metallic-electron donation systems for optimized glycerol-to-1,3-propanediol bioconversion - Da Seul Kong; Sakuntala Mutyala; Himanshu Khandelwal; Minsoo Kim; Shuwei Li; Chang Dou; Jung Rae Kim; Changman Kim (Chemical Engineering Journal, 2026)

Insight into the synergistic SO2 removal by activated carbon loaded with amino acid based deep eutectic solvents: Mechanism, DFT calculation - Yueying Li; Xinxin Xiao; Hua Li; Guangyue Li; Liangbin Dou; Lu Tian; Jingyang Chen; Xingxing Chen; Jianglong Yu; Jinxiao Dou (Chemical Engineering Journal, 2026)

Composite hydrogel microspheres modulate intestinal inflammation via releasing HA modified liposomes@4-OI targeting M1 macrophages - Shuanghong Yang; Ze Li; Guiwen Qu; Liting Deng; Liuqing Dou; Sicheng Li; Yitian Teng; Luqiao Huang; Haohui Li; Kang Chen; Jinpeng Zhang; Rui Ma; et al. (Chemical Engineering Journal, 2026)

Cellulose based hierarchical structural colored wood composite material for daytime radiative cooling - Biyao Sun; Shaoyi Cao; Shuliang Dou; Yudong Li; Wenye Sun; Chunhui Ma; Sha Luo; Mingcong Xu; Shouxin Liu; Wei Li (Carbohydrate Polymers, 2026)

HIF-1α/BNIP3L–mediated mitophagy is involved in T-2 toxin–induced myocardial injury - Qian Li; Miao Wang; Juan Zuo; Zaichao Dong; Tongtong Sha; Kangting Luo; Huanxia Zhang; Yanjie Dou; Guoyu Zhou; Yue Ba; Fang-fang Yu (Chemico-Biological Interactions, 2026)

Dynamics and driving factors of sedge reproductive strategies during the active restoration of “bare land” in the Three-River Headwater Region of China - Weike Yang; Yudan Xu; Jing Dou; Shuyue Li; Miao Liu; Shuai Li; Guorui Zhang; Xiaolong Zhao; Xiang Zhao; Xin Li (Plant and Soil, 2025)

Trans-2-decenal inhibits Phytophthora capsici by inducing ROS accumulation and mitochondrial dysfunction - Siyuan Xie; Lanning Wang; Jingkun Lv; Xiang Feng; Siyu Li; Haojie Tan; Chao Wang; Gang Wang; Hongjun Ge; Chun Xiao; Danyu Shen; Daolong Dou (Pesticide Biochemistry and Physiology, 2025)

Characteristics of aeolian deposits and evolution of surface process since 15.5 ka in the Zoige Basin, northeastern Tibetan Plateau - Dou Chen; Jiangli Pang; Xiaochun Zha; Chunchang Huang; Yuzhu Zhang; Yali Zhou; Yuqin Li; Meihui Zhang; Ruiqi Huang; Xinran Fan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Origins of Cobalt’s superiority over adjacent transition metals (Fe/Cu/Ni) in single-atom electrocatalytic H2O2 production: Delicate balance between activity and selectivity - Xinyu Li; Jin Wang; Boru Gao; Mengmeng Dou; Yadong Hu (Journal of Environmental Chemical Engineering, 2025)

Enhancing the synergistic coupling oxidation performance through electronic space separation: Shortening the free radical mass transfer distance to improve the degradation efficiency of PFOA - Jianyang Dou; Xiang Li; Wen Zhou; Shaokang Li; Jinjin Yang; Boru Gao (Journal of Environmental Chemical Engineering, 2025)

Divergent response of denitrification and its nitrous oxide emissions to vegetation restoration of abandoned farmland - Yawen Li; Xingwu Duan; Shengzhao Wei; Jiao Dou; Bowen Deng; Chenli Liu (Journal of Environmental Management, 2025)

The effect of minimum temperatures on changes in river dissolved oxygen is more pronounced in the climate transition zone - Qin Zhang; Rui Xia; Kai Zhang; Haiming Li; Yan Chen; Ruining Jia; Jinghui Dou; Lina Li; Chao Yan; Xiang Li (Journal of Environmental Management, 2025)

Comprehensive analysis of R600a/R1150/R50 on performance, economy, and environmental impact of auto-cascade refrigeration system: Experimental study - Peicheng Ma; Zilong Wang; Hua Zhang; Rui Wu; Dong Wang; Binlin Dou; Kang Li; Yugang Zhao (International Journal of Refrigeration, 2025)

Strategic design of interesterified lipid phases: Developing an α-linolenic enriched whipping cream using perilla-palm stearin composite fat - Qing Ma; Yiming Sun; Lijuan Wang; Enguo Lyu; Jingwen Li; Dongkun Zhao; Usman Amjad; Baocheng Xu; Xinjing Dou; Lili Liu (Innovative Food Science & Emerging Technologies, 2025)

Comparing methods of assessing uncertainty in DEM of difference for soil erosion detection based on UAV laser scanning data - Dou Li; Pengfei Li; Jinfei Hu; Wanqiang Yao; Lu Yan; Fabian Ewald Fassnacht; Hooman Latifi; Yang Dan; Lifeng Liu; Jianjian Gao; Tianmin Dang (Geomorphology, 2025)

Insight into emulsion gels stabilized by soy protein isolate–flavonoid complexes: based on structural, interfacial, and emulsifying properties of the protein - Baorui Li; Shaokun Dou; Qian Li; Hao Yue; Aizhen Zong; Fangling Du; Tongcheng Xu (Food Research International, 2025)

Exploring the feasibility of multi-element fingerprinting with chemometrics for discriminating the geographical origins of asparagus and its risk assessment - Qiuhong Zhang; Min Li; Chuanhao Dou; Xiangliang Yan; Bing Wang; Huimin Zhang; Yongqiang Lin; Dantong Zhao (Food Chemistry, 2025)

Magnetic molecularly imprinted inverse opal photonic microspheres for high-performance enrichment and analysis of ochratoxin A in cereals - Qianjin Li; Yulu Xiao; Qinglong Yuan; Menghua Dou; Jianlin Li (Food Chemistry, 2025)

Covalent grafting of corn stover cellulose nanofibers with zein for pickering emulsion stabilization and controlled quercetin delivery - Xinling Wu; Qiang Zhang; Deyi Zhou; Jianpeng Dou; Qing Liang; Li Zhang; Haigen Zhou; Xiaodi Gao; Xuelin Zhao; Jinsong Zhang (Food Chemistry, 2025)

Montmorillonite loaded with cinnamaldehyde and Bacillus velezensis for sustained control of diverse toxigenic fungi - Guidong Li; Baocheng Xu; Kuijie Gong; Changying Guo; Mingxiao Ning; Bingchun Zhang; Lixia Fan; Xinjing Dou; Amnart Poapolathep; Xianfeng Ren (Food Bioscience, 2025)

Synergistic enhancement of waste activated sludge anaerobic digestion by iron-modified biochar activated peroxydisulfate: Dual mechanisms of pretreatment disintegration and bioelectrochemical enhancement - Zisheng Zhao; Peng Li; Xiaowei Wang; Tingting Zhang; Guangyi Zhang; Ming Dou (Chemical Engineering Journal, 2025)

Environmental chromium and cadmium co-exposure induces GADD45A-mediated rDNA instability in human cohorts and cell models - Yongxin Li; Yao Qin; Chuyan Zhang; Chan Ding; Minqian Feng; Yifan Dou; Xinran Wang; Xia Rao; Xiaoxue Gong; Zhaoqiang Jiang; Jianlin Lou; Huadong Xu (Chemico-Biological Interactions, 2025)

Real touch behaviors and control strategies of norovirus transmission among young children in kindergarten: An on-site investigation and intervention study - Minghan Yang; Zhiyang Dou; Wei Liu; Xian Li; Nan Zhang (Building and Environment, 2025)

Synergistic Enhancement of Cobalt Adsorption by Graphitization and Magnetic Modification of Biochar: Synthesis, Characterization, Performance and Mechanism - Hui Liu; Chen Li; Zhichao Fan; Zhirui Dou; Beibei Lu; Xiao Fan; Xiaohui Ji; Jinlong Lai; Qian Fu; Songlin Gong; Xinna Wang; Jie Liu (Water, Air, & Soil Pollution, 2025)

Synergistic effects and mechanism of recombinant viral vector-mediated STAT1 overexpression and STAT3 silencing on glioma U251 apoptosis - Xin-Long Hu; Hong Li; Guo-Dong Zhang; Chao Lin; Ping Huang; Xiu-Feng Chen; Fang Wan; Chang-Wu Dou; Hai-Tao Ju (Molecular Biology Reports, 2025)

Genome-wide identification of zinc finger-homeodomain (ZF-HD) gene family and expression analysis during abiotic stress in rye - Qingfeng Li; Yuzhao Ren; Jiaohui Long; Zhaoyi Wang; Feifei Dou; Shilei Wang; Chunying Liu; Xiaodong Wang; Caixia Liu; Fenglou Liu; Zhangjun Wang (Genetic Resources and Crop Evolution, 2025)

WISP2/CCN5 revealed as a potential diagnostic biomarker for endometriosis based on machine learning and single-cell transcriptomic analysis - Sheng Dou; Shaohua Ling; Weihua Nong; Bixiao Wei; Yuehua Huang; Guangjing Li; Rong Wang; Haimei Qin (Functional & Integrative Genomics, 2025)

Spatiotemporal patterns and drivers of grassland changes in China from 1990 to 2020 - Zherui Yin; Yinyin Dou; Wenhui Kuang; Changqing Guo; An Chang; Yuwei Li; Xiwei Zhang; Fanhao Meng; Chula Sa (Journal of Geographical Sciences, 2025)

LncRNA H19 Promotes Angiogenesis in Mouse Pulmonary Artery Endothelial Cells by Regulating the HIF-1α/VEGF Signaling Pathway - Lei Dou; Wei You; Yannan Chai; Huiju Shi; Qing Liu; Qiaoli Jiang; Huiling Li (Biochemical Genetics, 2025)

Impact of Ocean Acidification on the Intestinal Microflora of Sinonovacula constricta - Yuan Wei; Hesheng Dou; Chengju Chai; Tingkuan Wang; Huiru Liu; Shuang Liang; Yongren Li; Jian Liang; Yongjun Guo (Fishes, 2025)
The intestinal microflora, which is vital for nutrient absorption and immune regulation, can experience dysbiosis under environmental stress, potentially enhancing host susceptibility to pathogenic invasion. The impact of ocean acidification on bivalves is substantial, but its effects on their intestinal microflora remain poorly understood. To explore the impact of ocean acidification on the intestinal microflora of Sinonovacula constricta, this study used high-throughput 16S rRNA sequencing technology to investigate the variations in the intestinal microflora communities of S. constricta during ocean acidification across different time points. After exposure to ocean acidification, changes in the composition of the intestinal microflora of S. constricta were observed, with no significant difference in α-diversity between the acidified and control groups. The abundance of Proteobacteria in the acidification group increased, whereas that of Cyanobacteria decreased. The abundance of Firmicutes initially decreased and then increased. At the genus level, the relative abundance of Pseudomonas was lower than that in the control group, whereas the relative abundance of Photobacterium, Acinetobacter, and Enterobacter gradually increased. LEfSe analysis identified Serpens as the discriminative biomarker at 7 days of acidification, Enterobacteriales, Rhodobacteraceae, and Martvita at 14 days of acidification, and Serpens, Acidibacteria, and Aeromonadaceae at 35 days of acidification. Functional prediction analysis indicated significant stimulation in various metabolic pathways at different time points following acidification stress. Specifically, pathways involved in biosynthesis were significantly stimulated at 14 days of acidification, while those related to sucrose degradation were disrupted at 35 days. The results further indicated that ocean acidification stress can influence the intestinal microflora of S. constricta, but no severe dysbiosis or digestive system impairment was observed at the microbial level. This study provides new insights into the effects of ocean acidification on the intestinal microflora of marine bivalves.

Multimedia distribution of polycyclic aromatic hydrocarbons in an intensive aquaculture area in the East China Sea: Focusing on bioaccumulation and health risks in mollusks - Wenwen Li; Jinhu Liu; Liang Cao; Xizhi Shi; Shuozeng Dou (Marine Pollution Bulletin, 2025)

Quantifying the impact of landscape pattern on land surface temperature: an integrated landscape index from perspective of scale response and threshold effect - Xiaolei Geng; Dou Zhang; Jing Gao; Yuan Yuan; Chengwei Li; Xiaoning Li; Xiangrong Wang (Urban Forestry & Urban Greening, 2025)

Corrigendum to “LSTM-transformer hybrid model predicts and unveils Total phosphorus dynamics and pollutions in Poyang Lake” [Sci. Total Environ. 1003 (2025) 180622] - Yihan Li; Hua Wang; Yanqing Deng; Dongfang Liang; Ming Qiao; Jiayao Dou; Zhiheng Qiu; Linyou Chu (Science of The Total Environment, 2025)

LSTM-Transformer hybrid model predicts and unveils total phosphorus dynamics and pollutions in Poyang Lake - Yihan Li; Hua Wang; Yanqing Deng; Dongfang Liang; Ming Qiao; Jiayao Dou; Zhiheng Qiu; Linyou Chu (Science of The Total Environment, 2025)

Sesame pods derived high-efficiency demulsifier: Synthesis and demulsification performance in oily wastewater treatment - Dou Wang; Jianle Li; Yongzhi Liu; Na Guo; Qingwen Qin (Process Safety and Environmental Protection, 2025)

Investigation of cavitation control mechanism around bionic hydrofoil from multi-perspective vortex identification methods - Huancheng Xue; Peifeng Lin; Wei Dou; Zhilei Jin; Zuchao Zhu; Xiaojun Li (Ocean Engineering, 2025)

A sequence boundary related aeolian sand record in a continental basin: The Cretaceous-Paleogene White Sandstone Member, Tabei Uplift, Tarim Basin, NW China - Xiaoyang Gao; Luxing Dou; Wenxiang He; Qi Sun; Zhenli Yi; Bin Li; Qiaolin He; Jineng Jin; Yong Hu; Jingwen Yan; Li Zhang (Marine and Petroleum Geology, 2025)

Self-standing graphite felt supported S-doped bimetallic MOF-derived carbon anode: Boosting rhodamine B degradation via synergistic Fe/Co redox catalysis and enhanced electron transfer - Jiaxin He; Haoran Pan; Liye Shuai; Hanxiao Liu; Xinning Huang; Jianglong Yu; Guangyue Li; Jinxiao Dou; Xingxing Chen (Journal of Water Process Engineering, 2025)

Investigating sediment connectivity of a small catchment on the Loess Plateau using an appropriate index at an optimal spatial resolution - Jinfei Hu; Jingjing Zhang; Weiguang Li; Pengfei Li; Guangju Zhao; Shugang Li; Leiqin Wang; Yuhan Li; Dou Li; Min Du (Journal of Hydrology, 2025)

miR-927 links nutrient signals and 20-hydroxyecdysone regulation and mediates oviposition in Bactrocera dorsalis - Tong-Jun Jin; Zheng-Yang Wang; Qian-Ping Xie; Li-Yuan Zheng; Guy Smagghe; Jin-Jun Wang; Qiang Zhang; Wei Dou (Insect Biochemistry and Molecular Biology, 2025)

Insights into the effects of volcanic rocks on the anaerobic digestion efficiency of dairy wastewater: Properties, performance, and mechanisms - Zisheng Zhao; Yixin Li; Guangyi Zhang; Ming Dou (Fuel, 2025)

Contribution of bound water to the compressibility and drainage during clay consolidation - Wen Zhang; Zhi Dou; Yongqiang Chen; Zejun Wang; Hao Li; Meng Chen (Engineering Geology, 2025)

Light-switchable Ti3+ species in photochromic TiO2 nanoparticles for efficient photooxidation of C H bonds - Yun Zhang; Derong Kong; Xiaotong Li; Guanfeng Ji; Feng Liu; Yao Dou; Wenshou Wang (Chemical Engineering Journal, 2025)

When AI meets AIE: Machine learning in design function-oriented AIEgens for antibacterial ability - Leina Dou; Penghui Zhou; Fei Qi; Qing Li; Yuchen Bai; Liang Luo; Kai Wen; Wenbo Yu; Xuezhi Yu; Jianzhong Shen; Zhanhui Wang (Chemical Engineering Journal, 2025)

Engineering of chain extender rigidity and hierarchical hydrogen bonding toward ultra-strong and tough cold-resistant poly(urethane-urea) elastomers - Pengrui Cao; Jing Yang; Qian Dou; Yanhui Li; Lihe Guo; Yaoming Zhang; Jie Yan; Haijiao Xie; Qihua Wang; Tingmei Wang; Liming Tao (Chemical Engineering Journal, 2025)

3D printed electrochemical sensors with femtosecond laser treatment for cellphone-based portable detection - Yan Dou; Kewei Li; Haofan Sun; Kun Bi; Chenyang Zhu; Zuanyu Chen; Kailong Jin; Wonmo Kang; Xin Zhao; Qiong Nian (Chemical Engineering Journal, 2025)

Therapeutic strategy for corneal edema: Nicotinamide - based anterior chamber perfusion agent for efficacy - verified treatment - Liwei Huang; Xiaomin Liu; Xiaoming Wu; Haoyun Duan; Simeng Zheng; Xiangyue Hu; Shengqian Dou; Xiaoyu Li; Zongyi Li; Qingjun Zhou; Lixin Xie (Chemical Engineering Journal, 2025)

Crosslinking-engineered lignin-derived hard carbons for high-performance sodium-ion storage - Sishi Li; Yandong Xie; Yulong Zhang; Yuecong Chen; Shiyin Xie; Xiuxia Zhang; Jian Zhu; Qingyun Dou; Wangda Qu; Xingbin Yan (Chemical Engineering Journal, 2025)

A novel method to quantify Dendrobium officinale polysaccharides in biological samples via 99mTc-labelling and radioHPGPC analysis - Pengfei Dou; Jinglin Wang; Yamin Shu; Fang Cheng; Gang Nie; Li Luo; Zhijing Wu; Ziming Zheng; Yongkang Gai; Junxi Liu; Yan Liu; Yinxing Zhou; et al. (Carbohydrate Polymers, 2025)

Binder Jetting 3D Printing Cementitious Layered Structure vs. Natural Layered Rock: Mechanical Similarity and Failure Analysis - Tingyu Hu; Chaoyu Dou; Guowei Ma; Zhijian Li (Rock Mechanics and Rock Engineering, 2025)

Bioinspired urchin-like AuMnCu nanoreactors: Integrating tip-enhanced electric fields with alloy-tuned interfacial electron for precision photothermal immunoassays - Weijie Gong; Yuechun Li; Bangfeng Fu; Jinrui Shan; Jing Zhou; Sijie Liu; Jing Sun; Leina Dou; Jianlong Wang (Analytica Chimica Acta, 2025)

A study on detection of human activity using SDGSAT-1 glimmer imager data over urban agglomerations in China - Lu Zhang; Huadong Guo; Dong Liang; Zhuoran Lv; Zilu Li; Yaqi Geng; Xuting Liu; Mingyang Lv; Changyong Dou (Remote Sensing of Environment, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Hydrological variability significantly influences aquatic biological integrity at the spatial scale in semi-arid watersheds - Lina Li; Rui Xia; Xinghui Xia; Ming Dou; Minhua Ling; Yan Chen; Jinghui Dou; Kai Zhang; Ruining Jia; Chao Yan (Journal of Hydrology, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

β-cyclodextrin and TiO2 synergistically enhance the negative charge and reduce roughness for ultrafiltration membranes: Preparation and performance analysis - Kaibo Wang; Jin Wang; Mengmeng Dou; Chao Han; Wubin Wang; Xinyu Li; Yadong Hu; Guangxu Zhang (Journal of Environmental Chemical Engineering, 2025)

Modified ultrafiltration membrane to improve organic matter conversion in anaerobic digestion of kitchen waste: Performance and separation mechanism - Boru Gao; Yiheng Xue; Shaokang Li; Jinjin Yang; Mengmeng Dou; Xiang Li (Journal of Environmental Chemical Engineering, 2025)

Boosting dynamic NH3 adsorption performance of UiO-66 via amino-induced local polarization - Zimu Liu; Mingtai Li; Zitong Zhao; Yulong Yang; Linlin Deng; Baojuan Dou; Feng Bin (Journal of Environmental Chemical Engineering, 2025)

Preparation of Co-Ce modified sludge-based catalyst and its application in CO2 photothermal catalytic reduction - Shu Hao; Luo Xinzeng; Liu Yuling; Jia Yang; Dou Chuanchuan; Li Bo (Fuel, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Effect of pH on oxidation and hydrolysis of myofibrillar protein and the ability to bind heptanal - Xia Hu; Qingzhe Dou; Mengtong Li; Qiang Wang; Baohua Kong; Qian Chen (Food Research International, 2025)

Three-dimensional functionalized graphene oxide for enhanced hexavalent chromium remediation: Mechanistic insights and practical wastewater treatment potential - Yanhui Dou; Li Cao; Mengxin Wu; Zidong Wang; Di Yang; Zongzheng Yang (Environmental Research, 2025)

Engineering antioxidant ion-solvating membranes via precise metal oxide hybridization for 3000 h-durable alkaline water electrolyzers - Xu Hu; Mengyu Dou; Bin Hu; Hongjing Li; Erqiang Yang; Yixin Wang; Baoliang Lv; Nanwen Li (Chemical Engineering Journal, 2025)

Layered transition metal oxide cathodes for sodium-ion batteries: Challenges, progress, and perspectives - Jiaxuan Liu; Nan Zhang; Huiming Shi; Zhipeng He; Zhiyu Zhang; Dmitrii V. Anishchenko; Elena V. Alekseeva; Ruopeng Li; Peixia Yang; Oleg V. Levin; Dianlong Wang; Huakun Liu; et al. (Chemical Engineering Journal, 2025)

Constructing directed charge transfer microregions via vacancy and doping engineering for photocatalytic hydrogen production coupled with biomass upgrading - Guang Yang; Mingyu Dou; Dacheng Li; Hua Yang; Zunhao Wang; Xinyi Chi; Erkang Liu; Lingqian Kong; Yu Cui; Jianmin Dou (Chemical Engineering Journal, 2025)

Dipole-unit mediated Co-solute engineering to construct nanodomain electrolytes for highly reversible and shuttle-free ZnI2 batteries - Renwu Feng; Qingying Li; Haozhen Dou; Yihan Xie; Jinliang Yan; Mi Xu; Dan Luo; Zhile Yang; Yuanjun Guo; Xinru Wu; Xin Wang; Zhongwei Chen (Chemical Engineering Journal, 2025)

The relationship between Holocene environmental evolution and human activities on the Chinese Loess Plateau inferred from an aeolian loess-paleosol profile in the Xitou Ruins - Mengting Li; Yuzhu Zhang; Yan Zhu; Haifeng Dou; Shuheng Li; Xinwen Xu; Jinpeng Zhou; Yao Jin; Pengpeng Cao; Zikun Li; Ziang Wang; Jiahui Wang; et al. (CATENA, 2025)

Influx of Metabolites into Cerebrospinal Fluid in Intracerebral Hemorrhage is Associated with Increased Central Inflammation: a Retrospective Observational Study - Huaying Zhang; Yuxia Zhong; Jinlian Shao; Kaijian Sun; Lingling Zhang; Yulong Zhang; Yu Xiao; Xiangyu Zuo; Zhixin Li; Tianhui Zeng; Zizheng Gao; Chun Yang; et al. (Translational Stroke Research, 2025)

Preclinical Evaluation of AAV8-R338L Gene Therapy for Hemophilia: Efficacy, Pharmacokinetics, Distribution, Excretion and Toxicity in Mouse Models and Non-human Primates - Dehu Dou; Jing Lu; Deli Li; Fengxia He; Xi Zhu; Xuefeng Zhang; Xijing Chen (Pharmaceutical Research, 2025)

FLSM: Featureless Surface Matching for Multi-instance Pose Estimation - Huakai Zhao; Jiansheng Li; Xiaomin Liu; Zidi Yang; Xiaojing Dou (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2025)

Apigenin inhibits endothelial-to-mesenchymal transition of coronary artery endothelial cells and myocardial fibrosis by regulating ribosome biogenesis through GTPBP4 modulation - Xiaoyong Hu; Zhaoying Yang; Rui Tang; Zhongying Lv; Ting Zou; Yuanyuan Dou; Hongjian Li (Human Cell, 2025)

Dendrobium officinale Kimura et Migo regulates the proliferation and migration of colon adenocarcinoma via LGALS4 - Jiawei Miao; Bingrui Luo; Xiuzhen He; Guoli Li; Lu Dou; Yongbo Yan; Xiaoyan Tang (Molecular Diversity, 2025)

Regulation of coagulant dosage in water treatment based on explainable integrated time-series deep learning models - Wangben Zhao; Yuling Liu; Ren Shuang; Wang Lu; Shuaishuai Li; Chenxu Zhao; Chuanchuan Dou; Hao Shu (Process Safety and Environmental Protection, 2025)

Demulsification of vegetable oil-in-water emulsions using magnetic biochar: Flocculation performance and mechanistic insights - Yongzhi Liu; Jianle Li; Dou Wang; Zhengan Zhang; Du Zhimin (Process Safety and Environmental Protection, 2025)

Extreme rainfall drives the shift in dominant water quality “Sink” from forest land to grassland in the Yellow River Basin - Jinghui Dou; Rui Xia; Xinghui Xia; Xiaohui Jiang; Kai Zhang; Yan Chen; Lina Li; Chao Yan (Journal of Hydrology, 2025)

Phytohormone-augmented microalgae: A dual-functional solution for pharmaceutical contaminants removal and resource recovery - Jun-Jie Gu; Xiao-Xiao Dou; Jin-Long Zhou; Si-Yuan Guo; Ashiwin Vadiveloo; Xiao-Ling Zhang; Kai-Yuan Li; Dong-Zhi Chen; Feng Gao (Journal of Hazardous Materials, 2025)

Multidimensional characteristics as a clue to tracing pollution and source-specific ecological risk of microplastics in large-scale basin - Siqiong Li; Hua Wang; Dongfang Liang; Yichuan Zeng; Haosen Xu; Jiayao Dou; Xinchen He; Qihui Gu (Journal of Cleaner Production, 2025)

Acidic-thermal coupled degradation of tylosin by using magnetic sulfonated resins under microwave irradiation - Caitiao Fang; Wei Zhang; Chunmei Wang; Shiling Li; Xiaomin Dou; Jun Liu (Journal of Environmental Sciences, 2025)

Ferroelectric heterostructures modulated tribo-piezoelectric hybrid nanogenerator for mechanical energy harvesting and water splitting applications - Mingyang Yan; Yan Zhang; Huimin Li; Shengwen Liu; Qianqian Xu; Xi Yuan; Kechao Zhou; Dou Zhang (Chemical Engineering Journal, 2025)

Connecting biodiversity and potential functional to promote motivated labor in iron sulfide-amended partial denitrification/anammox systems - Quanhao Dou; Li Zhang; Yongzhen Peng (Chemical Engineering Journal, 2025)

Dual-electric-field synergy in CdS/NiCo2S4 heterojunctions for flexible integrated photo-supercapacitors - Tianqi Li; Xuexiao Chen; Kefeng Ren; Yaqi Zhang; Jianuo Yao; Wenping Zhang; Wendong Dou; Peicheng Wang; He Liu; Cong Guo; Jingfa Li (Chemical Engineering Journal, 2025)

Novelty carbon-based Fe-S-Mo catalyst to achieve adsorption oxidation cooperative reinforcement for Fenton-like reaction - Yanchun Huang; Weifang Huang; Luming Dou; Yuesen Wang; Jun Li; Bo Lai; Chao Liu; Naiwen Li (Chemical Engineering Journal, 2025)

Phosphorus recovery from sewage sludge: Progress, challenges, policies, and future directions - Yanyan Dou; Yanqiang Du; Yufeng Xu; Yang Li; Xiaoqi Wu; Dunqiu Wang (Chemical Engineering Journal, 2025)

In-situ secondary organic aerosol formation from ambient air in suburban Eastern China: Substantially distinct characteristics between summer and winter - Jibin Dou; Tengyu Liu; Dafeng Ge; Ying Zhang; Junchao Yin; Lei Wang; Haoyu Liu; Duzitian Li; Guangdong Niu; Liangduo Chen; Jiaping Wang; Ximeng Qi; et al. (Atmospheric Environment, 2025)

Isoliquiritigenin alleviates radiation-induced intestinal injury in lung cancer by inhibiting TNF-α/caspase3 signaling pathway - Ya-ping Chen; Liang-liang Shi; Yang-yang Li; Yi-Ming Zhang; Shang-zu Zhang; Hong-dou Hou; Yan Chen; Qi-hong Zhuo; Yong-qi Liu; Ben-jun Wei; Li-ying Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The Reorganization of Subcortical Network Reflects Sensory-Motor Abilities in Patients after Spinal Cord Injury - Na Li; Meisi Song; Mao Pang; Xiaodan Ma; Weihong Qiu; Zhuang Kang; Yong Yu; Zhaocong Chen; Zulin Dou; Xiquan Hu; Bin Liu; Limin Rong (Brain Topography, 2025)

Residues and Dietary Risk of Lambda-Cyhalothrin in Fresh and Dried Panax notoginseng, Lilium, and Lonicera japonica - Haojie Wang; Hui Ye; Zhaojun Meng; Wen Dou; Xiangyun Wang; Hongmei He; Jianzhong Yu; Xiaohui Li; Xueping Zhao; Changpeng Zhang (Environmental Monitoring and Assessment, 2025)

Optimal Fluoride Concentration in Drinking Water for Preventing Dental Fluorosis and Caries in 8–12-Year-Old Children in Qingdao, China: A Restricted Cubic Spline and Spatial Epidemiological Analysis Following Rural Safe Drinking Water Interventions in Endemic Fluorosis Region - Xiaojuan Dou; Xiaoyi Liu; Shitao Liu; Changxun Ge; Shirui Yan; Di Wu; Xinyue Meng; Xinxiao Li; Junrui Pei; Fengying Ji (Biological Trace Element Research, 2025)

Impacts of metropolitan area expansion on ecosystem use efficiency: evidence from the Wuhan metropolitan area, China - Yanqiong Zhao; Shiquan Dou; Junhui Li; Jinhua Cheng; Deyi Xu (Environment, Development and Sustainability, 2025)

Homologues of PFOA substitutes in a semi-closed bay near source region: contamination status and risk assessments - Dawei Shi; Yitao Pan; Wenke Dou; Fengfeng Dong; Jian Zhang; Xinqi Xin; Yanan Li; Jiayin Dai; Jianhui Tang (Marine Pollution Bulletin, 2025)

Delta-scale mapping of coastal erosion vulnerability at the modern Yellow River Delta and implications for geomorphic sustainability - Hongyu Ji; Xuelei Gong; Yaoshen Fan; Yuanbin Fu; Hanghang Lyu; Peng Li; Yin Cao; Shenliang Chen; Shentang Dou (Ocean & Coastal Management, 2025)

Controlling high-concentration precursor crystallization to minimize photon loss in bifacial perovskite solar cells - Shan Gan; Haoxuan Sun; Min Wang; Da Dou; Siyang Zhang; Chen Li; Liang Li (Science Bulletin, 2025)

Proteomics and metabolomics reveal the role of miR-320b in regulating inflammation of bovine mammary epithelial cells - Li Zhou; Zhuo-Ma Luoreng; Xing-Ping Wang; Ya-Qing Dou; Hui Li (Research in Veterinary Science, 2025)

TSC2/mTORC1 integrates deoxynivalenol signals recognized by membrane receptors IR and EGFR to restrict intestinal stem cell function - Cai-xia Dou; Hao-zhan Qu; Ying-chao Qin; Xiao-fan Wang; Hui-chao Yan; Run-sheng Li; Yu-guang Zhao; Jia-yi Zhou; Xiu-qi Wang (Journal of Hazardous Materials, 2025)

Water environmental capacity of estuarine microplastics capped by species sensitivity threshold - Yichuan Zeng; Hua Wang; Dongfang Liang; Weihao Yuan; Yuting Yan; Haosen Xu; Siqiong Li; Jiayao Dou (Journal of Hazardous Materials, 2025)

Construction of new thermostable MtLPMO9V in synergism with cellulases for efficient lignocellulosic hydrolysis - Weimeng Li; Hang Yuan; Yun Hu; Shaohua Dou; Ezhen Zhang; Qun Wu; Fubao Sun (Bioresource Technology, 2025)

A hybrid optimized Picard method for neutronic/thermal-hydraulic coupling problem - Xinru Peng; Han Zhang; Lixun Liu; Qinrong Dou; Yingjie Wu; Jiong Guo; Fu Li (Annals of Nuclear Energy, 2025)

A novel Zn2+ probe for fluorescent monitoring of drug and E6/E7 protein interaction in living cells - Zhenzhen Xie; Lan Yu; Zuoping Li; Na Zhao; Shiwan You; Zhihao Zhao; Jindi Dou; Xiling Deng; Shiguo Sun (Analytica Chimica Acta, 2025)

Nutrient amendment promotes vegetation restoration and improves ecosystem carbon uptake capacity in a degraded grassland - Yaxiang Lü; Binger An; Qingmin Pan; Wei Liu; Jiamei Sun; Jing Wang; Zhiyan Qi; Chao Li; Shande Dou; Xingguo Han (Agriculture, Ecosystems & Environment, 2025)

Astrocyte involvement in brain metastasis: from biological mechanisms to therapeutic strategies - Teng Zhou; Yuxin Yan; Mingxi Lin; Cheng Zeng; Xinhui Mao; Yifei Zhu; Jinlu Han; Dou-Dou Li; Jian Zhang (Cancer and Metastasis Reviews, 2025)

In-situ Validation of Low-cost Sensors Based on Physical Calibration Model - Xiaoting Li; Dou Liu; Rui Yang; Ning Xue; Lina Zheng (Aerosol Science and Engineering, 2025)

Characteristic analysis of floc size distribution and image texture evolution in chemical coagulation process - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao; Hao Shu (Process Safety and Environmental Protection, 2025)

Transcriptome sequence reveal the roles of MaGME777 and MabHLH770 in drought tolerance in Musa acuminata - Yuchen Wei; Jingfang Shi; Xueyi Xie; Feng Zhang; Huizhen Dong; Yaoyao Li; Fangcheng Bi; Xiaosan Huang; Tongxin Dou (Plant Science, 2025)

A thorough accuracy assessment of MT-InSAR for soil erosion monitoring in the hilly and gully Loess Plateau - Yafei Zhang; Pengfei Li; Liuru Hu; Jinfei Hu; Yun Shi; Yufen Niu; Xuejian Zhu; Dou Li (Journal of Hydrology, 2025)

Active restoration facilitates sedge colonization in degraded alpine meadows on the Qinghai-Tibetan Plateau - Miao Liu; Yudan Xu; Shuai Li; Shikui Dong; Weike Yang; Guorui Zhang; Shuyue Li; Jing Dou; Xiaolong Zhao (Journal of Environmental Management, 2025)

Thermodynamic controls on plutonium(Pu) speciation in deep groundwater: Implications for HLW disposal safety at Beishan, China - Nan Li; Xianzhe Duan; Jiale Dou; Wenting Bi; Peng Wu; Nadia Cheemaa; Hafiza Tasneem Nazish; Guowen Peng (Journal of Environmental Radioactivity, 2025)

Molecular interactions and physiological effects of oyster-derived synthetic peptide-calcium complex: Insight in improving the bone growth and health - Xuening Yu; Guang Li; Shijie Dou; Shuling Zhou; Xiaoyang Liu; Dayong Zhou (Food Research International, 2025)

GeoAvatar: A big mobile phone positioning data-driven method for individualized pseudo personal mobility data generation - Peiran Li; Haoran Zhang; Wenjing Li; Dou Huang; Zhiling Guo; Jinyu Chen; Junxiang Zhang; Xuan Song; Pengjun Zhao; Jinyue Yan; Shibasaki Ryosuke; Noboru Koshizuka (Computers, Environment and Urban Systems, 2025)

Entropy engineering to modulate oxygen adsorption of bi-functional perovskite-type catalysts toward intermediate-temperature solid oxide cells - Chao Huang; Zixuan Tang; Yingnan Dou; Liping Sun; Qiang Li; Lihua Huo; Hui Zhao (Chemical Engineering Journal, 2025)

In situ surface modification with solid-state reaction enabling long cycle performance of 4.5 V LiCoO2 - Chong Ni; Zhen Li; Kai Wang; Yongchao Liu; Yuanyun Dou; Wentao Wu; Hongyu Wang; Yu Yao; Hongfa Xiang; Xuyong Feng (Chemical Engineering Journal, 2025)

Innovative MOF linker engineering in PVDF-HFP gel electrolyte matrix for solid-state lithium-oxygen batteries - Minghui Li; Yaying Dou; Zuliang Zhou; Zhenzhen Li; Kecheng Pan; Zhang Zhang; Zhen Zhou (Chemical Engineering Journal, 2025)

Impacts of spatial resolutions of UAV-LiDAR-derived DEMs on erosion modelling in the hilly and gully Loess Plateau - Wenli Li; Pengfei Li; Lu Yan; Jinfei Hu; Leiqin Wang; Dou Li; Yang Dan; Linlin Huang; Guangju Zhao (CATENA, 2025)

Investigating the potential of magnesium isotopes in bioarchaeology: evidence from the Zaoshugounao Site - Keyu Liu; Xue Ling; Haifeng Dou; Yaopeng Qian; Zhen Wang; Yue Li; Kangjun Huang; Chunlei Zong (Archaeological and Anthropological Sciences, 2025)

Crop rotations reduce pathogenic fungi compared to continuous cropping - Yanhui Dou; Shuting Yu; Song Liu; Tingting Cui; Rongyan Huang; Yushu Wang; Junqiang Wang; Kefei Tan; Xinyuan Li (Rhizosphere, 2025)

Numerical analysis of parametric excitation characteristics of a deep-sea mining riser under vessel heave motions - Yan Li; Xingkun Zhou; Yaning Dou; Huade Cao; Wenhua Li (Ocean Engineering, 2025)

Enhancing hydrological model performance through multi-source open-data utilization in the highly managed, data-scarce basin - Jiayan Zhang; Zhihong Liu; Yu Li; Yanhong Dou; Mingjun Wang; Huicheng Zhou; Bo Xu (Journal of Hydrology, 2025)

Hydraulic properties and groundwater depletion of a nonlinear consolidated aquitard considering vertical heterogeneity with drawdown in adjacent aquifers - Hao Li; Zhi Dou; Wen Zhang; Ruizhe Wang; Zhaofeng Li (Journal of Hydrology, 2025)

Geochemistry, geochronology and Fe-Mg-S isotopic composition of the Liaoshang gold deposit, Jiaodong Peninsula, China: Implications for ore-forming processes and mineral exploration - Yuan-lin Chen; Huan Li; Shang-yi Gu; Scott A. Whattam; Chao-yang Zheng; Li-gong Wang; Da-dou Li; Liu-an Duan (Journal of Geochemical Exploration, 2025)

Promoting oxidation of high concentration CO via strong metal support interaction in unreduced Pt-based catalysts - Yulong Yang; Xiaokun Yi; Linlin Deng; Zitong Zhao; Zimu Liu; Mingtai Li; Baojuan Dou; Feng Bin (Journal of Environmental Chemical Engineering, 2025)

Ripening-stage variations in small metabolites across six banana cultivars: A metabolomic perspective - Huijun Gao; Ping Liu; Weidi He; Fangcheng Bi; Chunhua Hu; Guiming Deng; Tongxin Dou; Qiaosong Yang; Chunyu Li; Ganjun Yi; Ou Sheng; Tao Dong (Food Chemistry, 2025)

Molecularly imprinted Fe3O4 nanoparticles-based magnetic 3D photonic crystal microspheres for specific adsorption of aflatoxin B1 in grains - Qianjin Li; Xiaoxiao Hong; Menghua Dou; Shuying Guan; Jianlin Li (Food Chemistry, 2025)

Copper sulfide for high-rate and long-life sodium storage through conversion–displacement chemistry - Caifu Dong; Chuanchuan Li; Yifan Zhang; Qingyu Dong; KaiZhong Li; Yunxiu Wang; Fuyi Jiang; Nana Wang; Shi Xue Dou; Zhongchao Bai (Chemical Engineering Journal, 2025)

Tuning electronic properties of NiCo2S4 nanofibers through phosphorous doping for optimized oxygen reduction and evolution reactions in Li-O2 batteries - Sana Shoukat; Yichuan Dou; Mingzhu Gao; Dongning Wan; Muhammad Shoaib; Sikandar Iqbal; Amina Tariq; Irum Rafique; Amir Said; Songze Li; Imran Haider; Jun Wang (Chemical Engineering Journal, 2025)

Removal of fluoride and chloride from waste acid by Bi2O3: comparison between the synchronous and two-step methods - W. Dou; Y. Song; Y. Zhang; T. Liu; L. Kong; X. Hu; D. Li (International Journal of Environmental Science and Technology, 2025)

Three-dimensional Copula-based Assessment of Meteorological Drought Characteristics and Driving Mechanisms in Haihe River Basin, China - Jianwen Xue; Qiang Zhao; Yuhu Zhang; Yali Chen; Xuan Wang; Xiangzhou Dou; Xiumei Li (Chinese Geographical Science, 2025)

Assembling metal nanoclusters with high luminescence performance and anti-interference ability for sensing p-nitrophenol - Jiaxi Wang; Jiaqing Li; Yuexiang Lu; Xiwen Zhang; Huashuo Dou; Yueying Liu (Analytica Chimica Acta, 2025)

Automatic identification of GPR targets on roads based on CNN and Grad-CAM - Yi-Tao Dou; Guo-Qi Dong; Xin Li (Applied Geophysics, 2025)

A Bletilla striata calcium-dependent protein kinase gene, BsCDPK1 , enhances salinity stress tolerance in Arabidopsis thaliana - Shuangshuang Wang; Yongchun Qian; Li Ma; Quanli Dou; Yuxia Zheng (Plant Biosystems, 2025)

Multiple snapshot RFI localization fusion algorithm based on Gaussian process regression - Yang Zhao; Rong Jin; Yinan Li; Haofeng Dou (International Journal of Remote Sensing, 2025)

Genomic dissection of high-temperature resistance in hybrid oysters (Crassostrea gigas ♀ × C. angulata ♂) using SNP- and InDel-GWAS based on whole-genome resequencing - Shilong Dou; Gaowei Jiang; Ben Yang; Lingling Sun; Qi Li (Aquaculture, 2025)

Membrane-associated NAC transcription factor MaNAC169 is a positive regulator during banana fruit ripening - Fan Liu; Xueli Sun; Jia He; Jingjing Shan; Ou Sheng; Tongxin Dou; Yaoyao Li; Weidi He; Qiaosong Yang; Chunhua Hu; Huijun Gao; Xinxiang Peng; et al. (Postharvest Biology and Technology, 2025)

Energy storage in Hf0.5Zr0.5O2(3):ZrO2(12)-based films with heterostructures formed at different deposition temperatures - Haiyan Chen; Chengfeng Jiang; Lei Liu; Ru Guo; Zhongna Yan; Chuanchang Li; Dou Zhang (Chemical Engineering Journal, 2025)

ZnAl alloy and organosulfur hybrid energy storage for long term cyclability - Qing Liu; Zhiyong Zheng; Chun Huang; Gun Jang; Qingyun Dou; Yong Li; Shengyang Huang; Baohuai Zhao; Yongan Wu; Yi Zhang; Bo-Kyong Kim; Xu Yu; et al. (Chemical Engineering Journal, 2025)

Constructing efficient PVDF-HFP-based intercalated composite solid electrolytes via competitive solvation structures for rechargeable lithium metal batteries - Yutong Jing; Shen Liu; Cheng Li; Qiang Lv; Daming Liu; Manxing Huo; Bochen Wu; Siyuan Liu; Yuhang Zhang; Mingyu Yin; Zhipeng He; Dianlong Wang; et al. (Chemical Engineering Journal, 2025)

Ferrosilicon alloy as both reactant and catalyst for hydrogenation of SiCl4: Thermodynamics, mechanism, and kinetics studies - Zheng-Peng Wang; Zi-Yi Chi; Huai-Qiang Dou; Xue-Gang Li; Cheng-Wei Liu; Wen-De Xiao (Chemical Engineering Journal, 2025)

Vertically oriented micron-thick perovskite film enables efficient and stable inverted perovskite solar cells - Bing-Hao Lv; Yong-Chun Ye; Jun-Gan Wang; Liu-Jiang Zhang; Yu-Hang Zhang; Ming-Li Zheng; Xian-Min Chen; Hui-Wei Du; Jie Yang; Xin-Yu Zhang; Meng-Lei Xu; Qiu-Feng Ye; et al. (Chemical Engineering Journal, 2025)

High performance rechargeable aluminium ion batteries enabled by strategy of covalent organic frame material - Guokang Wei; Jia Qiao; Xin Li; Aichun Dou; Sijiang Hu; Wei Xie; Zhenhua Luo; Jianhong Yang (Chemical Engineering Journal, 2025)

Fine-tuning the pathway and fermentation conditions to explore Pichia pastoris for high-level d-arabitol production from glucose - Yuan Dou; Zhang Yufei; Hossain M. Zabed; Junhua Yun; Jia Li; Xianghui Qi (Bioresource Technology, 2025)

Advances of microalgae-based enhancement strategies in industrial flue gas treatment: From carbon sequestration to lipid production - Kai-Yuan Li; Jin-Long Zhou; Si-Yuan Guo; Xiao-Xiao Dou; Jun-Jie Gu; Feng Gao (Bioresource Technology, 2025)

Study on the regulatory effects of Δ4-DES and LACS genes on the synthesis of LC-PUFAs, based on the transcriptome changes induced by fluridone in Aurantiochytrium limacinum OUC86 - Ying Li; Menghui Shang; Wenhua Zhang; Rongxiu Tian; Mengchao Liu; Ruyi Dou; Di Xu; Xiaonan Zang (World Journal of Microbiology and Biotechnology, 2025)

Quantifying the impacts of climate change and human activities on vegetation in ecologically fragile regions: a case study of Northern China - Xiangzhou Dou; Xiumei Li; Guoqing Sang; Ping Yang; Yuhu Zhang; Jianing Wang; Zhicheng Zhong; Feng Lin; Qiang Zhao (Theoretical and Applied Climatology, 2025)

Impact of particle geometry and critical dimensionless parameters on hydraulic collection performance of near-wall particles - Xiu Li; Lixin Xu; Yajiao Liu; Peilin Dou; Zhichao Hong; Chaoshuai Han (Ocean Engineering, 2025)

Simulation study on damage behavior of a shallow-buried Foundation bridge under combined action of flood scouring and heavy vehicle load - Tong Wu; Gangping Fan; Chuandong Dou; Xing Li; Chunyang Dou; Jian Che; Tianzhuo Wang; Jincheng Rao (Ocean Engineering, 2025)

Performance study of high-temperature proton exchange membrane fuel cell based on novel fan-fins gas channel - Zhiqing Zhang; Hui Liu; Feng Jiang; Shuwan Cui; Mingzhang Pan; Dongmei Li; Guangyu Ma; Jiajia Dou (Journal of Environmental Chemical Engineering, 2025)

Elucidating the biofilm formation process, microstructure and functional gene expression of Listeria monocytogenes in beef juice - Yangtai Liu; Lili Hu; Zhuosi Li; Huajian Zhu; Xin Dou; Yue Ma; Xiaojie Qin; Xiang Wang; Xuejuan Xia; Qingli Dong (International Journal of Food Microbiology, 2025)

Bending performance of highly pressured inflatable membrane arches - Runsheng Zhao; Xiongyan Li; Wei Wang; Suduo Xue; Fengchun Dou (Engineering Structures, 2025)

Stereo-selectivity of enantiomeric inhibitors to ubiquitin-specific protease 7 (USP7) dissected by molecular docking, molecular dynamics simulations, and binding free energy calculations - Yusheng Zhang; Wenwen Dou; Ziqi Zhao; Guozhen Li; Chunlong Li; Xiangyu Chen; Linkai Mou (Molecular Diversity, 2025)

Comparing Surface Mass Balance and Surface Temperatures From Regional Climate Models and Reanalyses to Observations Over the Antarctic Ice Sheet - Xiaofeng Wang; Peter L. Langen; Rongxing Li; Gang Qiao; Xiaopeng Fan; Yinke Dou; Xiangbin Cui (International Journal of Climatology, 2025)
This article assesses the performance of surface mass balance (SMB) and surface temperature products from seven climate models (ERA5, MERRA2, HIRHAM5_ERA‐Interim, HIRHAM5_ERA5, MARv3.11, RACMO2.3p1 and RACMO2.3p2) to be used as inputs to firn densification models (FDMs), crucial for the whole Antarctic mass balance estimation. The evaluation compiles and utilises a new dataset combining existing observations with 184 stake SMB measurements in the Vostok region and two SMB radar transects in Blåskimen Island and Nivlisen Ice Shelf, significantly enhancing the AntSMB dataset. For temperatures at 10 m (T10), 992 observations are included, offering vastly improved spatial coverage. Compared with multi‐year SMB observations, RACMO2.3p1 and ERA5 align closely with observed SMB over the inland and the whole Antarctic, with ERA5 exhibiting superior alignment in coastal areas. However, in terms of temporal SMB variations, ERA5, RACMO2.3p2 and HIRHAM5_ERA‐Interim demonstrate the best consistency with observed SMB, with ERA5 excelling in regression slope comparisons. In our surface temperature evaluation, RACMO2.3p2 and ERA5 have a minimal mean bias from T10 over the whole Antarctic. RACMO2.3p2 performs well with few occurrences of deviations beyond ±3°C in coastal areas, while RACMO2.3p2 and HIRHAM5_ERA5 are both close to T10 in inland areas. In inter‐model SMB comparisons, ERA5, HIRHAM5_Interim, HIRHAM5_ERA5, RACMO2.3p1 and RACMO2.3p2 exhibit similar deviations from the multi‐model mean (MMM), while MARv3.11 and MERRA2 show larger deviations in some coastal areas. For surface temperature, MARv3.11 and ERA5 display larger deviations from the MMM in some coastal areas where ERA5 actually matches the observations well, illustrating that MMM should not be taken to represent the true climate conditions. In conclusion, ERA5 demonstrates the best overall consistency with SMB and T10 observations compared with the other models.

Effects of Gillnet Mesh Size on the Size Selectivity and Catch Efficiency for Two Rockfish in the Artificial Reef Area of Shandong Province, China - Liyou Zhang; Mengjie Yu; Yilin Dou; Linjie Li; Guangrui Qi; Yanli Tang (Fisheries Management and Ecology, 2025)
Gillnets are the most commonly used fishing gear targeting black rockfish ( Sebastes schlegeli ) and fat greenling ( Hexagrammos otakii ) in the artificial reef area in coastal China. However, a minimum mesh size (MMS) has not yet been established for this fishery, which is unfavorable for sustainable development and effective management of fishery resources. We compared size selectivity and catch efficiency of gillnets of four commonly used mesh size (stretched mesh size; 40, 50, 60, and 70‐mm) in a typical artificial reef area in the Yellow Sea, China. Increasing the mesh size improved size selectivity of gillnets for black rockfish and fat greenling by reducing the proportion of undersized individuals. Further, changes in mesh size affected catch efficiency of target‐sized individuals. To protect juveniles, while maintaining catch efficiency for target‐sized fish, we recommend 60‐mm as the MMS for this fishery. Our study will contribute to the development of MMS regulations in reef fisheries management in China.

Coapplication of biochar and nitrogen fertilizer affects soybean yield by regulating the microbiome and metabolite profile of rhizosphere soil - Hui Liu; Wanyu Dou; Wenlong Zhang; Guoxin Shi; Yutao Li; Lihong Wang (Rhizosphere, 2025)

Risk assessment of broflanilide resistance in Panonychus citri (McGregor): Cross-resistance, inheritance and relative fitness - Ke Li; Chunyu Zhang; Yiting Ren; Xunyan Liu; Deng Pan; Wei Dou; Jin-Jun Wang; Guorui Yuan (Pesticide Biochemistry and Physiology, 2025)

A typical NLR recognizes a family of structurally conserved effectors to confer plant resistance against adapted and non-adapted Phytophthora pathogens - Xiaohua Dong; Xu Lu; Hai Zhu; Zhengxue Zhu; Peiyun Ji; Xianglan Li; Tianli Li; Xiong Zhang; Gan Ai; Daolong Dou (Molecular Plant, 2025)

Evolutionary trends and photothermal catalytic reduction performance of carbon dioxide by MOF-derived MnOx - Dou Chuanchuan; Liu Yuling; Shu Hao; Li Shuaishuai; Shi Qiyuan; Luo Xinzeng (Fuel, 2025)

The role of GSK3β signaling mediated lysosomal biosynthesis dysregulation in fluoride-induced neurological impairment - Yi Cheng; Yuhui Du; Yue Hu; Xinying Wang; Qingyuan Li; Xi Yan; Ming Dou; Weihua Jia; Fangfang Yu; Yue Ba; Guoyu Zhou (Food and Chemical Toxicology, 2025)

Multifunctional Modification of the Buried Interface in all-inorganic perovskite solar cells - Linde Li; Yuanyuan Zhao; Qing Su; Qiyao Guo; Jialong Duan; Jie Dou; Liqing Sun; Qiang Zhang; Qunwei Tang (Chemical Engineering Journal, 2025)

The role of lignin-molybdenum disulfide as a nano-filler in enhancing the performance of crosslinked hydrogel nanofibers membrane for lithium-ion battery separators - Yun Dou; Shen Li; Xinxin Zhu; Xia Meng; Shoujuan Wang; Magdi E. Gibril; Fangong Kong (Chemical Engineering Journal, 2025)

PbSQE3 and PbSQE6 regulates the formation of triterpenoid compounds in the russet mutant of ‘Dangshansuli variety’ pear - Zhenfeng Ye; Daozhi Yao; Qi Liu; Lingxia Chen; Lindong Dou; Jinhui Yu; Jie Deng; Zixiao Wu; Li Cao; Li Liu; Wei Heng (Acta Physiologiae Plantarum, 2025)

Multi-mode vibration suppression of a floating raft system via a tristable nonlinear energy sink - Jinxin Dou; Zhenping Li; Hongliang Yao; Tianzhi Yang; Shengji Liang (Ocean Engineering, 2025)

Sedimentation of tidal sand ridges off the Liuguhe River mouth in the Liaodong Bay, Bohai Sea - Libo Wang; Jun Li; Jingtao Zhao; Fenglong Bai; Bangqi Hu; Yanguang Dou; Weiyu Song; Liang Zou (Marine Geology, 2025)

Influence of atomic coordination on the activity of lattice oxygen and catalytic oxidation of toluene over regular Cu2O crystalline - Linlin Deng; Mingtai Li; Xin Gao; Xiaokun Yi; Yang Zhao; Yulong Yang; Zitong Zhao; Jiarui Chen; Baojuan Dou; Feng Bin (Journal of Hazardous Materials, 2025)

Rapid capture of perfluorooctanoic acid and perfluorooctane sulfonate at environmentally relevant concentrations via the ‘mesh trap’ of triazine-based polymer network: Mechanism and photocatalytic regeneration - Boru Gao; Lairong Wu; Shaokang Li; Jinjin Yang; Mengmeng Dou; Genwang Chang; Xiang Li (Journal of Hazardous Materials, 2025)

Single-atom Ag confined with nitrogen coordination in porous tubular g-C3N4 as fenton-like photocatalyst for solar-powered water purification - Yanchun Huang; Weifang Huang; Luming Dou; Longguo Li; Chao Liu; Bo Lai; Naiwen Li (Journal of Cleaner Production, 2025)

The economic inequality effect of environmental policies--a case from China's "authoritarian environmentalism" actions - Yanqiong Zhao; Shiquan Dou; Junhui Li; Jinhua Cheng; Deyi Xu (Journal of Environmental Management, 2025)

Novel bimetallic MIL-53(Fe/Mn) as dual cocatalysts promote charge separation efficiency of CdS for photocatalytic reduction of CO2 - Ruina Xuan; Jiwen Chen; Yixin Dou; Zhuo Jiang; Xiaofang Li; Deng Ding; Chunlei Wang; Juntao Yan; Linbing Sun (Journal of Environmental Chemical Engineering, 2025)

Experimental and numerical study on establishment, fuel-N conversion, and heat transfer of swirl, non-premixed MILD, and premixed MILD combustion - Shunta Xu; Chengxin Dou; Liyang Xi; Songjie Tian; Weijie Li; Hao Liu (Fuel, 2025)

Efficient photocatalytic CO2 and Cr(VI) reduction on carbon quantum dots/carbon nitride heterojunctions - Zhengdong Xu; Xun Su; Penghui Yang; Junbo Zhong; Minjiao Li; Clemens Burda; Lin Dou (Fuel, 2025)

Quantitative analysis of 4-hydroxy-2-nonenal (HNE) in fish muscle by high-performance liquid chromatography with pre-column derivatization using (2,4-dinitrophenyl)-hydrazine - Ruifang Feng; Xin Xiong; Peipei Dou; Jinlin Li; Soottawat Benjakul; Yongkang Luo; Yuqing Tan; Hui Hong (Food Chemistry, 2025)

Asymmetrical flow field-flow fractionation coupled with multi-detector: A robust method for evaluating the degradation of jujube polysaccharides with ultrasound-assisted H2O2 and subsequent conjugation with soybean 7S globulin - Jiaqi Li; Xirui Zhang; Haichen Lian; Chenjing Zhang; Hailiang Zheng; Dandan Han; Haiyang Dou (Food Chemistry, 2025)

Functional characteristics and mechanisms of microbial community succession and assembly in a long-term moving bed biofilm reactor treating real municipal wastewater - Fuqiang Fan; Mingtao Li; Junfeng Dou; Jiaqi Zhang; Danyi Li; Fangang Meng; Yue Dong (Environmental Research, 2025)

Comparison of spring phenology simulation in central Asian grasslands - Xin Dou; Lizhou Wu; Chengyi Zhao; Juyan Li; Yingyu Yan; Jianting Zhu; Dandan Wang (Ecological Modelling, 2025)

High-Detectivity Photomultiplication-Type organic photodetectors with Non-Fused ring electron acceptor Enabled by solid Additive-Induced efficient hole tunneling injection - Chengwei Shan; Dou Luo; Jie Zeng; Tingting Dai; Xiaoyu Gu; Xiaowei Xu; Zhibin Li; Erjun Zhou; Baomin Xu; Aung Ko Ko Kyaw (Chemical Engineering Journal, 2025)

Coseismic surface ruptures of MW7.8 and MW7.5 earthquakes occurred on February 6, 2023, and seismic hazard assessment of the East Anatolian Fault Zone, Southeastern Türkiye - Peng Liang; Yueren Xu; Xiaocheng Zhou; Ying Li; Qinjian Tian; Huiping Zhang; Zhikun Ren; Jingxing Yu; Chuanyou Li; Zheng Gong; Shiguang Wang; Aixia Dou; et al. (Science China Earth Sciences, 2025)

Crossbreeding of three selected strains of Crassostrea gigas reveals heterosis in survival and growth - Kunyin Jiang; Fangjian Dou; Qi Li (Aquaculture International, 2025)

The effect of Pseudomonas plecoglossicida vgrG gene on the immune response of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Dou Yang; Qi Li; Lingmin Zhao; Pan Wang; Chuanzhong Zhu; Yingzhe You; Qingpi Yan (Aquaculture, 2025)

A systematic review of the variability of freshly-emitted and aged black carbon based on various measurement techniques - Bobo Wu; Zichun Wu; Jiahang Dou; Zhiliang Yao; Xianbao Shen; Ao Wang; Long Li; Xuewei Hao (Science of The Total Environment, 2025)

Transport and deposition of terrestrial organic matter in marine littoral deltas: New evidence from flume experiments and 3D laser scanning - Yang Li; Wei Li; Yaohui Xu; Jianyong Xu; Kaiming Su; Hai Liu; Luxing Dou (Sedimentary Geology, 2025)

Thermochronological constraints on the evolution of the Bongor Basin, Chad - Ruxin Ding; Li Wang; Kunye Xiao; Yangshijia Li; Jie Hu; Yebo Du; Yu Yang; Xinshun Zhang; Lirong Dou (Marine and Petroleum Geology, 2025)

Experimental and numerical study on scroll compressor under different profile correction and discharge ports shapes - Kang Li; Chunyu Li; Soheil Mohtaram; Ni Liu; Hua Zhang; Binlin Dou; Chao Li; Qize He; Mohd Abul Hasan; Saiful Islam; Jingwu Wang; Zilong Wang; et al. (International Journal of Refrigeration, 2025)

3D CFD-DEM modeling of sand production and reservoir compaction in gas hydrate-bearing sediments with gravel packing well completion - Xiaofeng Dou; Zhichao Liu; Dianheng Yang; Yingjie Zhao; Yanlong Li; Deli Gao; Fulong Ning (Computers and Geotechnics, 2025)

MemriSim: A theoretical framework for simulating electron transport in oxide memristors - Shuwei Zhai; Wenjin Gao; Guoxiang Zhi; Tianzhao Li; Wenzhen Dou; Miao Zhou (Computer Physics Communications, 2025)

Perfluorodecanoic acid induces the increase of innate cells in zebrafish embryos by upregulating oxidative stress levels - Juhua Xiao; Dou Yang; Boxi Hu; Wenwen Zha; Weirong Li; Ying Wang; Fasheng Liu; Xinjun Liao; Huimin Li; Qiang Tao; Shouhua Zhang; Zigang Cao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Dual-cocatalysts-embedded hollow photocatalysis system drives solar fuel production - Tianwei Zhao; Jinyan Xiong; Wei Li; Gang Cheng; Shi Xue Dou (Chemical Engineering Journal, 2025)

Anion-regulated weakly solvation sulfolane-based electrolyte towards high-voltage lithium metal batteries - Jing Zhou; Ben Ma; Qinglei Wang; Li Su; Keli Yang; Xuesheng Song; Xianghao Dou; Mengru Wang; Xuehui Shangguan; Faqiang Li (Chemical Engineering Journal, 2025)

Single-atom Ag porous tubular carbon nitride photocatalyst with N-vacancies as efficient visible-light periodate activator: Performance and mechanism - Luming Dou; Weifang Huang; Yanchun Huang; Chao Liu; Naiwen Li; Jun Li; Bo Lai (Chemical Engineering Journal, 2025)

Phototunable phosphorescence energy transfer based on photodimerization of coumarin-12-crown-4 accelerated by γ-cyclodextrin - Hui-Juan Wang; Yan-Tao Li; Ming-Che Shao; Chang-Shuo Yu; Jin-Yao Yang; Lingyang Liu; Suna Wang; Jianmin Dou (Chemical Engineering Journal, 2025)

Synergistic enhancement of low-temperature strength and toughness in poly(boron-urethane) elastomers via π-π stacking and hydrogen bonding - Jing Yang; Pengrui Cao; Qian Dou; Lihe Guo; Yanhui Li; Yaoming Zhang; Jie Yan; Qihua Wang; Zhen Xu; Haijiao Xie; Tingmei Wang; Liming Tao (Chemical Engineering Journal, 2025)

Transmission of respiratory diseases in high-metabolic environments: A case study of gym - Haochen Zhang; Pengcheng Zhao; Zhiyang Dou; Boni Su; Yuguo Li; Nan Zhang (Building and Environment, 2025)

Forecasting step-like landslide displacement through diverse monitoring frequencies - Fei Guo; Zhizhen Xu; Jilei Hu; Jie Dou; Xiaowei Li; Qinglin Yi (Journal of Mountain Science, 2025)

Regulatory effects of high concentrate diet synergistically fermented with cellulase and lactic acid bacteria: In vitro ruminal fermentation, methane production, and rumen microbiome - Haokai Ma; Ao Dong; Yiou Xu; Qinghua Wu; Modinat Tolani Lambo; Yonggen Zhang; Xiujing Dou; Yang Li (Animal Feed Science and Technology, 2025)

Pilot scale application of 226Ra-contaminated soil leaching remediation - Juncheng Han; Guangming Xu; Kexin Shao; Haotian Yang; Aizhong Ding; Zhaorong Shang; Hongtu Sun; Ling Chen; Zhiyuan He; Qiao Li; Hongbo Fan; Junfeng Dou (Chemosphere, 2024)

Cobalt doped g-C3N4 activated peroxymonosulfate for organic pollutant degradation: Alterations in cobalt species and reactive oxygen species - Yuesen Wang; Yanchun Huang; Yi Chen; Luming Dou; Yi Ren; Naiwen Li; Bo Lai; Bo Tan (Chemosphere, 2024)

Implosion mechanisms of metallic cylindrical shells subjected to combined explosive loading and hydrostatic pressure - Zhixin Huang; Shuangtao Dou; Xianben Ren; Ying Li (Ocean Engineering, 2024)

Constructing a visual detection method for coagulation effect based on image feature machine learning - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao; Hao Shu (Journal of Water Process Engineering, 2024)

Landscape fragmentation of built-up land significantly impact on water quality in the Yellow River Basin - Jinghui Dou; Rui Xia; Kai Zhang; Chao Xu; Yan Chen; Xiaoyu Liu; Xikang Hou; Yingze Yin; Lina Li (Journal of Environmental Management, 2024)

Weathering and pedogenesis of the Holocene aeolian loess-paleosol sections in the Guanzhong Basin on the Chinese Loess Plateau - Yan Zhu; Yuzhu Zhang; Ninglian Wang; Shuheng Li; Menglei Wu; Yanfeng Li; Jianxi Li; Jiangli Pang; Yao Jin; Dou Chen; Qili Xiao; Pengpeng Cao; et al. (Journal of Asian Earth Sciences, 2024)

Investigating dehumidification and heating performance in a dual evaporator heat pump system for electric vehicles - Kang Li; Mingfei Tan; Yuan Man; Hua Zhang; Binlin Dou; Ni Liu; Tianjiao Zhang; Qize He; Lin Su; Soheil Mohtaram (International Journal of Refrigeration, 2024)

Refined one-dimensional modeling and experimental validation of scroll compressor with vapor injection for electric vehicles - Kang Li; Jiayun Hu; Chao Li; Xuejin Zhou; Ni Liu; Hua Zhang; Binlin Dou; Qize He; Ran Tu; Lin Su; Soheil Mohtaram (International Journal of Refrigeration, 2024)

Hydroxyl-functionalized cationic porous organic polymers for efficient enrichment and detection of phenolic endocrine disrupting chemicals in water and snapper - Yiran Dou; Zhi Li; Chenhuan Wang; Qianqian Wang; Zhi Wang; Qiuhua Wu; Chun Wang (Food Chemistry, 2024)

Perfluoroalkyl substances exposure and the risk of breast cancer: A nested case-control study in Jinchang Cohort - Qian Dou; Yana Bai; Yongjun Li; Shan Zheng; Minzhen Wang; Zhongge Wang; Jianyun Sun; Desheng Zhang; Chun Yin; Li Ma; Yongbin Lu; Lizhen Zhang; et al. (Environmental Research, 2024)

Regulatory roles of extracellular polymeric substances in uranium reduction via extracellular electron transfer by Desulfovibrio vulgaris UR1 - Guangming Xu; Haotian Yang; Juncheng Han; Xinyao Liu; Kexin Shao; Xindai Li; Guanying Wang; Weifeng Yue; Junfeng Dou (Environmental Research, 2024)

Driving factors of the distribution of microplastics in the surface soil of the typical uninhabited and habited areas in the Qinghai–Tibet plateau, China - Linyue Dai; Ruiqi Dou; Chunlong Jiang; Qinghai Xu; Yuecong Li; Fang Tian; Jifeng Li; Huiru Li; Zixiao Guo; Xueyong Zou; Chunping Chang; Zhongling Guo (Environmental Pollution, 2024)

Can the infection risk in elevators be negligible? A comparative study of airborne infection probability in elevators and conference rooms - Xian Li; Liangyu Zhu; Nan Zhang; Jianlin Liu; Wei Hua; Weichao Dou; Lihua Wei; Qingxia Tao; Fei Liu; Yunxiao Wang; Dongyu Xu (Energy and Buildings, 2024)

Li3VO4 mesocubes with exposed (200) facet as dendrite-free anode materials for high-safety Li-ion batteries - Didi Wang; Yijing Zhao; Pengchao Liu; Chunsheng Li; Chen Yang; Yan Sun; Meiqi Zhang; Yuqing Yang; Qing Wang; Guoliang Dai; Yuhai Dou; Chao Wu; et al. (Chemical Engineering Journal, 2024)

Ground-based MAX-DOAS observations of tropospheric formaldehyde and nitrogen dioxide: Insights into ozone formation sensitivity - Yuanyuan Qian; Dan Wang; Zhiyan Li; Houtong Liu; Haijin Zhou; Ke Dou; Liang Xi; Fuying Tang; Fuqi Si; Yuhan Luo (Atmospheric Pollution Research, 2024)

Amplification of warming-wetting in high mountains and associated mechanisms during the 21st century in Xinjiang, Central Asia - Rong Chen; Keqin Duan; Peihong Shi; Wei Shang; Junhua Yang; Jinping He; Yali Meng; Mingyu Dou; Liang Li (Climatic Change, 2024)

Processing of N-glycans in the ER and Golgi influences the production of surface sialylated glycoRNA - Yi-Shi Liu; Yu-Long Miao; Yue Dou; Ze-Hui Yang; Wenhao Sun; Xiaoman Zhou; Zijie Li; Nakanishi Hideki; Xiao-Dong Gao; Morihisa Fujita (Glycoconjugate Journal, 2024)

Decrypting the viral community in aerobic activated sludge reactors treating antibiotic production wastewater - Aixi Tang; Jiayu Zhang; Jin Huang; Yu Deng; Dou Wang; Pingfeng Yu; Renxin Zhao; Yulin Wang; Zihan Chen; Tong Zhang; Bing Li (Water Research, 2024)

Microbial fertilizers improve soil quality and crop yield in coastal saline soils by regulating soil bacterial and fungal community structure - Qicong Wu; Yang Chen; Xiaohui Dou; Dongxi Liao; Kaiyi Li; Chunchun An; Guohui Li; Zhi Dong (Science of The Total Environment, 2024)

Innovative energy solutions: Evaluating reinforcement learning algorithms for battery storage optimization in residential settings - Zhenlan Dou; Chunyan Zhang; Junqiang Li; Dezhi Li; Miao Wang; Lue Sun; Yong Wang (Process Safety and Environmental Protection, 2024)

Analysis of the effect of geometric and flow parameters on the separation efficiency of virtual impact separators: Optimization based on response surface methodology - Wen Nie; Yuxin Dou; Changwei Xu; Huitian Peng; Fei Liu; Haoming Li; Huaitong Li; Junchao Wan (Process Safety and Environmental Protection, 2024)

Numerical analysis of dynamic and fatigue characteristics of deep-sea mining riser considering irregular waves and currents - Yan Li; Xingkun Zhou; Yaning Dou; Xiantao Zhang; Wenhua Li (Ocean Engineering, 2024)

Hydro-morphology and water quality jointly shape the structure and network stability of the plankton community in multi-tributary river basins - Chao Chang; En Hu; Xudong Xue; Juan Li; Dou Du; Fang Yang; Ming Li (Journal of Hydrology, 2024)

Constructing a visual detection model for floc settling velocity using machine learning - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao (Journal of Environmental Management, 2024)

Employing genome-wide association studies to investigate acid adaptation mechanisms in Listeria monocytogenes - Xin Dou; Yangtai Liu; Kostas Koutsoumanis; Chi Song; Zhuosi Li; Hui Zhang; Fan Yang; Huajian Zhu; Qingli Dong (Food Research International, 2024)

Glycogen and zinc-enriched ferritin as bioavailable nanoparticulate nutrients released from gastrointestinal digestion of pacific oyster (Crassostrea gigas) - Shiyang Li; Yangguang Li; Mengting Dou; Meichao Zhang; Zifang Zhao; Haohao Wu; Suqin Zhu; Adewale Olusegun Obadina (Food Chemistry, 2024)

In situ regulating the interfacial work function of Ag doped Ni(OH)2 via trace of Fe2+ for efficient water splitting - Min Li; Runlin Huang; Chao Feng; Longfei Sun; Yanan Zhou; Haijun Liu; Chi Jiang; Yingli Wang; Jie Dou; Qiyao Guo; Yuanyuan Zhao; Jialong Duan; et al. (Chemical Engineering Journal, 2024)

Quantitative pre-lithiation modulation of aluminum foil anode kinetics enables high rate and stable cycling of high-loading all-solid-state batteries - Zengjie Fan; Bing Ding; Zhiwei Li; Zhi Chang; Langyuan Wu; Ben Hu; Chong Xu; Hui Dou; Xiaogang Zhang (Chemical Engineering Journal, 2024)

Corrigendum to “Design of molecular scale inhibitors for high temperature industrial cooling water systems based on group synergistic effects” [Chem. Eng. J. 494 (2024) 153164] - Jing Fang; Zhiqiu Ye; Zhansi Dou; Yanhua Zhang; Wei Wu; Yuan Hu; Bibo Wang; Hao Li (Chemical Engineering Journal, 2024)

Three-dimensional porous SiC/BDD electrode with long-term robustness and enhanced electrochemical degradation performance for refractory organic pollutants - Xiang Wang; Jinjie Dou; Zejun Deng; Mingchen Gong; Kechao Zhou; Li Ma; Qiuping Wei (Chemical Engineering Journal, 2024)

Enhanced Zinc-air battery performance and local electrochemical evaluation of atomically dispersed Co and Ni in S, N-codoped carbon nanofibersvia scanning electrochemical microscopy - Haoran Pan; Chen Zhang; Jiabin Wu; Huaiguang Li; Teng Zhang; Xinning Huang; Wenguang Tu; Jianglong Yu; Jinxiao Dou; Xingxing Chen (Chemical Engineering Journal, 2024)

Novel chitosan-oligosaccharide derivatives as fluorescent green corrosion inhibitors for P110 steel - Yue Wang; Feng Dou; Jian Han; Kaili Liu; Jihui Li; Huixin Zhang; Jianxin Chen (Carbohydrate Polymers, 2024)

Micromorphological characteristics and environmental significance of the Holocene aeolian loess-paleosol section in the Zoige Basin - Dou Chen; Jiangli Pang; Yuzhu Zhang; Chun Chang Huang; Yali Zhou; Xiaochun Zha; Yuqin Li; Qili Xiao; Xiaokang Zhao (CATENA, 2024)

Performance study of a novel indirect evaporative/air-cooled thermoelectric cooling air conditioning system - Yujie Duan; Yuanyuan Zhou; Zhongyu Dou; Qiumin Dai; Yanshun Yu; Qiang Li (Building and Environment, 2024)

Heterogenous impact of background meteorological factors on the cooling effect of two types of typical urban parks: Evidence from Shanghai, China - Xiaolei Geng; Dou Zhang; Wei Sun; Yuan Yuan; Chengwei Li; Zhaowu Yu (Building and Environment, 2024)

Assessment of brittle failure in deep tunnels via true triaxial compression - Ben-Guo He; Hong-Pu Li; Xiang-Rui Meng; Si-Yuan Dou; Shengcun Yan; Tao Chen (Tunnelling and Underground Space Technology, 2024)

Salvianolic acid B improves mitochondrial dysfunction of septic cardiomyopathy via enhancing ATF5-mediated mitochondrial unfolded protein response - Renshan Chen; Anran Zheng; Yunjing Wang; Liyou Guo; Huaqian Dou; Liangyan Lu; Muhammad Rafiq; Peihua Li; Xiuhui Chen; Qing Xiao (Toxicology and Applied Pharmacology, 2024)

Dose-dependent effects of different parabens on food waste biorefinery for volatile fatty acids production: Insight into specific fermentation processes, substrates transformation and microbial metabolic traits - Ziyu Li; Yuting Dou; Zhenzhou Li; Yujie Yuan; Qin Zhang; Song Cheng; Xiaoshi Cheng; Jingyang Luo (Science of The Total Environment, 2024)

Characteristics of methane and carbon dioxide in ice caves at a high-mountain glacier of China - Zhiheng Du; Hao Cui; Lei Wang; Fangping Yan; Yushuo Liu; Qian Xu; Simin Xie; Tingfeng Dou; Yanzhao Li; Pengfei Liu; Xiang Qin; Cunde Xiao (Science of The Total Environment, 2024)

A superstructure-based model for the evolution of park-wide water infrastructure - Zhiwei Li; Ziting Ge; Chao Wang; Dawei Zhang; Jianghai Dou; Raymond R. Tan; Fang Wang; Xiaoping Jia (Journal of Cleaner Production, 2024)

3D DEM investigation on macro-meso mechanical responses of gas hydrate-bearing sediments in process of unloading confining pressure - Xiaofeng Dou; Qi Wu; Zhichao Liu; Yingjie Zhao; Yanlong Li; Zhangxin Chen; Deli Gao; Fulong Ning (Gas Science and Engineering, 2024)

Deciphering the pivotal material properties of perovskite for hydrogen production in tar catalytic cracking - Wang-mi Chen; Bei-dou Xi; Mei-ying Ye; Ming-xiao Li; Jia-qi Hou; Yu-fang Wei; Cheng-ze Yu; Fan-hua Meng (Fuel, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Sludge-based biochar preparation: pyrolysis and co-pyrolysis methods, improvements, and environmental applications - Jun Cao; Yutong Jiang; Xiao Tan; Lei Li; Songshan Cao; Jiayao Dou; Runqi Chen; Xiaoyun Hu; Zhiheng Qiu; Ming Li; Ziyin Chen; Hualun Zhu (Fuel, 2024)

Preparation of high V-type relative crystallinity dextrin from V-type granular starch via high-temperature acid-ethanol hydrolysis - Jiahui Wang; Jiaqi Dou; Zixin Shu; Lele Li; Zhengyu Jin; Xing Zhou (Food Bioscience, 2024)

Rapid and accurate detection of Salmonella enterica serovar Enteritidis using a one-step LAMP-CRISPR/Cas12b method - Jiansen Gong; Di Zhang; Jingxiao Xu; Tingting Li; Zhipeng Zhang; Xinhong Dou; Chengming Wang (Food Control, 2024)

An integrated analysis framework of supply, demand, flow, and use to better understand realized ecosystem services - Shuyao Wu; Kai-Di Liu; Wentao Zhang; Yuehan Dou; Yuqing Chen; Taiping Zhang; Delong Li (Ecosystem Services, 2024)

Enhanced High-Temperature performance of PEI dielectrics via deep trap energy levels and physically crosslinked effects - Deng Hu; Hang Luo; Yuan Liu; Fan Wang; Bo Peng; Xiaona Li; Huan Wang; Guanghu He; Dou Zhang (Chemical Engineering Journal, 2024)

Nanofibrous dressing with drug/electroactivity synergistic effect for wound healing - Jinmiao Chen; Xihui Jia; Shuang Wang; Xueqin Wang; Ling Li; Guangting Han; Yuejie Dou; Jiwei Li (Chemical Engineering Journal, 2024)

A sulfhydryl-functionalized vinylene-linked covalent organic framework for promoting gold recovery by light-assistance - Di Jiang; Zhen-Lei Wang; Yuan-Zhe Cheng; Ya-Xi Yu; Hui-Yuan Kong; Xin-Yue Bian; Xiao-Meng Dou; Shun-Li Li; Dong-Hui Yang; Xuesong Ding; Bao-Hang Han (Chemical Engineering Journal, 2024)

Different contributions of meteorological conditions and emission reductions to the ozone pollution during Shanghai’s COVID-19 lockdowns in winter and spring - Xuedan Dou; Mengying Li; Yaping Jiang; Zhe Song; Pengfei Li; Shaocai Yu (Atmospheric Pollution Research, 2024)

The invasive Alternanthera philoxeroides modifies the sediment microbiome in urban and periurban river wetlands - Tong Wang; Jinming Yang; Yongfeng Zhu; Zeyu Zhang; Xiaolong Chi; Zhen Sun; Chunlin Wang; Lizheng Fang; Hongrui Dou; Zhenghao Fan; Shimei Li; Chunhua Liu (Urban Ecosystems, 2024)

Erratum to: A justice and innovative way ahead of consumption-based emission accounting approach - Qun Shen; Hongbo Duan; Yun Tang; Linbing Tang; Li Shang; Xinyu Dou; Wei Wei; Weiqiang Chen; Zhu Liu (Science China Earth Sciences, 2024)

Role of NF-κB signaling pathway in H2O2-induced oxidative stress of hiPSCs - Jian Qin; Jie Yang; Jun Li; Dipeng Zhao; Jie An; Zhuhui Zhai; Hejie Wang; Junling Li; Minmin Dou; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2024)

The Degradation and Migration of Cyclanilide in Soil and Sediment in China - Jian He; Yezhi Dou; Li Cao; Jian Yu; Tongliang Zhang; Jia Yu; Chunqin Cui; Deyang Kong; Juying Li (Bulletin of Environmental Contamination and Toxicology, 2024)

Classification Method of ECG Signals Based on RANet - Aoxiang Zhang; Xinwu Yang; Tong Li; Mengfei Dou; Hongxiao Yang (Cardiovascular Engineering and Technology, 2024)

Safety and efficacy of endoscope-assisted versus microscopic microvascular decompression surgery for hemifacial spasm: a prospective cohort study - Dou Yang; Wei Shu; Tao Du; Junchi Li; Hongwei Zhu (Acta Neurologica Belgica, 2024)

Sewage sludge pyrolysis ‘kills two birds with one stone’: Biochar synergies with persulfate for pollutants removal and energy recovery - Shaoya Li; Yanmei Zhou; Jin Wang; Mengmeng Dou; Qingyun Zhang; Kaili Huo; Chao Han; Jinyang Shi (Chemosphere, 2024)

Ridge-furrow film mulch with nitrogen fertilization improves grain yield of dryland maize by promoting root growth, plant nitrogen uptake and remobilization - Zhenlin Lai; Hui Zhang; Xiaohui Ding; Zhenqi Liao; Chen Zhang; Jiang Yu; Shengzhao Pei; Zhiyao Dou; Zhijun Li; Junliang Fan (Soil and Tillage Research, 2024)

Precise counter anion modulation of the self-assembly behavior-endowed ultrasensitive and specific dual-mode visualization of nitrate - Honghong Li; Jiguang Li; Baiyi Zu; Yuwan Du; Yuhong Su; Xincun Dou (Journal of Hazardous Materials, 2024)

Spatial heterogeneity of soil respiration after prescribed burning in Pinus koraiensis forest in China - Jianyu Wang; Yiyang Ding; Kajar Köster; Fei Li; Xu Dou; Guangxin Li; Tongxin Hu (Journal of Environmental Management, 2024)

Full-scale study on the coupling settling behavior of droplets and PM10 particles based on the CLSVOF method and wetting experiments - Wen Nie; Fei Liu; Lidian Guo; Huitian Peng; Qiang Liu; Changwei Xu; Yuxin Dou; Haoming Li (Fuel, 2024)

Hybrid nanovesicles comprising induced pluripotent stem cells and dendritic cell-derived exosomes enhance antitumor immunity - Ronghao Wang; Xianjun Li; Guining Fu; Mingyuan Hu; Haozhao Dou; Guihong Zhang; Qilin Pengshun; Jianfeng Mao; Tianchuan Zhu; Qingdong Cao (Chemical Engineering Journal, 2024)

Metal-organic cages for efficient capture and convenient detection of iodine from vapor and aqueous solutions - Zhi-Yong Zeng; Zhen-Chen Lou; Lianrui Hu; Weitao Dou; Xiaoli Zhao; Xiaodong Li; Junfeng Fang; Xuhong Qian; Hai-Bo Yang; Lin Xu (Chemical Engineering Journal, 2024)

A justice and innovative way ahead of consumption-based emission accounting approach - Qun Shen; Hongbo Duan; Yun Tang; Linbing Tang; Li Shang; Xinyu Dou; Wei Wei; Weiqiang Chen; Zhu Liu (Science China Earth Sciences, 2024)

Heat-shock transcription factor HsfA8a regulates heat stress response in Sorbus pohuashanensis - Yuyan Li; Qianwen Wu; Lingyi Zhu; Ruili Zhang; Boqiang Tong; Yan Wang; Yi Han; Yizeng Lu; Dequan Dou; Zhihui Tian; Jian Zheng; Yan Zhang (Planta, 2024)

A local rainfall-triggered giant landslide occurred in a region along a high-speed railway on the Qinghai–Tibetan Plateau - Qingpeng Li; Wenhui Liu; Renjie He; Chunye Ying; Hairui Liu; Zengning Dou; Yabing Liu; Sha Yang; Xianteng Song (Journal of Mountain Science, 2024)

Machine learning-based prediction of battery heat generation management in standard driving cycles to avoid thermal runaway and increasing safety - Zhenlan Dou; Chunyan Zhang; Dezhi Li; Zihua Ye; Yong Wang (Process Safety and Environmental Protection, 2024)

Constructing high-porosity composite membranes by loading novel CD@DCN in PVDF: Achieving superior permeability and selectivity simultaneously - Qingyun Zhang; Jin Wang; KaiLi Huo; Mengmeng Dou; Chao Han; Wubin Wang; Jizhen Li; Boru Gao (Journal of Water Process Engineering, 2024)

Occurrence, distribution characteristics and exposure assessment of perchlorate in the environment in China - Diancheng Dou; Ming He; Jinxin Liu; Shumin Xiao; Fu Gao; Wei An; Li Qi (Journal of Hazardous Materials, 2024)

Innovative detection mechanism for deltamethrin based on a dual-emitting Fluoroprobe and its application in a smartphone-based photoelectric conversion device - Zhongjie Li; Longtian Chen; Yuemao Dou; Huili Wang; Chunyang Chen; Xuedong Wang (Food Chemistry, 2024)

Design of molecular scale inhibitors for high temperature industrial cooling water systems based on group synergistic effects - Jing Fang; Zhiqiu Ye; Zhansi Dou; Yanhua Zhang; Wei Wu; Yuan Hu; Bibo Wang; Hao Li (Chemical Engineering Journal, 2024)

Lithium salt regulation enabling 3D printed solid-state electrolytes to achieve ultra-long cycle performance of LiNi0.8Mn0.1Co0.1O2 - Changgang Li; Shuolei Deng; Wenhao Feng; Yaowen Cao; Jiaxuan Bai; Qianqian Dou; Xiaocong Tian; Yifan Dong; Fan Xia (Chemical Engineering Journal, 2024)

Chemical looping dry reforming of waste glycerol coupled with thermochemical water splitting cycle by mesoporous Fe2O3-Co3O4/CeO2 oxygen carriers - Kai Wu; Binlin Dou; Hua Zhang; Yadong Wang; Haisheng Chen; Yujie Xu; Wei Li (Chemical Engineering Journal, 2024)

Numerical Simulation Study on Pressure-Relief Effect of Protective Layer Mining in Coal Seams Prone to Rockburst Hazard - Anliang Lu; Dazhao Song; Zhenlei Li; Xueqiu He; Linming Dou; Yarong Xue; Huakang Yang (Rock Mechanics and Rock Engineering, 2024)

Group A Streptococcal meningitis in children: a short case series and systematic review - Zhen-zhen Dou; Wanrong Li; Hui-Li Hu; Xin Guo; Bing Hu; Tian-ming Chen; He-ying Chen; Ling-yun Guo; Gang Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Group A streptococcal(GAS) meningitis is a severe disease with a high case fatality rate. In the era of increasing GAS meningitis, our understanding about this disease is limited. Purpose To gain a better understanding about GAS meningitis. Methods Five new cases with GAS meningitis were reported. GAS meningitis related literatures were searched for systematic review in PUBMED and EMBASE. Case reports and case series on paediatric cases were included. Information on demographics, risk factors, symptoms, treatments, outcomes, and emm types of GAS was summarized. Results Totally 263 cases were included. Among 100 individuals, 9.9% (8/81) had prior varicella, 11.1% (9/81) had anatomical factors, and 53.2% (42/79) had extracranial infections. Soft tissue infections were common among infants (10/29, 34.5%), while ear/sinus infections were more prevalent in children ≥ 3 years (21/42, 50.0%). The overall case fatality rate (CFR) was 16.2% (12/74). High risk of death was found in patients with shock or systemic complications, young children(< 3 years) and cases related to hematogenic spread. The predominate cause of death was shock(6/8). Among the 163 patients included in case series studies, ear/sinus infections ranged from 21.4 to 62.5%, while STSS/shock ranged from 12.5 to 35.7%, and the CFR ranged from 5.9 to 42.9%. Conclusions A history of varicella, soft tissue infections, parameningeal infections and CSF leaks are important clinical clues to GAS in children with meningitis. Young children and hematogenic spread related cases need to be closely monitored for shock due to the high risk of death.

The effect of soak time on pot escape opening selectivity in swimming crab (Portunus trituberculatus) fishery - Mengjie Yu; Bent Herrmann; Kristine Cerbule; Changdong Liu; Yilin Dou; Liyou Zhang; Linjie Li; Yanli Tang (Fisheries Research, 2024)

Learning spectral-indices-fused deep models for time-series land use and land cover mapping in cloud-prone areas: The case of Pearl River Delta - Zhiwei Li; Qihao Weng; Yuhan Zhou; Peng Dou; Xiaoli Ding (Remote Sensing of Environment, 2024)

Insight into the mechanisms involved in the improved antagonistic efficacy of Pichia caribbica against postharvest black spot of tomato fruits by combined application with oligochitosan - Xiaoyun Zhang; Yu Xin; Qingrong Yue; Esa Abiso Godana; Linlin Gao; Mengge Dou; Hongyao Zhou; Jun Li; Lina Zhao; Hongyin Zhang (Postharvest Biology and Technology, 2024)

Climatic and anthropogenic forcing of vegetation change at different altitudes on the northeastern Tibetan Plateau over the past millennium - Dou Chen; Youmo Li; Shilong Guo; Tao Wang; Lin Chen; Lanlan Hu; Jinghua Huang; Lili Pan; Xuyi Ma; Duo Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Genotoxicity and cytotoxicity evaluation of a heat-not-burn product - Fudong Fu; Xiaoyu Li; Younan Chen; Lan Li; Jiexiong Dou; Kun Liang; Yexian Chen; Yanrong Lu; Yuchuan Huang (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

An aeration requirements calculating method based on BOD5 soft measurement model using deep learning and improved coati optimization algorithm - Wangben Zhao; Yuling Liu; Xing Zhou; Shuaishuai Li; Chenxu Zhao; Chuanchuan Dou; Hao Shu (Journal of Water Process Engineering, 2024)

3D investigation of gully headcut processes: A slicing segmentation based on filed scouring experiments and laser scanning - Chendi Gao; Pengfei Li; Xin Yang; Jinfei Hu; Xiao Bai; Wanqiang Yao; Dou Li; Hooman Latifi; Jianjian Gao; Tianmin Dang; Pan Zhang (Journal of Hydrology, 2024)

Qualitative and quantitative analysis of electrons donated by pollutants in electron transfer-based oxidation system: Electrochemical measurement and theoretical calculations - Mengmeng Dou; Jin Wang; Zhaokun Ma; Chao Han; Wen Zhou; Qingyun Zhang; Shaoya Li (Journal of Hazardous Materials, 2024)

Pulsed electro-catalysis enables effective conversion of low-concentration nitrate to ammonia over Cu2O@Pd tandem catalyst - Fei Dou; Fengchen Guo; Bo Li; Kai Zhang; Nigel Graham; Wenzheng Yu (Journal of Hazardous Materials, 2024)

Synergistic interactions of electronic modulation and low crystallization in Ru-RuO2/C heterostructure for highly efficient multifunctional electrocatalysis - Yuanyuan Cong; Di Dou; Limin Zhang; Haibin Wang; Mengling Liu; Luyun Chen; Qiuping Zhao; Chunlei Li (Fuel, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Comparison of the physical stability, microstructure and protein-lipid co-oxidation of O/W emulsions stabilized by l-arginine/l-lysine-modified soy protein hydrolysate - Bin Zhu; Jinjie Yang; Jingjing Dou; Yijie Ning; Baokun Qi; Yang Li (Food Chemistry, 2024)

Effect of sheep bone protein hydrolysate on promoting calcium absorption and enhancing bone quality in low-calcium diet fed rats - Guanhua Hu; Xueying Sun; Shiqi Hao; Xiaotong Li; Min Qian; Lu Dou; Min Zhang; Puxin Hou; Lin Su; Lihua Zhao; Lina Sun; Ye Jin (Food Chemistry, 2024)

The removal of Cl− from acidic wastewater by Cu2+/VC: Through reduction & precipitation function - Wenyue Dou; Dong Li; Xiaoyi Zou; Zihan Wang; Yifei Song; Linghao Kong; Xingyun Hu (Desalination, 2024)

Flexible-Rigid Aluminum-Organic frameworks with Ultra-Fine Pore-Environment regulation for benchmark acetylene storage and purification - Hai-Peng Li; Jia-Wen Wang; Zhaodi Dou; Li-Zhou Wu; Ying Wang; Yucang Liang; Quan-Guo Zhai (Chemical Engineering Journal, 2024)

Sulfur-carbon loop enhanced efficient nitrogen removal mechanism from iron sulfide-mediated mixotrophic partial denitrification/anammox systems - Li Zhang; Yufei Cui; Quanhao Dou; Yongzhen Peng; Jiachun Yang (Bioresource Technology, 2024)

Mitigation of Desulfovibrio ferrophilus IS5 degradation of X80 carbon steel mechanical properties using a green biocide - Zhong Li; Jike Yang; Shihang Lu; Wenwen Dou; Tingyue Gu (Biodegradation, 2024)

Control of coptis root rot by combination of Bacillus cereus isolate Y9 and other antagonistic microorganisms - Pengying Mei; Tao Dou; Xuhong Song; Longyun Li (Journal of Plant Pathology, 2024)
Root rot is a destructive soil-borne disease of Coptis chinensis , which depends on chemical control at present, and more attention should be paid to biocontrol of disease. In the present research, isolate Y9 isolated from healthy root samples of Coptis , was identified as Bacillus cereus. Further screening and pot experiments showed that B. cereus isolate Y9 inhibited the growth of the main causal agents of coptis root rot disease ( Fusarium solani and F. avenaceum ) and seven other phytopathogenic fungi. The application of B. cereus isolate Y9 and compatible Trichoderma harzianum , T. atroviride and B. amyloliquefaciens , singly and in combination were found to be effective against Fusarium root rot in vitro and in field experiments. In field experiments, combinations of T. harzianum + B. amyloliquefaciens + Y9 (HYJ, in ratio of 1:1:1) showed the highest control efficacy of 63.85%, which was higher than the expected value (53.18%), indicating synergistic effect on the control of coptis root rot. Therefore, B. cereus isolate Y9 may be a potential biological control agent, and combined use with T. harzianum and B. amyloquefaciens offered even greater potential. The long-term effects of isolate B. cereus Y9 and its combinations on C. chinensis should be assessed in different locations and seasons in the future.

Effect of initial moisture content, resulting from different ratios of vegetable waste to maize straw, on compost was mediated by composting temperatures and microbial communities at low temperatures - Shanshan Sun; Cheng Guo; Jianyu Wang; Li Ren; Jianping Qu; Qi Guan; Nongxiao Dou; Jiahui Zhang; Qiuhua Chen; Qi Wang; Jiguang Wang; Jieming Li; et al. (Chemosphere, 2024)

Dual-specificity phosphatase 26 protects against kidney injury caused by ischaemia-reperfusion through restraint of TAK1-JNK/p38-mediated apoptosis and inflammation of renal tubular epithelial cells - Heli Xiang; Zepeng Li; Yang Li; Jin Zheng; Meng Dou; Wujun Xue; Xiaoyan Wu (Toxicology and Applied Pharmacology, 2024)

Degradation of the chiral fungicide penthiopyrad by six bacteria strains isolated from soils and the potential stereoselectivity - Jinming Chang; Li Dou; Shiyin Mu; Du Chi; Jing Shi; Kankan Zhang (Journal of Environmental Chemical Engineering, 2024)

The role of rcpA gene in regulating biofilm formation and virulence in Vibrio parahaemolyticus - Wenxiu Zhu; Jiaxiu Liu; Yingying Zhang; Dongyun Zhao; Shugang Li; Hanzheng Dou; Haisong Wang; Xiaodong Xia (International Journal of Food Microbiology, 2024)

Bio-adhesives derived from sewage sludge via hydrothermal carbonization: Influence of aqueous phase recycling - Zhi-Xiang Xu; Rui Dou; Fan Gao; Yong-Xing Chen; Li-Jian Leng; Sameh M. Osman; Rafael Luque (Chemical Engineering Journal, 2024)

Intelligent Off/On switchable electromagnetic wave absorbing material based on VO2 nanowires - Shuhui Liang; Huan Guan; Hainan Zhang; Xiangge Han; Jia Gao; Jiupeng Zhao; Shuliang Dou; Yao Li (Chemical Engineering Journal, 2024)

Response of anammox consortia to inhibition from high ferroferric oxide nanoparticles concentration and potential recovery mechanism - Li Zhang; Lixia Yang; Tingjun Dong; Jiachun Yang; Quanhao Dou; Shou-Qing Ni; Yongzhen Peng (Bioresource Technology, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Variations in Column Concentration of Greenhouse Gases in China and Their Response to the 2015–2016 El Niño Event - Ningwei Liu; Lingjun Xia; Youjun Dou; Shaorou Dong; Jing Wen; Ying Wang; Rui Feng; Ruonan Wang; Yuhe Li (Journal of Meteorological Research, 2024)

Culture of cerebrospinal fluid-contacting neurons from neonatal mouse spinal cord - Liang Cao; Hui-Qian Zhang; Yu-Qi He; Ping-Jiang An; Lei-Luo Yang; Wei Tan; Gang Liu; Chun-Qing Wang; Xiao-Wei Dou; Qing Li (Cell and Tissue Banking, 2024)

Differences among active toluene-degrading microbial communities in farmland soils with different levels of heavy metal pollution - Fei Dou; Yundang Wu; Jibing Li; Chuanping Liu (Biodegradation, 2024)

Research on channel selection of low-carbon product considering advertising promotion under substitute competition - Haiyan Li; Qihan Cui; Lei Dou; Han Song; Ying Dai; Xinran Hu (Environment, Development and Sustainability, 2024)

A multifactorial study of mass movement in the hilly and gully Loess Plateau based on intensive field surveys and remote sensing techniques - Lu Yan; Xiao Bai; Pengfei Li; Li Chen; Jinfei Hu; Dou Li; Xin Yang; Lifeng Liu; Jianjian Gao; Tianmin Dang (Science of The Total Environment, 2024)

Vulnerability optimization for determining water restoration strategies in industrial park water networks - Yanmei Zhang; Chenxuan Wang; Jianghai Dou; Zhiwei Li; Peidong Zhang; Raymond R. Tan; Fang Wang; Xiaoping Jia (Resources, Conservation and Recycling, 2024)

Effects of exercise on muscle fiber conversion, muscle development and meat quality of Sunit sheep - Lin Su; Congying Zhao; Bing Sun; Lu Dou; Chenlei Wang; Zhihao Yang; Tianle Li; Ye Jin (Meat Science, 2024)

Electroactive nanofibrous membrane with antibacterial and deodorizing properties for air filtration - Yuejie Dou; Na Wang; Shaohua Zhang; Caihong Sun; Jinmiao Chen; Zhenghai Qu; Aihua Cui; Jiwei Li (Journal of Hazardous Materials, 2024)

Ratiometric fluoroprobe based on Eu-MOF@Tb3+ for detecting tetracycline hydrochloride in freshwater fish and its application in rapid visual detection - Longtian Chen; Zhongjie Li; Yuemao Dou; Huili Wang; Chunyang Chen; Xuedong Wang (Journal of Hazardous Materials, 2024)

Modeling and evaluating costs and greenhouse gas emissions in solid waste management based on system dynamics in a mega-city: The case of Xi'an - Wangrui Dou; Haimei Li; Zhulin Li; Penglong Li; Chao Wu; Yili Liu (Journal of Cleaner Production, 2024)

Integrated machine learning reveals aquatic biological integrity patterns in semi-arid watersheds - Lina Li; Rui Xia; Ming Dou; Kai Zhang; Yan Chen; Ruining Jia; Xiaoxuan Li; Jinghui Dou; Xiang Li; Qiang Hu; Hui Zhang; Nixi Zhong; et al. (Journal of Environmental Management, 2024)

Aluminum exposure impairs oocyte quality via subcellular structure disruption and DNA damage-related apoptosis in mice - Hongge Li; Jingcai Liu; Weihua Nong; Mengying Shen; Sheng Dou; Shaochen Sun; Junli Wang (Journal of Environmental Sciences, 2024)

Growth, biofilm formation, and motility of Listeria monocytogenes strains isolated from food and clinical samples located in Shanghai (China) - BinRu Gao; Hua Cai; Biyao Xu; Fan Yang; Xin Dou; Qingli Dong; Hui Yan; Xiangfeng Bu; Zhuosi Li (Food Research International, 2024)

A dual-mode lateral flow immunoassay by ultrahigh signal-to background ratio SERS probes for nitrofurazone metabolites ultrasensitive detection - Yanli Tian; Xuechi Yin; Jiawei Li; Leina Dou; Shaochi Wang; Conghui Jia; Yuechun Li; Yaqian Chen; Shengxue Yan; Jianlong Wang; Daohong Zhang (Food Chemistry, 2024)

3D seismic mask auto encoder: Seismic inversion using transformer-based reconstruction representation learning - Yimin Dou; Kewen Li (Computers and Geotechnics, 2024)

Ultra-high electron affinity and peripheral electronegativity co-constructing all-organic dielectrics with outstanding capacitive performance at high temperature - Xiaona Li; Hang Luo; Yuting Wan; Bo Peng; Yuan Liu; Sheng Chen; Dou Zhang (Chemical Engineering Journal, 2024)

Coupling effect of vacancy defects and multi-adsorption sites in porous carbon cathode for high-performance aqueous zinc-ion hybrid capacitors - Heng-Xiang Li; Wen-Jing Shi; Ling-Yang Liu; Xiaohua Zhang; Peng-Fang Zhang; Qun Wang; Ying Liu; Zhao-Yang Wang; Jianmin Dou (Chemical Engineering Journal, 2024)

Transcriptome and small RNA analysis unveils novel insights into the C4 gene regulation in sugarcane - Xiuting Hua; Zhen Li; Meijie Dou; Yanqing Zhang; Dongxu Zhao; Huihong Shi; Yihan Li; Shuangyu Li; Yumin Huang; Yiying Qi; Baiyu Wang; Qiyun Wang; et al. (Planta, 2024)

Levels, Distribution and Ecological Risk Assessment of PBDEs in Soils and Plants Around the Engineering Plastics Factory - Jing Xu; Feng Ge; Jia Yu; Juying Li; Yezhi Dou; Didi Shan; Xiaoyu Cai; Deyang Kong (Bulletin of Environmental Contamination and Toxicology, 2024)

The Effects of Zinc Oxide Nanoparticles on Antioxidation, Inflammation, Tight Junction Integrity, and Apoptosis in Heat-Stressed Bovine Intestinal Epithelial Cells In Vitro - Yuanxiao Li; Mengying Pan; Sudan Meng; Wenhao Xu; Shuai Wang; Mengying Dou; Cai Zhang (Biological Trace Element Research, 2024)

Mapping sustainability-oriented China’s cropland use stability - Xinyuan Liang; Xiaobin Jin; Yue Dou; Xiaolin Zhang; Hanbing Li; Shilei Wang; Fei Meng; Shaojun Tan; Yinkang Zhou (Computers and Electronics in Agriculture, 2024)

Transport and health risk of legacy and emerging per-and polyfluoroalkyl substances in the water cycle in an urban area, China: Polyfluoroalkyl phosphate esters are of concern - Yueqing Zhang; Jing Meng; Yunqiao Zhou; Ninghui Song; Yaxin Zhao; Minghui Hong; Jia Yu; Li Cao; Yezhi Dou; Deyang Kong (Science of The Total Environment, 2024)

Inorganic ion accumulation model in wastewater recycling systems: Printing and dyeing case - Hanmou Dou; Xiali Jing; Wuang Ren; Rui Wang; Kai Ju; Yajiao Li; Xin Jin; Pengkang Jin (Journal of Water Process Engineering, 2024)

Chlorination-improved adsorption capacity of microplastics for antibiotics: A combined experimental and molecular mechanism investigation - Peng Hu; Yuanyuan Dou; Bohua Ji; Manhong Miao; Yao Li; Tianwei Hao (Journal of Hazardous Materials, 2024)

Study on the remediation of uranium-contaminated soils by compound leaching: Screening of leaching agents and a pilot-scale application - Juncheng Han; Jing Zou; Xindai Li; Aizhong Ding; Zhaorong Shang; Hongtu Sun; Ling Chen; Zhiyuan He; Qiao Li; Hongbo Fan; Junfeng Dou (Journal of Cleaner Production, 2024)

Antibacterial performance effects of Ag NPs in situ loaded in MOFs nano-supports prepared by post-synthesis exchange method - Yan Gao; Huawei Dou; Yang Ma; Guohong Tian; Delika M. Weragoda; Shijie Li; Xue Yang; Zhanchao Zhang; Guolan Fan; Baoming Chen (Journal of Environmental Chemical Engineering, 2024)

The kinetic characteristics of mullite crystallization in slag with high SiO2 and Al2O3 content at gasification condition of solid fuel - Kaifeng Li; Hao Lu; Zongshuai Yuan; Haoyu Dou; Jin Bai; Lingxue Kong; Huaizhu Li; Zhenxing Guo; Zongqing Bai; Wen Li (Fuel, 2024)

Comparison of cardiotoxicity induced by alectinib, apatinib, lenvatinib and anlotinib in zebrafish embryos - Jieping Liu; Wanbo Li; Sujie Sun; Ling Huang; Mengqi Wan; Xue Li; Li Zhang; Dou Yang; Fasheng Liu; Xinjun Liao; Huiqiang Lu; Juhua Xiao; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Fabrication of nanozyme-thixotropic anionic hydrogel coating with multi-enzyme-mimicking activity for the treatment of fungal keratitis - Depeng Shi; Xia Qi; Li Ma; Lihua Zhao; Shengqian Dou; Yao Wang; Qingjun Zhou; Yongfei Zhang; Chao Yang; Hongwei Wang; Lixin Xie (Chemical Engineering Journal, 2024)

Novel design of in-situ hydrogen sorption/storage integrated enhanced hydrogen production in supercritical CO2 gasification, air gasification, and steam gasification from biomass - Tiebing Yang; Binlin Dou; Hua Zhang; Kai Wu; Ning Luo; Haisheng Chen; Yujie Xu; Wei Li; Chunfei Wu (Chemical Engineering Journal, 2024)

Ligand structure optimization leads to efficient acid-resist Am(III)/Eu(III) separation in n-octanol - Yaoyang Liu; Mingjie Bao; Ludi Wang; Yu Kang; Yangcheng Dou; Jiaojiao Qin; Fan Guo; Huaixin Hao; Zhipeng Wang; Xiaoyan Tang; Jing Chen; Li Wang; et al. (Chemical Engineering Journal, 2024)

A novel method to quantify chitosan in aqueous solutions by ultrahigh-performance liquid chromatography–tandem mass spectrometry - Ting Xue; Lei Zhou; Fanjun Wang; Zhuang Tian; Nanxi Li; Tong Ye; Ruolin Hao; Lei Yang; Ruolan Gu; Hui Gan; Zhuona Wu; Xiaoxia Zhu; et al. (Carbohydrate Polymers, 2024)

Monitoring small-scale mass movement using unmanned aerial vehicle remote sensing techniques - Lu Yan; Pengfei Li; Jinfei Hu; Dou Li; Yang Dan; Xiao Bai; Lifeng Liu; Jianjian Gao; Tianmin Dang; Weiqin Dang (CATENA, 2024)

BPA induces hepatotoxicity in zebrafish through oxidative stress and apoptosis pathways - Ying Wang; Jie Wu; Dagang Wang; Mengqi Wan; Xue Li; Li Zhang; Dou Yang; Fasheng Liu; Jiejun Liu; Kehao Li; Shouhua Zhang; Huiqiang Lu (Fish Physiology and Biochemistry, 2024)

Visual surround suppression at the neural and perceptual levels - Yang Li; Weifeng Dai; Tian Wang; Yujie Wu; Fei Dou; Dajun Xing (Cognitive Neurodynamics, 2024)

Molecular cloning, subcellular localization, and expression of BsWRKY51 gene from Bletilla striata - Shuangshuang Wang; Yuxia Zheng; Quanli Dou; Zhengling Zhang; Boping Zeng; Ying Li; Yongchun Qian; Li Ma (Plant Biotechnology Reports, 2024)

Dietary astaxanthin supplementation improves the growth performance, immune response, and immunity-related gene expression of sea cucumber (Apostichopus japonicas) - Keqiang Qin; Shengfu Li; Shengjun Wu; Hongxuan Dou (Aquaculture International, 2024)

Dimethyl fumarate induces cardiac developmental toxicity in zebrafish via down-regulation of oxidative stress - Mengqi Wan; Jiejun Liu; Dou Yang; Zhonghao Xiao; Xue Li; Jieping Liu; Ling Huang; Fasheng Liu; Shouhua Zhang; Qiang Tao; Juhua Xiao; Zigang Cao (Toxicology, 2024)

Bibliometric insights into the evolution of uranium contamination reduction research topics: Focus on microbial reduction of uranium - Guangming Xu; Xindai Li; Xinyao Liu; Juncheng Han; Kexin Shao; Haotian Yang; Fuqiang Fan; Xiaodong Zhang; Junfeng Dou (Science of The Total Environment, 2024)

Effects of chronic low-level lead (Pb) exposure on cognitive function and hippocampal neuronal ferroptosis: An integrative approach using bioinformatics analysis, machine learning, and experimental validation - Yingsi Cao; Wenjing Zhao; Yanqi Zhong; Xiaofan Jiang; Huiya Mei; Yuanjin Chang; Dongqin Wu; JianRui Dou; Emely Vasquez; Xian Shi; Jiatao Yang; Zhongtang Jia; et al. (Science of The Total Environment, 2024)

Embryonic exposure to aluminum chloride blocks the onset of spermatogenesis through disturbing the dynamics of testicular tight junctions via upregulating Slc25a5 in offspring - Junhan Chen; Yunhui Xia; Yu Ben; Xinyan Lu; Kou Dou; Yibing Ding; Xiaodong Han; Fenglian Yang; Junli Wang; Dongmei Li (Science of The Total Environment, 2024)

Whole blood cadmium levels and depressive symptoms in Chinese young adults: A prospective cohort study combing metabolomics - Liu Yang; Qingxia Yu; Siqi Dou; Xinyuan Li; Shuo Wen; Jia Zhang; Mingyu Feng; Lailai Yan; Chengshuai Zhang; Shanshan Li; Peng Lu; Yuming Guo (Journal of Hazardous Materials, 2024)

Response of the C-fixing bacteria community to precipitation changes and its impact on bacterial necromass accumulation in semiarid grassland - Na Li; Baorong Wang; Yue Zhou; Huijun Li; Zhaolong Zhu; Yanxing Dou; Yimei Huang; Feng Jiao; Shaoshan An (Journal of Environmental Management, 2024)

Effects of Bacillus-based inoculum on odor emissions co-regulation, nutrient element transformations and microbial community tropological structures during chicken manure and sawdust composting - Huaxuan Zhao; Shangmin Li; Junhua Pu; Hongzhi Wang; Xinhong Dou (Journal of Environmental Management, 2024)

A novel nanoparticle-based fluorescent sandwich immunoassay for specific detection of Salmonella Typhimurium - Xuechen Dou; Zhiwei Zhang; Chao Li; Yaohua Du; Feng Tian (International Journal of Food Microbiology, 2024)

Co-pyrolysis of Hami coal and mixed plastic: An interaction between primary volatiles study via in-situ Py-TOF-MS - Tingting Zhang; Zongqing Bai; Hongyan Zheng; Haoyu Dou; Zhenxing Guo; Lingxue Kong; Jin Bai; Wen Li (Fuel, 2024)

Simulation and optimization of fracture pattern in temporary plugging fracturing of horizontal shale gas wells - Xin Chang; Xingyi Wang; Chunhe Yang; Yintong Guo; Kai Wei; Guang Hu; Chengbai Jiang; Qiang Li; Ruijie Dou (Fuel, 2024)

Te-vacancy-rich CoTe2− anodes for efficient potassium-ion storage - Gaoyu Wang; Jian Peng; Wei Zhang; Qinghua Li; Zhixin Liang; Jiawei Wu; Wenbo Fan; Jiazhao Wang; Shixue Dou; Shaoming Huang (Chemical Engineering Journal, 2024)

Angelica dahurica extract and its effective component bergapten alleviated hepatic fibrosis by activating FXR signaling pathway - Chong Gao; Zhong-He Hu; Zhen-Yu Cui; Yu-Chen Jiang; Jia-Yi Dou; Zhao-Xu Li; Li-Hua Lian; Ji-Xing Nan; Yan-Ling Wu (Journal of Natural Medicines, 2024)

Removal of NO with Fe(II)NTA solution catalyzed by the carbon treated with ethylenediamine - X.-w. Dou; P.-y. Chen; R.-c. Zhang; X.-li Long (International Journal of Environmental Science and Technology, 2024)

The deterministic neutron transport calculation for the HTR-PM by the three-dimensional method of characteristics code ARCHER - Kaijie Zhu; Qinrong Dou; Han Zhang; Boran Kong; Zhaoyuan Liu; Jiong Guo; Fu Li (Annals of Nuclear Energy, 2024)

Weakening Indian monsoon favors vegetation growth in humid but not in semi-arid ecosystems - Lijun Deng; Yang Fu; Xiaoxia Li; Zhuosong Geng; Jingtian Zhang; Junhe Chen; Dou Li; Jian Sun; J．Julio Camarero; Eryuan Liang (Agricultural and Forest Meteorology, 2024)

Organic carbon burial and their implication on sea surface primary productivity in the middle Okinawa Trough over the past 200 ka - Yunge Jing; Taoliang Zhang; Ben Zhu; Jingtao Zhao; Xiaoxiao Zhao; Yanguang Dou; Qing Li; Feng Cai; Bangqi Hu; Liang Dong (Frontiers in Marine Science, 2024)
The long-term burial of organic carbon in marginal seas plays a critical role in Earth’s carbon cycle and climate change. However, the mechanism of organic carbon (OC) burial in the Okinawa Trough (OT) during glacial-interglacial timescales remains unclear. In this study, we analyzed the foraminiferal carbon isotopes, total organic carbon (TOC), and δ 13 C-TOC over the past 200 ka in core Z1 collected in the central OT. We aimed to reveal the history of OC burial in the middle Okinawa Trough during the past 200 ka, and we combined our findings with relevant paleoenvironmental indices to reveal underlying mechanisms. We found reduced surface primary productivity during MIS 6, which may indicate changes in the pathways of the Kuroshio Current (KC). Furthermore, we observed decoupling between high TOC flux and low OC burial during glacial periods. We proposed that the dilution effect caused by the high sedimentation rate and poor OC preservation during the glacial period resulted in the low TOC content. Ventilation of the North Pacific Intermediate Water (NPIW) regulated the redox conditions of the intermediate water in the Okinawa Trough. Additionally, the intensified Kuroshio Current during interglacial phases led to water column stratification, creating reducing conditions in the bottom water and facilitating improved OC preservation. Subsequently, the enhanced water column oxygenation resulting from the oxygen carried by the intensified glacial NPIW weakened the burial of OC. This study sheds new light on our understanding of the carbon cycle in marginal seas on a glacial-interglacial timescale.

Comparison of leaf chlorophyll content retrieval performance of citrus using FOD and CWT methods with field-based full-spectrum hyperspectral reflectance data - Bin Xiao; Sunzhe Li; Shiqing Dou; Hongchang He; Bolin Fu; Tengxu Zhang; Weiwei Sun; Yanli Yang; Yuankang Xiong; Jinke Shi; Jie Zhang (Computers and Electronics in Agriculture, 2024)

m-Cresol,a pesticide intermediate, induces hepatotoxicity and behavioral abnormalities in zebrafish larvae through oxidative stress, apoptosis - Ying Wang; Jie Wu; Mengqi Wan; Dou Yang; Fasheng Liu; Kehao Li; Manxin Hu; Yuanyuan Tang; Huiqiang Lu; Shouhua Zhang; Yuanzhen Xiong (Toxicology in Vitro, 2024)

Proteomic analysis of boar sperm with differential ability of liquid preservation at 17 °C - Chenglei Song; Zhe Zhang; Yilin Wei; Yaqing Dou; Kunlong Qi; Xiuling Li; Feng Yang; Xinjian Li; Kejun Wang; Ruimin Qiao; Xuelei Han (Theriogenology, 2024)

Phosphorus species transformation and recovery in deep eutectic solvent-assisted hydrothermal carbonization of sewage sludge - Rui Dou; Fan Gao; Yi Tan; Huan-Ran Xiong; Zhi-Xiang Xu; Sameh M. Osman; Li-Jun Zheng; Rafael Luque (Sustainable Chemistry and Pharmacy, 2024)

Drought limits vegetation carbon sequestration by affecting photosynthetic capacity of semi-arid ecosystems on the Loess Plateau - Dou Li; Xiaoxia Li; Zongshan Li; Yang Fu; Jingtian Zhang; Yijin Zhao; Yafeng Wang; Eryuan Liang; Sergio Rossi (Science of The Total Environment, 2024)

Char and soot records of the Holocene fire history and its implications for climate-vegetation change and human activities within the Guanzhong Basin, southern Loess Plateau, China - Yuzhu Zhang; Qili Xiao; Yan Zhu; Ninglian Wang; Menglei Wu; Yanfeng Li; Jianxi Li; Dou Chen; Xiaoling Huang; Sikai Wang; Pengpeng Cao; Yao Jin; et al. (Science of The Total Environment, 2024)

High-performance pulse light stable perovskite indoor photovoltaics - Chen Li; Haoxuan Sun; Min Wang; Shan Gan; Da Dou; Liang Li (Science Bulletin, 2024)

Late Neoproterozoic tectonic evolution of the northern Tarim block: New insights from integrated detrital zircon and rutile geochronology and trace element geochemistry - Yifan Song; Zhiyuan He; Zhong Li; Johan De Grave; Linglin Zhong; Shida Song; Lirong Dou (Precambrian Research, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Two-photon fluorescence probe for palladium with perchlorate induced quenching mechanism and its application in smartphone-based rapid detection - Chunyang Chen; Yuemao Dou; Wei Liu; Zhongjie Li; Longtian Chen; Huili Wang; Xuedong Wang; Weisheng Liu (Journal of Hazardous Materials, 2024)

Antibiotic resistance genes and heavy metals in landfill: A review - Yan-Jiao Li; Ying Yuan; Wen-Bing Tan; Bei-Dou Xi; Hui Wang; Kun-Long Hui; Jia-Bao Chen; Yi-Fan Zhang; Lian-Feng Wang; Ren-Fei Li (Journal of Hazardous Materials, 2024)

Enhanced and accelerated degradation of PFOA using visible light—Applying semiconductor carbon nitride as an accelerator - Juying Li; Ying Liu; Yiqian Song; Li Cao; Yezhi Dou; Jia Yu; Yueqing Zhang; Jian He; Wei Dai; Cheng Yao; Deyang Kong (Journal of Environmental Chemical Engineering, 2024)

Analysis of influencing factors on dust separation efficiency of new virtual impact separator based on CFD technology - Wen Nie; Yuxin Dou; Huitian Peng; Changwei Xu; Fei Liu; Haoming Li (Fuel, 2024)

Geographical origin identification of camellia oil based on fatty acid profiles combined with one-class classification - Xinjing Dou; Xuefang Wang; Fei Ma; Li Yu; Jin Mao; Jun Jiang; Liangxiao Zhang; Peiwu Li (Food Chemistry, 2024)

Exposure to blue space surroundings and depressive symptoms in young Chinese adults: The mediating role of sleep - Jialian Li; Jing Hou; Li Zhang; Siqi Dou; Liu Yang; Victor Teng; Chengshuai Zhang; Hongwei Sun; Peng Lu; Yuming Guo (Environmental Research, 2024)

A magnetically induced self-assembly of Ru@Fe3O4/rGO cathode for diclofenac degradation in electro-Fenton process - Bing Qiu; Xiaolan Zhou; Weimin Li; Houjuan Zhu; Long Yu; Chao Yuan; Rongni Dou; Mingtai Sun; Suhua Wang (Environmental Research, 2024)

Deficient Tin oxide nanofibers with regulated valence for efficient nitrate reduction to ammonia - Kaihe Wang; Jiaqi Pan; Jiachong Hu; Xingyue Fu; Yao Dou; Haohong Xian; Haoran Guo; Jun Song Chen; Tingshuai Li (Chemical Engineering Journal, 2024)

Zinc sulfide quantum dots modified 3D Nitrogen-Doped framework carbon enhances the ion transport rate of potassium ion hybrid capacitors - Shuolei Deng; Yifan Dong; Changgang Li; Wenhao Feng; Yaowen Cao; Qianqian Dou; Ziting Ma; Fan Xia (Chemical Engineering Journal, 2024)

Confined bismuth single atoms and nanoparticles dual-sites constructed via reverse etching for CO2 photoreduction to CH4 - Dou Zhang; Ying-jie Sun; Kai-hua Zhang; Guang Yang; Xiao-jing Wang; Yi-lei Li; Hui-yun Han; Xinying Liu; Bao-Hang Han; Fa-tang Li (Chemical Engineering Journal, 2024)

Hydrochar-based facile and greenwood bio-adhesives production from distilled spent grain - Zhi-Xiang Xu; Huan-Ran Xiong; Rui Dou; Yi Tan; Yong-Xing Chen; Li-Jian Leng (Chemical Engineering Journal, 2024)

Tri-functional carbon nanocages coated CoNi electrocatalyst with micro twinning structure for high-performance electrochemical devices - Chao Han; Haitao Li; Anqiang Pan; Shixue Dou; Yong Liu; Jian Liu; Weijie Li (Chemical Engineering Journal, 2024)

Efficient photocatalytic reduction of nitrate byproducts during anammox process by novel extracellular polymeric substances-embedded NH2-MIL-101(Fe) photocatalysts - Li Zhang; Running Fan; Tingjun Dong; Quanhao Dou; Yongzhen Peng; Shou-Qing Ni; Jiachun Yang (Bioresource Technology, 2024)

OsMKK1 is a novel element that positively regulates the Xa21-mediated resistance response to Xanthomonas oryzae pv. oryzae in rice - ZeXi Yang; Zheng Zhu; Yalu Guo; Jinping Lan; Jianshuo Zhang; Shuo Chen; Shijuan Dou; Ming Yang; Liyun Li; Guozhen Liu (Plant Cell Reports, 2024)

Variations and driving factors of annual frequency of ground surface freeze–thaw in China - Ze Zhang; Xiang Long Li; Andrey Melnikov; Anatoli Brouchkov; Dou Dou Jin; Xiang Xi Meng (Climate Dynamics, 2024)

Adsorption–desorption of Atrazine with 9 Agricultural Soils in China - Juying Li; Li Cao; Jing Xu; Yezhi Dou; Jia Yu; Jian He; Linghao Xu; Cunliang Zhang; Jian Yu; Deyang Kong; Wenzhu Wu (Bulletin of Environmental Contamination and Toxicology, 2024)

High spatial variability in water use efficiency of terrestrial ecosystems throughout China is predominated by biological factors - Xiaojun Dou; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Lang Han; Zhaogang Liu; Lexin Ma; Yong Lin; Xianjin Zhu; Weikang Zhang; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

SLCO1B1 Polymorphisms are Associated with the Susceptibility to Pulmonary Tuberculosis in Chinese Females - Wei Li; Wei Liu; Xiong Wang; Rui Dou; Zunmin Zhu (Biochemical Genetics, 2024)

Polysulfide regulation by defect-modulated Ta3N5− electrocatalyst toward superior room-temperature sodium-sulfur batteries - Zhen Zhang; Dan Luo; Jun Chen; Chuyin Ma; Matthew Li; Haoze Zhang; Renfei Feng; Rui Gao; Haozhen Dou; Aiping Yu; Xin Wang; Zhongwei Chen (Science Bulletin, 2024)

Sublethal and transgenerational effects of lufenuron on the biological traits of Panonychus citri (McGregor) (Acari: Tetranychidae) - Meng-Hao Xia; Deng Pan; Chuan-Zhen Li; Yu-Chuang Li; Wei Dou; Jin-Jun Wang (Pesticide Biochemistry and Physiology, 2024)

Partial melting of multiple mantle domains underneath the Paleo-Tethyan cold subduction zone triggered by slab rollback - Xiguang Huang; Jun He; Jingxin Zhao; Jingzhao Dou; Weiyong Li; Aimin Hu; Ge Liu; Yiru Ji; Fukun Chen; Shuangqing Li (Lithos, 2024)

Degradation properties of fulvic acid and its microbially driven mechanism from a partial nitritation bioreactor through multi-spectral and bioinformatic analysis - Quanhao Dou; Li Zhang; Tingjun Dong; Zixuan Song; Xuepeng Fan; Yongzhen Peng; Xiayan Wang; Jiachun Yang (Journal of Environmental Sciences, 2024)

Effects of l-arginine/l-lysine modifications on the protein structure, binding interactions, and functional properties of soy protein hydrolysate - Bin Zhu; Jinjie Yang; Jiaye Yu; Jingjing Dou; Yijie Ning; Baokun Qi; Yang Li (Food Hydrocolloids, 2024)

Water-responsive entangled underwater adhesives enable strong adhesion in natural dynamic water - Sidi Li; Peng Sun; Wenguang Dou; Weijun Ji; Qingxi Wang; Xueping Li; Chan Liu; Jin Zhao; Hongliang Liu; Honglei Fan; Xin Hou; Xubo Yuan (Chemical Engineering Journal, 2024)

Improving the application of UAV-LiDAR for erosion monitoring through accounting for uncertainty in DEM of difference - Pengfei Li; Dou Li; Jinfei Hu; Fabian Ewald Fassnacht; Hooman Latifi; Wanqiang Yao; Jianjian Gao; Faith Ka Shun Chan; Tianmin Dang; Fuquan Tang (CATENA, 2024)

Occurrence and Distribution Characteristics of Microplastics in Surface Water of China: a Review - Yang Li; Minghui Shen; Liwen Qin; Xudong Chen; Tongtong Qin; Wenjing Wu; Yixuan Chang; Yanyan Dou; Yue Liu; Xuejun Duan (Water, Air, & Soil Pollution, 2024)

Matrine Mediated Immune Protection in MS by Regulating Gut Microbiota and Production of SCFAs - Mengmeng Dou; Yaojuan Chu; Xueliang Zhou; Mengru Wang; Xinyu Li; Rui Ma; Zhirui Fan; Xiaoyu Zhao; Wenbin Wang; Silu Li; Ying Lv; Lin Zhu (Molecular Neurobiology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Observation of Arctic surface currents using data from a surface drifting buoy - Hongxia Chen; Lina Lin; Long Fan; Wangxiao Yang; Yinke Dou; Bingrui Li; Yan He; Bin Kong; Guangyu Zuo; Na Liu (Acta Oceanologica Sinica, 2024)

Toxicologic effect and transcriptome analysis for sub-chronic exposure to carbendazim, prochloraz, and their combination on the liver of mice - Shuwen Zhang; Ting Luo; You Weng; Dou Wang; Li Sun; Zheping Yu; Yao Zhao; Senmiao Liang; Haiying Ren; Xiliang Zheng; Yuanxiang Jin; Xingjiang Qi (Environmental Science and Pollution Research, 2023)

Mechanisms underlying soil microbial regulation of available phosphorus in a temperate forest exposed to long-term nitrogen addition - Shiqi Wang; Minghua Song; Chunmei Wang; Xiaomin Dou; Xinqing Wang; Xingyue Li (Science of The Total Environment, 2023)

Refining detection methods for emerging SARS-CoV-2 mutants in wastewater: A case study on the Omicron variants - Xiaoqing Xu; Yu Deng; Jiahui Ding; Xianghui Shi; Xiawan Zheng; Dou Wang; Yu Yang; Lei Liu; Chunxiao Wang; Shuxian Li; Haogao Gu; Leo L.M. Poon; et al. (Science of The Total Environment, 2023)

Solution plasma synthesis of Pt-decorated Bi12O17Cl2 photocatalysts for efficient upcycling of plastics - Feiyan Wu; Changming Li; Yibo Dou; Jianchi Zhou; Tao Jiang; Yuechao Yao; Na Yeon Lee; Sung Yul Lim; Claus Hélix-Nielsen; Wenjing Zhang (Science of The Total Environment, 2023)

Establishment of oyster protein hydrolysate-chitosan oligosaccharide-zinc delivery system and its characterization, digestion & absorption in-vitro and in-vivo - Xuening Yu; Shijie Dou; Xiaoyang Liu; Fawen Yin; Deyang Li; Pengfei Jiang; Dayong Zhou (Food Bioscience, 2023)

Bisphenol A and its analogue bisphenol S exposure reduce estradiol synthesis via the ROS-mediated PERK/ATF4 signaling pathway - Zhou Li; Chen Chen; Pan Ying; Gu Ji-jun; Dou Lian-jie; Huang Dan; Zou Xuan-min; Guan Tian-yue; Zhang Chao; Hao Jia-hu (Food and Chemical Toxicology, 2023)

Self-standing electrospun Co/Zn@N-doped carbon nanofiber electrode for highly stable liquid and solid-state rechargeable zinc-air batteries and performance evaluated by scanning electrochemical microscopy at various temperatures - Haoran Pan; Chen Zhang; Zhenjie Lu; Jinxiao Dou; Xinning Huang; Jianglong Yu; Jiabin Wu; Huaiguang Li; Xingxing Chen (Chemical Engineering Journal, 2023)

Controllable reduction of absorbance and two-step reaction for 3D-printed SiC ceramics with micron-level periodic structure - Dou Yang; Hao Li; Wenqiang Yang; Minggang Zhang; Hui Mei; Shixiang Zhou; Jin Zhao; Tong Zhao; Yuekai Yan; Chengyu Liang; Lei Qiao; Laifei Cheng; et al. (Chemical Engineering Journal, 2023)

Mettl13 protects against cardiac contractile dysfunction by negatively regulating C-Cbl-mediated ubiquitination of SERCA2a in ischemic heart failure - Shuting Yu; ZhiYong Sun; Xiuzhu Wang; Tiantian Ju; Changhao Wang; Yingqi Liu; Zhezhe Qu; KuiWu Liu; Zhongting Mei; Na Li; Meixi Lu; Fan Wu; et al. (Science China Life Sciences, 2023)

Construction and application of a new watermelon germplasm with the phenotype of dwarf and branchless - Junling Dou; Qishuai Kang; Tengwei Li; Muhammad Jawad Umer; Badr Alharthi; Dongming Liu; Sen Yang; Huanhuan Niu; Changsheng Ma; Huayu Zhu; Luming Yang (Functional & Integrative Genomics, 2023)

Prevalence of Ureaplasma species among patients at a tertiary hospital in China: a 10-year retrospective study from 2013 to 2022 - Ziran Wang; Mingqi Xia; Yu Chen; Zhuo Yang; Jie Yi; Lingjun Kong; Han Zhang; Guoju Luo; Rui Li; Yaling Dou (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Analysis of Boundary Layer Structure, Turbulence, and Flux Variations before and after the Passage of a Sea Breeze Front Using Meteorological Tower Data - Ju Li; Junxia Dou; Donald H. Lenschow; Mingyu Zhou; Lihong Meng; Xiaobin Qiu; Yubing Pan; Jingjiang Zhang (Journal of Meteorological Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Biochar alleviates the crop failure of rice production induced by low-nitrogen cultivation mode by regulating the soil microbes taxa composition - Yan Jiao; Yutao Li; Wanyu Dou; Wenlong Zhang; Hui Liu (Archives of Microbiology, 2023)

Consequences of vacuum evaporation on physicochemical properties, storage stability and in vitro digestion of fermented goat milk - Jiage Ma; Tianzhu Li; Nianxu Dou; Yanan Li; Qingyun Wang; Mengguo Wu; Yusi Miao; Jinzhe Li; Chengcheng Su; Lijun Chen; Muhammad Altaf Hussain; Juncai Hou; et al. (Food Control, 2023)

Pterostilbene exerts cytotoxicity on activated hepatic stellate cells by inhibiting excessive proliferation through the crosstalk of Sirt1 and STAT3 pathways - Jiayi Dou; Haozhen Cui; Zhenyu Cui; Meiyan Xuan; Chong Gao; Zhaoxu Li; Lihua Lian; Jixing Nan; Yanling Wu (Food and Chemical Toxicology, 2023)

Temporal dynamics of soil dissolved organic carbon in temperate forest managed by prescribed burning in Northeast China - Xu Dou; Tongxin Hu; Kajar Köster; Aobo Sun; Guangxin Li; Yang Yue; Long Sun; Yiyang Ding (Environmental Research, 2023)

Clay minerals and elemental composition of sediments on different sedimentary units in the northern East China Sea shelf: provenance tracing and genetic mechanism analysis - Xiaoyan Xu; Yong Zhang; Yanguang Dou; Jingyi Cong; Beibei Mi; Xiaohui Chen; Xia Li; Chengfen Xu; Yongyu Ye (Acta Oceanologica Sinica, 2023)

Land-use conflict identification in urban fringe areas using the theory of leading functional space partition - Shuo Yang; Shibin Dou; Chenxi Li (The Social Science Journal, 2023)

Study on progressive failure behavior and mechanical properties of tunnel arch support structures - Wei Lu; Lingxiao Meng; Shucai Li; Yingdong Xu; Lei Wang; Peng Zhang; Songtao Dou; Huibin Sun (Tunnelling and Underground Space Technology, 2023)

Bifacial perovskite solar cells: a universal component that goes beyond albedo utilization - Shan Gan; Haoxuan Sun; Chen Li; Da Dou; Liang Li (Science Bulletin, 2023)

Blood multiple heavy metals exposure and lung function in young adults: A prospective Cohort study in China - Minghao Wang; Lailai Yan; Siqi Dou; Liu Yang; Yiwen Zhang; Wenzhong Huang; Shanshan Li; Peng Lu; Yuming Guo (Journal of Hazardous Materials, 2023)

Experimental investigation into damage and failure process of coal-rock composite structures with different roof lithologies under mining-induced stress loading - Yanjiang Chai; Linming Dou; Wu Cai; Piotr Małkowski; Xuwei Li; Siyuan Gong; Jinzheng Bai; Jinrong Cao (International Journal of Rock Mechanics and Mining Sciences, 2023)

High-throughput, highly sensitive and rapid SERS detection of Escherichia coli O157:H7 using aptamer-modified Au@macroporous silica magnetic photonic microsphere array - Xiu Wang; Wei Li; Shijie Dai; Menghua Dou; Saisai Jiao; Jing Yang; Weiwei Li; Ya Su; Qianjin Li; Jianlin Li (Food Chemistry, 2023)

Effects of hydrate distribution heterogeneity on the mechanical properties of hydrate-bearing sediments with consideration of the coalescence phenomenon: Insights from DEM simulations - Xiaofeng Dou; Qi Wu; Zhichao Liu; Yingjie Zhao; Yanlong Li; Deli Gao; Fulong Ning (Computers and Geotechnics, 2023)

Calcium carbonate regulates soil organic carbon accumulation by mediating microbial communities in northern China - Xiaolu Dou; Jiabao Zhang; Congzhi Zhang; Donghao Ma; Lin Chen; Guixiang Zhou; Jingwang Li; Yan Duan (CATENA, 2023)

Circuit VRC: A circuit theory-based ventilation corridor model for mitigating the urban heat islands - Yunhao Fang; Liyuan Zhao; Biying Dou; Yao Li; Shuxian Wang (Building and Environment, 2023)

Manual correction of genome annotation improved alternative splicing identification of Artemisia annua - Zhaoyu Liu; Yupeng Du; Zhihao Sun; Bohan Cheng; Zenghao Bi; Zhicheng Yao; Yuting Liang; Huiling Zhang; Run Yao; Shen Kang; Yuhua Shi; Huihua Wan; et al. (Planta, 2023)

Distribution and Controlling Factors of Dissolved Gaseous Mercury and Reactive Mercury in Seawater Near Yangtze River Estuary - Pingping Yin; Wen Zheng; Yan Wang; Ruhai Liu; Xin He; Haolin Sun; Dou Li (Journal of Ocean University of China, 2023)

The involvement of the T6SS vgrG gene in the pathogenicity of Pseudomonas plecoglossicida - Dou Yang; Lingmin Zhao; Qi Li; Lixing Huang; Yingxue Qin; Pan Wang; Chuanzhong Zhu; Qingpi Yan (Journal of Fish Diseases, 2023)
Pseudomonas plecoglossicida , the causative agent of white spot disease of large yellow croaker, has caused serious economic losses to the aquaculture industry. The type VI secretion system (T6SS) is a significant virulence system widely distributed among Gram‐negative bacteria. VgrG, a structural and core component of T6SS, is crucial to the function of T6SS. To explore the biological profiles mediated by vgrG gene and its effects on the pathogenicity of P. plecoglossicida , the vgrG gene deletion (Δ vgrG ) strain and complementary (C‐Δ vgrG ) strain were constructed and the differences in pathogenicity and virulence‐related characteristics between different strains were analysed. The results showed that vgrG gene deletion significantly affected the virulence‐related characteristics of P. plecoglossicida , including chemotaxis, adhesion, and biofilm formation. In addition, the LD 50 of Δ vgrG strain was nearly 50‐fold higher than that of the NZBD9 strain. Transcriptome data analysis suggested that the vgrG gene may affect the virulence of P. plecoglossicida by regulating the quorum sensing pathway to inhibit the secretion of virulence factors and affect biofilm formation. Besides, deletion of the vgrG gene may reduce bacterial pathogenicity by affecting bacterial signal transduction processes and the ability to adapt to chemotactic substances.

Detoxification enzyme is involved in the temperature effect on the toxicity of tetrachlorantraniliprole to Plutella xylostella - Jingjie An; Ya’nan Dou; Zhihong Dang; Jianglong Guo; Zhanlin Gao; Yaofa Li (Pesticide Biochemistry and Physiology, 2023)

Comparative genomics provides insights into the phylogeny and environmental adaptations of Peritrichia (Protista, Ciliophora) – A potential resource for environmental pollution control and bioremediation - Ying Zhang; Huan Dou; Yu Fu; Fasheng Liang; Zhe Wang; Alan Warren; Lifang Li (Molecular Phylogenetics and Evolution, 2023)

Close contact behaviors of university and school students in 10 indoor environments - Nan Zhang; Li Liu; Zhiyang Dou; Xiyue Liu; Xueze Yang; Doudou Miao; Yong Guo; Silan Gu; Yuguo Li; Hua Qian; Jianjian Wei (Journal of Hazardous Materials, 2023)

Effects and control mechanisms of ammonia, particulate matters and aerosol bacterial compositions in poultry houses by spray technology - Huaxuan Zhao; Shangmin Li; Junhua Pu; Hongzhi Wang; Xinhong Dou; Hongguang Liu; Juntao Liao; Lishun Du (Journal of Cleaner Production, 2023)

In-Situ construction of hierarchically porous CoNiP/MP Ni electrocatalyst for overall water splitting - Ziyi Xu; Sinan Li; Weizhao Lu; Xiaoyi Dou; Yong Wu; Julan Zeng; Yuhai Dou; Jian Zhang; Jinchao Wei; Linping Yu (Fuel, 2023)

Arsenic induced autophagy-dependent apoptosis in hippocampal neurons via AMPK/mTOR signaling pathway - Yao Chen; Xudan Liu; Qianhui Zhang; Huanhuan Wang; Ruo Zhang; Yanhong Ge; Huning Liang; Wanying Li; Juanjun Fan; Huimin Liu; Zhengyang Lv; Wenting Dou; et al. (Food and Chemical Toxicology, 2023)

Functionalized 2D defect g-C3N4 for artificial photosynthesis of H2O2 and synchronizing tetracycline fluorescence detection and degradation - Shirong Kang; Xiaojie Liu; Zixian Wang; Yue Wu; Mingyu Dou; Hua Yang; Hongjie Zhu; Dacheng Li; Jianmin Dou (Environmental Research, 2023)

Two strategies for rapid and sensitive detection of procalcitonin using carbon dots-encapsulated nanocapsule and magnetic carbon dots as coupled labels - Bo Liu; Siyu Lu; Kun Yang; Xuechen Dou; Xiangling Feng; Haoran Cui; Fan Li; Feng Tian (Chemical Engineering Journal, 2023)

Achieving multi-dimensional Li+ transport nanochannels via spatial-partitioning in crystalline ionic covalent organic frameworks for highly stable lithium metal anode - Wenbo Wang; Yantao Zhang; Haichao Jiang; Ruijuan Zhang; Ning Wang; Yaying Dou; Zhiyi Zhao; Xue Yang; Xiaoyun Fan; Xiaodi Li; Xiaomeng Guo; Qingliang Feng; et al. (Chemical Engineering Journal, 2023)

High-performance organic solar cell and self-power photodetector with chemically robust, near-infrared acceptor enabled by strengthening interfacial contact and compositional modulation - Chengwei Shan; Tao Liu; Jialing Zhou; Yang He; Dou Luo; Zhengyan Jiang; Zhaojin Wang; Qian Liu; Chang'an Li; Fucai Zhang; Erjun Zhou; Kai Wang; et al. (Chemical Engineering Journal, 2023)

N-methylpiperazine-diepoxyovatodiolide ameliorates peritoneal fibrosis via suppressing TGF-β/Smad and JAK/STAT signaling pathway - Min Mo; Yao Zeng; Yiqun Zeng; Shuting Li; Xiaoyang He; Xiaowen Chen; Qimei Luo; Mi Liu; Congwei Luo; Xianrui Dou; Fenfen Peng; Haibo Long (Chemico-Biological Interactions, 2023)

Treatment of fresh leachate by anaerobic membrane bioreactor: On-site investigation, long-term performance and response of microbial community - Weifu Yan; Yulin Wang; Yemei Li; Chao Rong; Dou Wang; Chunxiao Wang; Yubo Wang; Yee-lok Yuen; Fanny Fong Wong; Ho-Kwong Chui; Yu-You Li; Tong Zhang (Bioresource Technology, 2023)

Metabolomics of astaxanthin hyperaccumulation in Haematococcus pluvialis under high light stress - Yong Dou; Jiayi Li; Wenli Zhou (Journal of Oceanology and Limnology, 2023)

Tracing groundwater discharge into a coal mining subsidence lake in eastern China: Observations from water stable (δD and δ18O) and radon (222Rn) isotopes - Chunlu Jiang; Dou Liu; Chenghong Jiang; Qianqian Wang; Mahmood Sadat-Noori; Hailong Li (Applied Geochemistry, 2023)

Estimating the model parameters for remote sensing reflectance pixel by pixel: a neural network approach for optically deep waters - Jun Chen; Xianhui Dou; Xianqiang He; Min Xu; Xinyue Li; Delu Pan (International Journal of Remote Sensing, 2023)

Nanocatalyst-triggered cascade immunoassay: Multi-model immunochromatography assay for sensitive detection of Salmonella typhimurium - Xuechi Yin; Jingxin Hou; Jing Guo; Jiawei Li; Di Yang; Linpin Luo; Leina Dou; Yawei Liang; Yanru Wang; Jianlong Wang; Daohong Zhang (Chemical Engineering Journal, 2023)

Structural characterization of corn fiber hemicelluloses extracted by organic solvent and screening of degradation enzymes - Yingjie Guo; Zheng Zhang; Jinze Dou; Guodong Liu; Xuezhi Li; Jian Zhao (Carbohydrate Polymers, 2023)

Hmmr Acts as a Key Regulator in the ADSCs Proliferation and Mitosis - Xiao Zhang; Dou Huang; Kaide Li; Chaoying Han; Hui Li; Cai Li; Lei Liu (Stem Cell Reviews and Reports, 2023)

Association of short-term nitrogen dioxide exposure with hospitalization for urolithiasis in Xinxiang, China: a time series study - Yangdong Li; Yongbin Wang; Maochuan Fan; Weisheng Li; Xiangzhen Meng; Hao Zhou; Shaohua Zhang; Qifeng Dou (Environmental Science and Pollution Research, 2023)
Urolithiasis accounts for the highest incidence of all urologic-associated hospitalizations. However, few studies have explored the effect of nitrogen dioxide (NO 2 ) on hospitalizations for urolithiasis. We included 5956 patients with urolithiasis, collected daily meteorological and air pollution data between 2016 and 2021, and analyzed the associations between air pollutants and hospitalization, length of the hospital stay, and hospitalization costs attributable to urolithiasis. NO 2 exposure was associated with an increased risk of hospitalization for urinary tract stones. For each 10-μg/m 3 increase and 1-day lag of NO 2 , the maximum daily effect on the risk of hospitalization for urolithiasis was 1.020 (95% confidence interval [CI]: 1.001–1.039), and the cumulative effect peaked on lag day 4 (relative risk [ RR ]: 1.061; 95% CI: 1.003–1.122). Attribution scores and quantitative analysis revealed that the mean number of hospital days and mean hospital costs were 16 days and 21,164.39 RMB, respectively. Up to 5.75% of all urolithiasis hospitalizations were estimated to be attributable to NO 2 , and the cost of NO 2 -related urolithiasis hospitalizations reached approximately 3,430,000 RMB. Stratified analysis showed that NO 2 had a more sensitive impact on urolithiasis hospitalizations in women and in those aged ≥65 years. Notably, men and those younger than 65 years of age (exclude people aged 65) incurred more costs for urolithiasis hospitalizations. In the population level, the association between NO 2 and risk of urolithiasis hospitalization was more pronounced during the warm season. NO 2 can increase hospitalizations for urolithiasis for Xinxiang City residents, and there is a cumulative lag effect. Focusing on air pollution may have practical significance in terms of the prevention and control of urolithiasis.

Spatio-temporal evolution of coupling coordination between new infrastructure and regional sustainability in China - Ziwei Yi; Long Li; Yudan Dou (Environmental Science and Pollution Research, 2023)

Hypoxia formation triggered by the organic matter from subsurface chlorophyll maximum in a large estuary-shelf system - Dou Li; Jianping Gan; Zhongming Lu; Weicong Cheng; Hiusuet Kung; Junlu Li (Water Research, 2023)

Hepatic lipid metabolism disorders and immunotoxicity induced by cysteamine in early developmental stages of zebrafish - Chao Chen; Yuhua Zuo; Hongmei Hu; Xue Li; Li Zhang; Dou Yang; Fasheng Liu; Xinjun Liao; Guanghua Xiong; Zigang Cao; Zilin Zhong; Yanlong Bi; et al. (Toxicology, 2023)

Removal of Cl( I) from zinc sulfate electrolyte by the porous Bi2O3 rich in OVs: Efficiency and mechanism - Dong Li; Dongjie Lu; Jinyu Liu; Linghao Kong; Xingyun Hu; Lei Wan; Wenyue Dou (Journal of Water Process Engineering, 2023)

Phosphate adsorption on amorphous aluminum hydroxide-yielded transition aluminas: Insights on fundamental chemistry and making engineering adsorbents - Chunmei Wang; Wei Li; Xueqin Zhao; Zhen Chen; Yonghuan Li; Guichang Wang; Xiaomin Dou (Journal of Water Process Engineering, 2023)

The influences of the oil circulation ratio on the performance of a vapor injection scroll compressor in heat pump air conditioning system intended for electrical vehicles - Kang Li; Jingru Ma; Jian Cao; Bin Zhang; Binlin Dou; Ni Liu; Hua Zhang; Lin Su; Xuejin Zhou; Ran Tu (International Journal of Refrigeration, 2023)

Discrete element simulation of the hydrate-bearing sediments mechanical behaviors under typical hydrate dissociation patterns - Qi Wu; Xiaofeng Dou; Yingjie Zhao; Zhichao Liu; Yanlong Li; Norimasa Yoshimoto; Fulong Ning (Gas Science and Engineering, 2023)

Effect of phosphorus on viscosity-temperature behavior of high-sodium coal ash slag - Xianxian Zhang; Haoyu Dou; Jin Bai; Lingxue Kong; Wei Feng; Huaizhu Li; Zhenxing Guo; Zongqing Bai; Ping Li; Wen Li (Fuel, 2023)

Construction and characterization of Pickering emulsions stabilized by soy protein hydrolysate microgel particles and quercetin-loaded performance in vitro digestion - Jinjie Yang; Bin Zhu; Keyang Lu; Jingjing Dou; Yijie Ning; Huan Wang; Yang Li; Baokun Qi; Lianzhou Jiang (Food Research International, 2023)

Pexidartinib hydrochloride exposure induces developmental toxicity and immunotoxicity in zebrafish embryos via activation of Wnt signaling - Fasheng Liu; Hongmei Hu; Guilan Chen; Yanqi Lin; Wei Li; Ziyi Liu; Chao Chen; Xue Li; Sujie Sun; Li Zhang; Dou Yang; Kangyu Liu; et al. (Fish & Shellfish Immunology, 2023)

Response of soil enzymes to soil properties and seasonal characteristics of cyanobacteria-dominated crusts in a dryland ecosystem - Ke Zhang; Yi Li; Kai Wang; Dequan Liu; Shuo Dou; Yongle Chen; Mingzhu He; Chuang Ma (Journal of Soils and Sediments, 2023)

Optimization and analytical behavior of a morphine electrochemical sensor in environmental and biological samples based on graphite rod electrode using graphene/Co3O4 nanocomposite - Chan Wang; Jing Luo; Hao Dou; Amir Raise; Mohammed Sardar Ali; Wei Fan; Qian Li (Chemosphere, 2023)

Association between mercury exposure and lung function in young adults: A prospective cohort study in Shandong, China - Jiaming Miao; Shurong Feng; Siqi Dou; Yang Ma; Liu Yang; Lailai Yan; Pei Yu; Yao Wu; Tingting Ye; Bo Wen; Peng Lu; Shanshan Li; et al. (Science of The Total Environment, 2023)

Identification, expression profiles and involvement in insecticides tolerance and detoxification of carboxylesterase genes in Bactrocera dorsalis - Zhenyu Li; Mengling Chen; Wenjie Bai; Shuxia Zhang; Liwei Meng; Wei Dou; Jinjun Wang; Guorui Yuan (Pesticide Biochemistry and Physiology, 2023)

Insight into the protein oxidation impact on the surface properties of myofibrillar proteins from bighead carp - Yueyue Liu; Elliot Mubango; Peipei Dou; Yulong Bao; Yuqing Tan; Yongkang Luo; Xingmin Li; Hui Hong (Food Chemistry, 2023)

Characterization and comparison of structure, thermal and functional characteristics of various commercial pea proteins - Hong Sun; Jialu Sun; Nianxu Dou; Jinzhe Li; Muhammad Altaf Hussain; Jiage Ma; Juncai Hou (Food Bioscience, 2023)

Efficient synthesis of sugar alcohols using a composite trimetallic Pt–Ni–Sn/MWCNTs catalyst based on metal element coordination and valence regulation - Xiao-Jian Zhang; Bao-Juan Dou; Yu-Qi Wang; Fei Yang; Xue Cai; Mian Li; Zhi-Qiang Liu; Yu-Guo Zheng (Food Bioscience, 2023)

Fault-Seg-Net: A method for seismic fault segmentation based on multi-scale feature fusion with imbalanced classification - Xiao Li; Kewen Li; Zhifeng Xu; Zongchao Huang; Yimin Dou (Computers and Geotechnics, 2023)

Acid/Base-driven visualized molecular hinge for advanced information encryption - Yeye Ai; Yihang Zhu; Xin Lei; Yinghao Zhang; Qingguo Zeng; Yuncan Dou; Yuexuan Fei; Zhu Shu; Jiayun Xu; Hongliang Xu; Junqiu Liu; Yongguang Li (Chemical Engineering Journal, 2023)

Spatialization of Chinese R-410A emissions from the room air-conditioning sector - Pengcheng Wu; Li Zhang; Bo Yao; Bofeng Cai; Yifang Zhu; Hui Liu; Pengling Wang; Lisha Liu; Yanwei Dou; Han Yan; Yijun Liu; Zixuan Xie; et al. (Environment, Development and Sustainability, 2023)

Facile and scalable synthesis of baphicacanthin A by a two-pot procedure - Yalong Cuan; Wenhao Li; Yingchao Dou; Guanyu Yang (Natural Product Research, 2023)

The structure changes of microbial food web during the culture of grass carp larvae - Siqi Ma; Cui Feng; Mengqi Han; Chenchen Dong; Wenkai Chen; Jun Dou; Dapeng Li; Xiangjiang Liu (Aquaculture, 2023)

Revisiting resources allocation for slow-moving economies: A way forward for low-income economies - Yong Wang; Fang Li; Jiali Dou (Resources Policy, 2023)

Natural product 2-Phenylethanol inhibits ATP synthesis of P. infestans by blocking the oxidative phosphorylation pathway to prevent potato late blight - Jie Lu; Jie Li; Lei Li; Linlu Qi; Yuxi Wang; Shuai Yang; Guangyuan Xu; Daolong Dou; Jia Liu; Xiaodan Wang (Postharvest Biology and Technology, 2023)

Physical information-fused deep learning model ensembled with a subregion-specific sampling method for predicting flood dynamics - Changli Li; Zheng Han; Yange Li; Ming Li; Weidong Wang; Jie Dou; Linrong Xu; Guangqi Chen (Journal of Hydrology, 2023)

pH and ultrasound driven structure-function relationships of soy protein hydrolysate - Jinjie Yang; Bin Zhu; Jingjing Dou; Yijie Ning; Huan Wang; Yuyang Huang; Yang Li; Baokun Qi; Lianzhou Jiang (Innovative Food Science & Emerging Technologies, 2023)

Experimental and theoretical study of the adsorption of mixed low carbon alcohols and acids from Fischer Tropsch synthesis wastewater by activated carbon - Yingying Zhang; Baojuan Dou; Xiao Liu; Honglei Fan; Chunyu Geng; Xingchen Liu; Jie Chang; Qinglan Hao; Xin Hu; Yong Yang; Yongwang Li; Botao Teng (Fuel, 2023)

High electric field-induced ferroelectric loss of polymer/paraelectric barium titanate particle nanocomposites - Elshad Allahyarov; Qiong Li; Tianxiong Ju; Yeu-Wei Harn; Hang Luo; Dou Zhang; Zhiqun Lin; Lei Zhu (Chemical Engineering Journal, 2023)

One-Step Preparation of Novel Mn-Modified Biochar with Mn-Enriched Biomass for Efficient Adsorption of Methylene Blue - Dang Peipei; Li Chen; Dou Zhirui (Water, Air, & Soil Pollution, 2023)

Considering time-lag effects can improve the accuracy of NPP simulation using a light use efficiency model - Chuanhua Li; Yunfan Liu; Tongbin Zhu; Min Zhou; Tianbao Dou; Lihui Liu; Xiaodong Wu (Journal of Geographical Sciences, 2023)

Fluorescent labeling and tracing of immobilized efficient degrading bacterium DNB-S1 and its remediation efficiency of DBP contaminated soil - Lei Wang; Xiaochen Jia; Zeyu Dou; Xiaoqian Li; Wenjing Bao; Chaoran Ma; Hongye Wang; Lei Wang; Maofeng Dong; Ying Zhang (Chemosphere, 2023)

Mixture toxic effects of thiacloprid and cyproconazole on honey bees (Apis mellifera L.) - Lu Lv; Wenhong Li; Xinfang Li; Dou Wang; Hongbiao Weng; Yu-Cheng Zhu; Yanhua Wang (Science of The Total Environment, 2023)

Insights on the isolation, identification, and degradation characteristics of three bacterial strains against mandipropamid and their application potential for polluted soil remediation - Shiyin Mu; Li Dou; Yu Ye; Hao Zhang; Jing Shi; Kankan Zhang (Pesticide Biochemistry and Physiology, 2023)

Effect of temperature fluctuation during superchilling storage on the microstructure and quality of raw pork - Yu Tao; Yiping Guo; Jingwen Li; Keping Ye; Yuanyuan Zhang; Xianming Zeng; Han Dou (Meat Science, 2023)

An analytical model for solute transport in a large-strain aquitard affected by delayed drainage - Zhaofeng Li; Wen Zhang; Xi Zou; Xiaoli Wu; Walter A. Illman; Zhi Dou (Journal of Hydrology, 2023)

Influence of initial water saturation on three-phase displacement efficiency and residual distribution during NAPL invasion into unsaturated porous media based on low-field NMR - Zhi Dou; Jiajun Li; Yunbo Wei; Chao Zhuang; Yun Yang; Jinguo Wang (Journal of Hydrology, 2023)

Stabilizing Ni atoms on PtNi crystals by constructing PtNix-(CeO2)y heterostructures for improving durability of oxygen reduction reaction in acidic media - Haibin Wang; Fanchao Meng; Di Dou; Lixia Bao; Qiuping Zhao; Chuilei Li; Yi Wang; Yuanyuan Cong (Journal of Environmental Chemical Engineering, 2023)

Enhanced hydrolytic removal of tylosin in wastewater using polymer-based solid acid catalysts converted from polystyrene - Shiling Li; Shuhan Sun; Fei Qi; Xiaomin Dou (Journal of Environmental Sciences, 2023)

Synergistic effect of Hami coal and polystyrene on products properties during co-pyrolysis: Evaluation on the contribution of different interaction sources - Tingting Zhang; Zongqing Bai; Zhenxing Guo; Lingxue Kong; Haoyu Dou; Jin Bai; Wen Li (Fuel, 2023)

Establishment and evaluation of multiple adulteration detection of camellia oil by mixture design - Xinjing Dou; Liangxiao Zhang; Zhe Chen; Xuefang Wang; Fei Ma; Li Yu; Jin Mao; Peiwu Li (Food Chemistry, 2023)

Insights into the pigment and non-pigment phenolic profile of polyphenol extracts of jujube peel and their antioxidant and lipid-lowering activities - Jin-Feng Dou; Cai-E Wu; Gong-Jian Fan; Ting-Ting Li; Xiao-Jing Li; Dan-Dan Zhou; Jin-Peng Zhu; Chun-Mei Li (Food Bioscience, 2023)

Effects of chlorination on microplastics pollution: Physicochemical transformation and chromium adsorption - Manhong Miao; Bingqing Yu; Xuhua Cheng; Tianwei Hao; Yuanyuan Dou; Min Zhang; Yao Li (Environmental Pollution, 2023)

Free energy regulation and domain engineering of BaTiO3-NaNbO3 ceramics for superior dielectric energy storage performance - Wenrong Xiao; Zhen Liu; Chao Zhang; Zhanming Dou; Baoyan Fan; Meng Shen; Ying Yang; Wei Luo; Kanghua Li; Qiuyun Fu; Shenglin Jiang; Yaojin Wang; et al. (Chemical Engineering Journal, 2023)

Phosphorus Spatial Variation and Environmental Buffering Capacity of Mountainous River Bars - Chuanbin Dou; Jihong Xia; Wangwei Cai; Zhuo Zeng; Xiujun Liu; Jingjiang Li; Jiayi Zu; Zewen Liu; Yue Wang (Water, Air, & Soil Pollution, 2023)

Methcathinone Increases Visually-evoked Neuronal Activity and Enhances Sensory Processing Efficiency in Mice - Jun Zhou; Wen Deng; Chen Chen; Junya Kang; Xiaodan Yang; Zhaojuan Dou; Jiancheng Wu; Quancong Li; Man Jiang; Man Liang; Yunyun Han (Neuroscience Bulletin, 2023)

Two-phase flow pattern identification in horizontal gas–liquid swirling pipe flow by machine learning method - Wen Liu; Xiaofei Lv; Sheng Jiang; Huazheng Li; Hao Zhou; Xiangji Dou (Annals of Nuclear Energy, 2023)

“Nine syndromes” involving bilateral medial longitudinal fasciculus caused by cerebral hemorrhage - Fan Sun; Jia-jia Li; Yi Bu; Zhijie Dou; Yuan Qin (Acta Neurologica Belgica, 2023)

Effects of radon exposure on gut microbiota and its metabolites short-chain fatty acids in mice - Huimeng Liu; Meiyu Wang; Guangrui Chen; Huiyu Zhou; Jiahui Dong; Lei Yang; Tong Li; Zhiyun Meng; Ruolan Gu; Hui Gan; Zhuona Wu; Shuchen Liu; et al. (Toxicology, 2023)

Effects of pyrogenic carbon addition after fire on soil carbon mineralization in the Great Khingan Mountains peatlands (Northeast China) - Guangxin Li; Long Sun; Jianyu Wang; Xu Dou; Shengzhen Ji; Tongxin Hu; Chuanyu Gao (Science of The Total Environment, 2023)

Do tillage systems affect the cadmium threshold in farmland soil for environmental quality standard setting? - Zhaolin Du; Weiqiang Dou; Dasong Lin; Li Qin; Yi An; Hongan Chen; Lina Wu; Liyan Mou (Science of The Total Environment, 2023)

Development and characterization of yeast-incorporated coating films for improving the postharvest shelf-life of snap beans - Xinmao Li; Hossein Ghanizadeh; Zhengyuan Han; Tiantian Li; Yinghui Li; Zhitao Dou; Youwen Qiu; Xiuling Chen; Yao Zhang; Jiayin Liu; Aoxue Wang (Postharvest Biology and Technology, 2023)

Comparative transcriptome analysis of non-germinated and germinated spores of Enterocytozoon hepatopenaei (EHP) in vitro - Yabin Dou; Leiting Zhang; Hui Shen; Sheng Zhang; Xiaohui Cao; Yi Qiao; Ge Jiang; Jie Cheng; Xihe Wan; Xianping Fan; Hui Li; Libao Wang; et al. (Journal of Invertebrate Pathology, 2023)

Graphdiyne oxide elicits a minor foreign-body response and generates quantum dots due to fast degradation - Lizhen Wang; Yang Zhang; Linhao Li; Xuezheng Geng; Dandan Dou; Lu Yu; Haoyu Jing; Yubo Fan (Journal of Hazardous Materials, 2023)

A novel investigated method for decoupling adsorption and degradation effect on AFB1 based on isotope tracing and NMR analysis - Wan Zhang; Jun Wang; Jianpeng Dou; Tiantian Li; Hujun Liu; Xiaojiao Chang; Shengfeng Qian; Langao Lv; Wenfu Wu; Changpo Sun (Food Chemistry, 2023)

Insight into the self-assembly behavior of α-zein by multi-spectroscopic and molecular simulations: An example of combination with the main component of jujube peel pigments – Rutin - Jinpeng Zhu; Zhentian Li; Caie Wu; Gongjian Fan; Tingting Li; Dongbei Shen; Jinfeng Dou; Yi Liang (Food Chemistry, 2023)

Physicochemical stability and in vitro digestibility of goat milk affected by freeze-thaw cycles - Yue Ma; Jinzhe Li; Yuxuan Huang; Xin Liu; Nianxu Dou; Xuewei Zhang; Juncai Hou; Jiage Ma (Food Chemistry, 2023)

Uncovering the socioeconomic impacts of China's power system decarbonization - Pengfei Luo; Xu Tang; Xuming Dou; Shizhang Liu; Kaipeng Ren; Yuqing Jiang; Zheqi Yang; Yu Ding; Mengqiu Li (Environmental Impact Assessment Review, 2023)

Comparing the structural characteristics and expression of GA2ox gene in dwarf banana and its wild type - Jiaqi Lin; Dou Feng; Yanpei Li; Shixiang Xiao; Weiyan Xuan (Journal of Plant Biochemistry and Biotechnology, 2023)
It is necessary to understand the molecular mechanism of banana dwarfing mutation in order to improve the high stem character of banana varieties and breed the new excellent dwarf lines. To elucidate the molecular-level regulation of banana dwarf mutations and identify the relevant genes, the complete cDNA sequence of the gibberellin 2-oxidase gene ( GA2ox ) in the dwarf banana and its wild type was cloned by RT-PCR and the encoded amino acid sequences bioinformatically was analyzed. Meanwhile, the expression levels of banana GA2ox gene in different tissues of dwarfed banana and its wild type were analyzed by qRT-PCR. Between the GA2ox gene sequences of the dwarf banana and its wildtype, there were 5 base pairs of variation, leading to the predicted GA2ox proteins having different molecular weights, isoelectric points, fat indices, total numbers of positive and negative charges, and hydrophilicity. In addition, the expression of GA2ox in the leaves, stalks, and fruits of dwarf banana plants was higher than that in the wild type in the early and middle stages of banana development. The results showed that the GA2ox gene may have important regulatory effects on banana stem dwarfing, the knowledge of which can help our understanding and manipulation of this important plant.

Application of controlled-release urea to maintain rice yield and mitigate greenhouse gas emissions of rice–crayfish coculture field - Qiang Xu; Linxiu Dai; Ziyin Shang; Ying Zhou; Jingyong Li; Zhi Dou; Xiaochun Yuan; Hui Gao (Agriculture, Ecosystems & Environment, 2023)

Speciation and source changes of atmospheric arsenic in Qingdao from 2016 to 2020 - Response to control policies in China - Haolin Sun; Yan Wang; Ruhai Liu; Pingping Yin; Dou Li; Long Shao (Chemosphere, 2023)

Impacts of climatic zones on urban heat island: Spatiotemporal variations, trends, and drivers in China from 2001–2020 - Xiaolei Geng; Dou Zhang; Chengwei Li; Yuan Yuan; Zhaowu Yu; Xiangrong Wang (Sustainable Cities and Society, 2023)

Broad-specificity indirect competitive enzyme-linked immunosorbent assay for aristolochic acids: Computer-aided hapten design and molecular mechanism of antibody recognition - Xiaonan Wang; Qingpeng Lu; Leina Dou; Minggang Liu; Peipei Li; Wenbo Yu; Xuezhi Yu; Zhanhui Wang; Kai Wen (Science of The Total Environment, 2023)

Metagenomic insights into responses of microbial population and key functional genes to fulvic acid during partial nitritation - Li Zhang; Shuang Lan; Quanhao Dou; Shiwei Hao; Yueping Wang; Xiaoxuan Wang; Ruoyan Zhang; Yongzhen Peng; Jiachun Yang (Journal of Environmental Sciences, 2023)

Mechanism of thermally activated sodium persulfate–biochar skeleton treatment to improve the dewaterability of waste activated sludge - Shuaishuai Li; Yuling Liu; Chuanchuan Dou; Ruihao Sun (Journal of Environmental Chemical Engineering, 2023)

A review of potential antibacterial activities of nisin against Listeria monocytogenes: the combined use of nisin shows more advantages than single use - Mengjie Wu; Yue Ma; Xin Dou; Muhammad Zohaib Aslam; Yangtai Liu; Xuejuan Xia; Shuo Yang; Xiang Wang; Xiaojie Qin; Takashi Hirata; Qingli Dong; Zhuosi Li (Food Research International, 2023)

Air pollution exposure and ovarian reserve impairment in Shandong province, China: The effects of particulate matter size and exposure window - Lihong Pang; Wenhao Yu; Jiale Lv; Yunde Dou; Han Zhao; Shanshan Li; Yuming Guo; Gongbo Chen; Linlin Cui; Jingmei Hu; Yueran Zhao; Qi Zhao; et al. (Environmental Research, 2023)

Excavation of building energy conservation in university based on energy use behavior analysis - Qian Jiang; Qifen Li; Chunyan Zhang; Jun Wang; Zhenlan Dou; An Chen; Yongwen Yang; Hongbo Ren; Liting Zhang (Energy and Buildings, 2023)

3D DEM modeling on mechanical weakening of gas hydrate-bearing sandy sediments during hydrate dissociation - Xiaofeng Dou; Zhichao Liu; Fulong Ning; Yanlong Li; Xiaodong Li; Yingjie Zhao; Wei Hu; Deli Gao (Computers and Geotechnics, 2023)

Removal of gaseous Hg0 using biomass porous carbons modified by an environmental-friendly photochemical technique - Ying Li; Yan Wang; Zhifei Dou; Yangxian Liu (Chemical Engineering Journal, 2023)

3D-printed SiC lattices integrated with lightweight quartz fiber/silica aerogel sandwich structure for thermal protection system - Hui Mei; Hao Li; Zhipeng Jin; Liangjun Li; Dou Yang; Chengyu Liang; Laifei Cheng; Litong Zhang (Chemical Engineering Journal, 2023)

Trash to treasure: Green synthesis of novel Ag2O/Ag2CO3 Z-scheme heterojunctions with highly efficient photocatalytic activities derived from waste mussel shells - Jiazhen Cao; Peng Ju; Zheyang Chen; Kunpeng Dou; Jingxi Li; Peng Zhang; Zuhao Zhu; Chengjun Sun (Chemical Engineering Journal, 2023)

Early Permian bimodal magmatism and tectonic evolution of the easternmost Paleo-Asian orogenic system - Xiaopeng Yang; Shichao Li; Weifeng Luo; Kunpeng Jiang; Zheren Zhao; Hongtao Wang; Hongyu Wei; Sha Dou; Jinfeng Jia; Zuoting Ren (International Journal of Earth Sciences, 2023)

Notch1 signaling activation alleviates coronary microvascular dysfunction through histone modification of Nrg-1 via the interaction between NICD and GCN5 - Xiao-fei Qin; Ying-guang Shan; Min Dou; Feng-xiang Li; Yu-xi Guo (Apoptosis, 2023)

A prognostic cuproptosis-related lncRNA predictive signature for bladder cancer patients - Shaoqin Jiang; Jili Zhang; Qi Fan; Zhihao Li; Ruiling Dou; Zequn Lin; Zhenlin Chen; Yue Xu; Zhangcheng Huang; Jingyuan Lan; Wenwen Lin; Sijie Xu; et al. (Human Cell, 2023)

SDGSAT-1: the world’s first scientific satellite for sustainable development goals - Huadong Guo; Changyong Dou; Hongyu Chen; Jianbo Liu; Bihong Fu; Xiaoming Li; Ziming Zou; Dong Liang (Science Bulletin, 2023)

Coastal ecosystem service in response to past and future land use and land cover change dynamics in the Yangtze river estuary - Chengwei Li; Shubo Fang; Xiaolei Geng; Yuan Yuan; Xiaowei Zheng; Dou Zhang; Rongxi Li; Wei Sun; Xiangrong Wang (Journal of Cleaner Production, 2023)

flgC gene is involved in the virulence regulation of Pseudomonas plecoglossicida and affects the immune response of Epinephelus coioides - Dou Yang; Lingmin Zhao; Qi Li; Lixing Huang; Yingxue Qin; Pan Wang; Chuanzhong Zhu; Qingpi Yan (Fish & Shellfish Immunology, 2023)

Robustness evaluation of the probability-based HTCA model for simulating debris-flow run-out extent: Case study of the 2010 Hongchun event, China - Yangfan Ma; Zheng Han; Yange Li; Guangqi Chen; Weidong Wang; Ningsheng Chen; Guisheng Hu; Lianheng Zhao; Jie Dou (Engineering Geology, 2023)

Structure and defect strategy towards high-performance copper niobate as anode for Li-ion batteries - Mingru Su; Meiqing Li; Kuidong He; Tao Wan; Xueli Chen; Yu Zhou; Panpan Zhang; Aichun Dou; Haolan Xu; Chunsheng Lu; Renheng Wang; Dewei Chu; et al. (Chemical Engineering Journal, 2023)

All-inorganic CsPb1-xSnxI2Br perovskites mediated by dicyandiamide additive for efficient 4-terminal tandem solar cell - Qiaoyun Wen; Chenghao Duan; Feilin Zou; Dou Luo; Jiong Li; Zidan Liu; Jiarong Wang; Keyou Yan (Chemical Engineering Journal, 2023)

Sputter-deposited nickel nanoparticles on Kevlar fabrics with laser-induced graphene for efficient solar evaporation - Shuaihang Zhu; Zhiwei Lei; Yuejie Dou; Ching-Wen Lou; Jia-Horng Lin; Jiwei Li (Chemical Engineering Journal, 2023)

Zincophilic polymer semiconductor as multifunctional protective layer enables Dendrite-Free zinc metal anodes - Jiangmin Jiang; Zhenghui Pan; Jiaren Yuan; Jun Shan; Chenglong Chen; Shaopeng Li; HaiXu; Yaxin Chen; Quanchao Zhuang; Zhicheng Ju; Hui Dou; Xiaogang Zhang; et al. (Chemical Engineering Journal, 2023)

Injectable thermo-sensitive hydrogel containing ADSC-derived exosomes for the treatment of cavernous nerve injury - Shuai Liu; Ruiyu Li; Keke Dou; Kefan Li; Qihui Zhou; Qiang Fu (Carbohydrate Polymers, 2023)

Sensitivity analysis of seismic attributes and oil reservoir predictions based on jointing wells and seismic data – A case study in the Taoerhe Sag, China - Na Li; Jinliang Zhang; Jun Matsushima; Cheng Song; Xuwei Luan; Ming Dou; Tao Chen; Lingling Wang (Frontiers in Marine Science, 2022)
It is important to identify the location of gravelly sandstone in Taoerhe Sag, an oil target area in the Chezhen Depression. To date, most attention has focused on sedimentary characteristics; hence, information regarding a clear sensitivity analysis of seismic attributes is incomplete. To address this, we used well analysis and seismic attribute interpretation to find sensitive seismic attributes and sand bodies. Based on the well analysis and core data, a geologicald model of mudstone and sandstone was established, and the electrical characteristics of three kinds of lithology were identified. We used correlation analysis to select the optimal logging parameters and seismic attributes to identify sandstone. We used multi-attribute fusion technology and stratigraphic slices to characterize the spatial distribution characteristics of gravelly sandstone in the target area and used genetic algorithm inversion volume to evaluate the prediction results. The results indicate that the three main lithologies of the lower submember of Shahejie Formation 3 (P 2 S 3 X ) in the Taoerhe Sag can be distinguished by natural gamma (GR), acoustic time difference (AC) and saturated hydrocarbon content (SH) logging curves. The seismic attribute characteristics of gravelly sandstone of P 2 S 3 X are high root mean square amplitude (RMS) values, high instantaneous bandwidth (BW) values, low 3D curvature (Curv) values, medium-high instantaneous phase (Phase) values and high instantaneous frequency (Freq) values. In this study, we found two nearshore underwater fans in P 2 S 3 X . Gravelly sandstone is located along the slope zone and the lake bottom, with a total sedimentary area of 57.9 km 2 . The method summarized in this paper can be applied to other similar deep-water basins.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Soil Nutrients Drive Microbial Changes to Alter Surface Soil Aggregate Stability in Typical Grasslands - Cheng Ren; Kesi Liu; Pengpeng Dou; Xinqing Shao; Dingyuan Zhang; Kaili Wang; Xiqiang Liu; Jiahuan Li; Kun Wang (Journal of Soil Science and Plant Nutrition, 2022)

Summary of research progress on separation and extraction of valuable metals from Bayer red mud - Kun Wang; Zhihe Dou; Yan Liu; Xiaofei Li; Guozhi Lv; Ting-an Zhang (Environmental Science and Pollution Research, 2022)

Occurrence, Spatial Distribution and Health Risk of Hexabromocyclododecane (HBCD) in Source Water in the Lower Yangtze River, China - Yueqing Zhang; Yvette Baninla; Jia Yu; Juying Li; Yezhi Dou; Deyang Kong (Bulletin of Environmental Contamination and Toxicology, 2022)

Ferroptosis induced by the biocontrol agent Pythium oligandrum enhances soybean resistance to Phytophthora sojae - Yang Cheng; Huanxin Zhang; Wenyi Zhu; Qing Li; Rui Meng; Kun Yang; Ziqian Guo; Ying Zhai; Haijing Zhang; Rui Ji; Hao Peng; Daolong Dou; et al. (Environmental Microbiology, 2022)
Ferroptosis is a newly discovered form of cell death accompanied by iron accumulation and lipid peroxidation. Both biotic and abiotic stresses can induce ferroptosis in plant cells. In the case of plant interactions with pathogenic Phytophthora oomycetes, the roles of ferroptosis are still largely unknown. Here, we performed transcriptome analysis on soybean plants treated with the biocontrol agent Pythium oligandrum , a soilborne and non‐pathogenic oomycete capable of inducing plant resistance against Phytophthora sojae infection. Expression of homologous soybean genes involved in ferroptosis and resistance was reprogrammed upon P. oligandrum treatment. Typical hallmarks for characterizing ferroptosis were detected in soybean hypocotyl cells, including decreased glutathione (GSH) level, accumulation of ferric ions, and lipid peroxidation by reactive oxygen species (ROS). Meanwhile, ferroptosis‐like cell death was triggered by P. oligandrum to suppress P. sojae infection in soybean. Protection provided by P. oligandrum could be attenuated by the ferroptosis inhibitor ferrostatin‐1 (Fer‐1), suggesting the critical role of ferroptosis in soybean resistance against P. sojae . Taken together, these results demonstrate that ferroptosis is a P. oligandrum ‐inducible defence mechanism against oomycete infection in soybean.

Overall Scheduling Model for Vessels Scheduling and Berth Allocation for Ports with Restricted Channels That Considers Carbon Emissions - Xing Jiang; Ming Zhong; Jiahui Shi; Weifeng Li; Yi Sui; Yuzhi Dou (Journal of Marine Science and Engineering, 2022)
As maritime transportation develops, the pressure of port traffic increases. To improve the management of ports and the efficiency of their operations, vessel scheduling must be optimized. The vessel scheduling problem can be divided into channel scheduling and berth allocation. We considered the complex problem of vessel scheduling in a restricted channel and the berth allocation problem, and a combined model that considers carbon emissions was developed. This model should reduce vessel waiting times, improve the quality of the berth loading and unloading service, meet the requirements of “green” shipping, and improve the overall scheduling efficiency and safety of ports. An adaptive, double-population, multi-objective genetic algorithm NSGA-II-DP is proposed to calculate the mathematical model. In the case study, the rationality verification and sensitivity analysis of the model and algorithm are conducted, and the NSGA-II-DP and NSGA-II were compared. Results demonstrate that the overall convergence of the NSGA-II-DP algorithm is better than that of NSGA-II, demonstrating that the NSGA-II-DP algorithm is a useful development of NSGA-II. In terms of port scheduling, the results of our model and algorithm, compared with the decisions provided by the traditional First Come First Service (FCFS) strategy, are more in line with the requirements for efficiency and cost in the actual port management, and more dominant in the port management can provide better decision support for the decision-makers.

Pamiparib Induces Neurodevelopmental Defects and Cerebral Haemorrhage in Zebrafish Embryos via Inhibiting Notch Signalling - Dou Yang; Fasheng Liu; Mengqi Wan; Jieping Liu; Ling Huang; Chao Chen; Xue Li; Li Zhang; Xiaobing Ding; Xinjun Liao; Guanghua Xiong; Huiqiang Lu; et al. (Molecular Neurobiology, 2022)

Nitrogen fertilization weakens the linkage between soil carbon and microbial diversity: A global meta‐analysis - Yang Yang; Xinli Chen; Liangxu Liu; Ting Li; Yanxing Dou; Jiangbo Qiao; Yunqiang Wang; Shaoshan An; Scott X. Chang (Global Change Biology, 2022)
Soil microbes make up a significant portion of the genetic diversity and play a critical role in belowground carbon (C) cycling in terrestrial ecosystems. Soil microbial diversity and organic C are often tightly coupled in C cycling processes; however, this coupling can be weakened or broken by rapid global change. A global meta‐analysis was performed with 1148 paired comparisons extracted from 229 articles published between January 1998 and December 2021 to determine how nitrogen (N) fertilization affects the relationship between soil C content and microbial diversity in terrestrial ecosystems. We found that N fertilization decreased soil bacterial (−11%) and fungal diversity (−17%), but increased soil organic C (SOC) (+19%), microbial biomass C (MBC) (+17%), and dissolved organic C (DOC) (+25%) across different ecosystems. Organic N (urea) fertilization had a greater effect on SOC, MBC, DOC, and bacterial and fungal diversity than inorganic N fertilization. Most importantly, soil microbial diversity decreased with increasing SOC, MBC, and DOC, and the absolute values of the correlation coefficients decreased with increasing N fertilization rate and duration, suggesting that N fertilization weakened the linkage between soil C and microbial diversity. The weakened linkage might negatively impact essential ecosystem services under high rates of N fertilization; this understanding is important for mitigating the negative impact of global N enrichment on soil C cycling.

RNA-Seq Reveals the Effect of Ethylene on the Volatile Organic Components (VOCs) of Cavendish Banana at Different Post-harvesting Stages - Tongxin Dou; Chunhua Hu; Shujing Zhao; Huijun Gao; Weidi He; Guiming Deng; Ou Sheng; Fangcheng Bi; Qiaosong Yang; Chunyu Li; Ganjun Yi; Tao Dong (Journal of Plant Growth Regulation, 2022)
Aroma serves as one of the decisive factors influencing the value of banana commodities. Most of characteristic volatile organic components (VOCs) are formed during post-harvesting. However, the changing of VOCs of banana at different post-harvesting stages remain ambiguous. In this study, the VOCs of Cavendish banana for the four typical post-harvesting stages (green stage/half of yellow stage/yellow ripening stage/over ripening stage) are clarified using headspace solid phase micro-extraction (HS-SPME), combined with gas chromatography-mass spectrometry (GC–MS). The results inferred that the relative content of branched-chain esters such as acetate and butyrate, which form the main contributors of aroma in bananas, is higher in the T2 and T3 stages. Further, RNA-Seq technology was employed to clarify the formation mechanism of banana aroma in the post-harvesting stage. The MaTGL4 gene of the linoleic acid metabolism pathway and the MaBCAT3 and MaBCAT5 genes of the valine, leucine and isoleucine degradation pathway in banana suggest the expression is active late in the ripening stage, and the upregulated expression of these genes is analogous to the formation of aroma components such as branched-chain esters and hexenal. The above results not only provide baseline data on the differences in physical and chemical properties of VOCs in various post-harvesting stages of banana production, but also provide theoretical guidance facilitating the subsequent improvement of the commercial value of bananas through genetic improvement.

Expression patterns and correlation analyses of muscle-specific genes in the process of sheep myoblast differentiation - Hejie Wang; Minmin Dou; Jun Li; Peng Cao; Junling Li; Tianyan Guo; Dipeng Zhao; Ajab Khan; Yingliang Li; Baojun Li; Jian Qin; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2022)

Soil-resistant organic carbon improves soil erosion resistance under agroforestry in the Yellow River Flood Plain, of China - Jiachen Pan; Chao Liu; Hongli Li; Qicong Wu; Zhi Dong; Xiaohui Dou (Agroforestry Systems, 2022)

Monitoring periodically national land use changes and analyzing their spatiotemporal patterns in China during 2015–2020 - Wenhui Kuang; Shuwen Zhang; Guoming Du; Changzhen Yan; Shixin Wu; Rendong Li; Dengsheng Lu; Tao Pan; Jing Ning; Changqing Guo; Jinwei Dong; Yuhai Bao; et al. (Journal of Geographical Sciences, 2022)

Starch accumulation dynamics and transcriptome analysis of Chlorella sorokiniana during transition of sulfur nutritional status - Haiqing Xu; Jinzhi Yang; Xu Wang; Qing Peng; Yanxia Han; Xudong Liu; Kexin Liu; Shijuan Dou; Liyun Li; Guozhen Liu; Ming Yang (Frontiers in Marine Science, 2022)
Microalgae can effectively accumulate starch by using nutritional limitation methods in the context of bioalcohol fuel production. However, relatively few studies have focused on starch accumulation in microalgae and its molecular basis, especially under sulfur limitation conditions. In this study, the starch accumulation dynamics and physiological responses of Chlorella sorokiniana under sulfur starvation (SS) and sulfur replenishment (SR) conditions were investigated, and the genes involved in the transcriptional regulation were explored using RNA-seq. The starch content in C. sorokiniana cells significantly increased from 1.6% to 55.0% of dry weight within 24 h under SS conditions, and then, it decreased to 3.4% within 12 h after transition to SR conditions. However, cell growth was inhibited, and pigment content decreased under SS conditions. Using RNA-seq analysis, a total of 9720 differentially expressed genes (DEGs) induced by sulfur status were obtained. These genes were narrowed down to 454 starvation and replenishment cross-validated (SRV)-DEGs, among which 283 SRV-DEGs were significantly up-regulated and 171 SRV-DEGs were down-regulated under SS conditions, and returned to their previous state under SR conditions. The SRV-DEGs enriched in the sulfate metabolism pathway were all up-regulated under SS conditions after 6 h to speed up the sulfur metabolic cycle, and the transcriptional abundance of a sulfate transporter (SULTR4), cysteine synthase[O-acetylserine(thiol)-lyase] (OASTL), serine acetyltransferase (SAT), and methanethiol oxidase (SELENBP1) increased 8.6-fold, 12.6-fold, 8.7-fold, and 12.4-fold, respectively. Protein synthesis was correspondingly inhibited, which resulted in the reallocation of carbon and elevated the starch synthesis pathway, in which the expressions of glycogen branching enzyme (GBE) and starch synthase (SS) were up-regulated 12.0- and 3.0-fold, respectively. The fatty acid desaturase (FAD) and phosphatidic acid phosphatase (PAP) in the lipid synthesis pathway were strongly up-regulated 8.8- and 16.2-fold, respectively, indicating the competitive synthesis of lipids. The down-regulation of SRV-DEGs associated with carbon fixation, such as those in the Calvin cycle, possibly affected cell growth. The time-resolved transcriptional analysis identified the SRV-DEGs, revealing the underlying starch accumulation mechanism, as well as the relationship with cell growth and lipid synthesis.

Two distinct leaf anthracnose disease infections in hybrid Liriodendron trees in northern China - Guiming Dou; Xing Lü; Fei Ren; Ruhua Li; Dong-Hui Yan (European Journal of Plant Pathology, 2022)

Nematicidal activity of volatile organic compounds produced by Bacillus altitudinis AMCC 1040 against Meloidogyne incognita - Lin Ye; Jian-Yu Wang; Xiao-Fang Liu; Qi Guan; Nong-Xiao Dou; Jian Li; Qian Zhang; Yan-Ming Gao; Min Wang; Jian-She Li; Bo Zhou (Archives of Microbiology, 2022)

Production of indole and hydrogen sulfide by the oxygen-tolerant mutant strain Clostridium sp. Aeroto-AUH-JLC108 contributes to form a hypoxic microenvironment - Yu-Xia Liu; Shi-Juan Dou; Meng Li; Xiu-Ling Wang (Archives of Microbiology, 2022)

Review of the State-of-Art of MPS Method in Ocean Engineering - Zhe Sun; Li-Yuan Dou; Si-Yuan Tan; Zi-Kai Xu; Kamal Djidjeli; Yan Zhou (Journal of Marine Science and Engineering, 2022)
When dealing with the complex deformation of free surface such as wave breaking, traditional mesh-based Computational Fluid Dynamics (CFD) methods often face problems arising alongside grid distortion and re-meshing. Therefore, the meshless method became robust for treating large displaced free surface and other boundaries caused by moving structures. The particle method, which is an important branch of meshless method, is mainly divided into the Smoothed Particle Hydrodynamics (SPH) and Moving Particle Semi-implicit (MPS) methods. Different from the SPH method, which involves continuity and treat density as a variable when building kernel functions, the kernel function in the MPS method is a weight function which treats density as a constant, and the spatial derivatives are discretized by establishing the gradient operator and Laplace operator separately. In other words, the first- or second-order continuity of the kernel functions in the MPS method is not a necessity as in SPH, though it might be desirable. At present, the MPS method has been successfully applied to various violent-free surface flow problems in ocean engineering and diverse applications have been comprehensively demonstrated in a number of review papers. This work will focus on algorithm developments of the MPS method and to provide all perspectives in terms of numerical algorithms along with their pros and cons.

Characteristics of sea ice kinematics from the marginal ice zone to the packed ice zone observed by buoys deployed during the 9th Chinese Arctic Expedition - Xiaomin Chang; Longchun Ye; Guangyu Zuo; Jingyue Li; Keyu Wei; Yinke Dou (Acta Oceanologica Sinica, 2022)

Spatial correlation among cultivated land intensive use and carbon emission efficiency: A case study in the Yellow River Basin, China - Xiao Zhou; Juan Yu; Jiangfeng Li; Shicheng Li; Dou Zhang; Di Wu; Sipei Pan; Wanxu Chen (Environmental Science and Pollution Research, 2022)

Spatiotemporal evolution of chlorophyll-a concentration from MODIS data inversion in the middle and lower reaches of the Hanjiang River, China - Zhuo Chen; Ming Dou; Rui Xia; Guiqiu Li; Lisha Shen (Environmental Science and Pollution Research, 2022)

Impact mechanism and performance enhancement of ultrasound on ZVI-anammox system - Li Zhang; Shuang Lan; Quanhao Dou; Shiwei Hao; Yueping Wang; Yongzhen Peng (Environmental Science and Pollution Research, 2022)

The rapid induction of OsPR1A protein is crucial in Xa21-mediated rice bacterial blight resistance - Gaowei Yan; Yuqing Liu; Jinping Lan; Tong Zhang; Tianxingzi Wang; Liyun Li; Guozhen Liu; Shijuan Dou (Journal of Plant Pathology, 2022)

A semi-analytical water content model for pressure transient analysis of fractured horizontal well with complex fracture networks - Gang Bi; Mengmeng Li; Zhan Qu; Kai Zhao; Liangbin Dou (Arabian Journal of Geosciences, 2022)

Genetic variation of pharmacogenomic VIP variants in the Chinese Li population: an updated research - Shuangyu Yang; Xia Dou; Zhen Wang; Wenjie Zhang; Kefan Ding; Wenting Meng; Haiyue Li; Jianfeng Liu; Yuanwei Liu; Tianbo Jin (Molecular Genetics and Genomics, 2022)

Short-term impact of ambient temperature on the incidence of influenza in Wuhan, China - Yanbing Li; Jingtao Wu; Jiayuan Hao; Qiujun Dou; Hao Xiang; Suyang Liu (Environmental Science and Pollution Research, 2022)

Effect of Hepatocyte Targeting Nanopreparation Syringopicroside on Duck Hepatitis B Virus and Evaluation of Its Safety - X. W. Zhang; M. C. Li; J. J. Dou (Bulletin of Experimental Biology and Medicine, 2022)

3D Geological Suitability Evaluation for Urban Underground Space Development Based on Combined Weighting and Improved TOPSIS - Fanfan Dou; Huaixue Xing; Xiaohui Li; Feng Yuan; Zhitang Lu; Xiangling Li; Weiya Ge (Natural Resources Research, 2022)

Effect of Carbonation and Drying-Wetting Cycles on Chloride Diffusion Behavior of Coral Aggregate Seawater Concrete - Bo Da; Yipeng Li; Hongfa Yu; Haiyan Ma; Haoyu Chen; Xuemei Dou; Zhangyu Wu (Journal of Ocean University of China, 2022)

Antimicrobial Natural Products Produced by Soil-Derived Fungus Penicillium cremeogriseum W1-1 - Xu-Yan Sang; Zhao-Jie Wang; Ya-Bin Yang; Yong-Liang Wang; Mei-Ling Xiang; Dou-Ying Zhu; Ying Zhou; Xiao-Dong Luo; Li-Xing Zhao (Indian Journal of Microbiology, 2021)

Memory regulation in feeding habit transformation to dead prey fish of Chinese perch (Siniperca chuatsi) - Linjie Shi; Jiao Li; Xu-Fang Liang; Shan He; Yaqi Dou; Jian Peng; Wenjing Cai; Hui Liang (Fish Physiology and Biochemistry, 2021)

Method for Analyzing Copula-Based Water Shortage Risk in Multisource Water Supply Cities - Chen An; Ming Dou; Jianling Zhang; Guiqiu Li (Water Resources Management, 2021)

Comparative study of flash flood in ungauged watershed with special emphasizing on rough set theory for handling the missing hydrological values - Muhammad Waseem Boota; Chaode Yan; Tanveer Abbas; Ziwei Li; Ming Dou; Ayesha Yousaf (Natural Hazards, 2021)

Eutrophication model driven by light and nutrients condition change in sluice-controlled river reaches - Ming Dou; Li Liang; Yuping Han; Ruipeng Jia; Yan Zhang (Environmental Science and Pollution Research, 2021)

Transcriptome sequencing reveals terpene biosynthesis pathway genes accounting for volatile terpene of tree peony - Rongchen Li; Ziyao Li; Pingsheng Leng; Zenghui Hu; Jing Wu; Dequan Dou (Planta, 2021)

Three-Dimensional Seismic Response in Complex Site Conditions: A New Approach Based on an Auxiliary-Model Method - Xiaolong Zhang; Xiaobo Peng; Xiaojun Li; Zhenghua Zhou; Chong Xu; Zhan Dou; Bideng Liu (Journal of Earth Science, 2021)

Research on ultrasonic-based investigation of mechanical properties of ice - Xiaomin Chang; Wenhao Liu; Guangyu Zuo; Yinke Dou; Yan Li (Acta Oceanologica Sinica, 2021)

Effect of Immersion Duration on Shear Behavior of Granite Fractures - Zihao Dou; Tianyang Gao; Zhihong Zhao; Jinjin Li; Qiang Yang; Shuang Yi (Rock Mechanics and Rock Engineering, 2021)

Human Methylmercury Exposure and Potential Impacts in Central Tibet: Food and Traditional Tibetan Medicine - Menghan Cheng; Maodian Liu; Dou Li; Qing Luo; Zhihao Zhang; Liuliang Yuan; Chenghao Yu; Han Xie; Huiming Lin; Qianru Zhang; De Ji; Xuejun Wang (Bulletin of Environmental Contamination and Toxicology, 2021)

Low-latitude control on sea surface temperatures in the middle Okinawa Trough over the last 3.6 kyr - Fangjian Xu; Yanguang Dou; Jingtao Zhao; Jun Li; Xiting Liu; Kehui Xu; Feng Cai; Zhenhe Wen; Xiaohui Chen (Geo-Marine Letters, 2021)

Upregulated SOCC and IP3R calcium channels and subsequent elevated cytoplasmic calcium signaling promote nonalcoholic fatty liver disease by inhibiting autophagy - Lin Zhang; Yifan Zhang; Yuanqing Jiang; Xiaobing Dou; Songtao Li; Hui Chai; Qianyu Qian; Miaojuan Wang (Molecular and Cellular Biochemistry, 2021)

The mechanism and application of high-pressure water jet technology to prevent compound dynamic disaster - Zeng-qiang Yang; Chang Liu; Feng-shuo Li; Lin-ming Dou; Gang-wei Li; Da-wei Wang (Arabian Journal of Geosciences, 2021)

In-Situ Seawater Gamma Spectrometry with LaBr3 Detector at a Nuclear Power Plant Outlet - Daowei Dou; Zhi Zeng; Wen Yu; Ming Zeng; Wu Men; Feng Lin; Hao Ma; Jianping Cheng; Junli Li (Journal of Marine Science and Engineering, 2021)
In a nuclear emergency, the application of in situ spectrometers for monitoring environmental radioactivity is significantly important, as information on the type and activity of radionuclides released from the accident can be obtained quickly. However, in emergency environmental radiological monitoring, a balance between energy resolution and detecting efficiency must be considered in selecting an appropriate detector. In this study, in situ gamma spectrometry was conducted with the LaBr3 detector to determine the radioactivity of seawater at the discharging outlet of a coastal nuclear power plant in southeast China. The results show that the LaBr3 scintillator has excellent energy resolution and detection efficiency, making it a promising detector for emergency monitoring.

A Conserved miR394-Targeted F-Box Gene Positively Regulates Drought Resistance in Foxtail Millet - Zhao Geng; Jianguang Liu; Dan Li; Guiyuan Zhao; Xu Liu; Haikuan Dou; Linxuan Lv; Hanshuang Zhang; Yongqiang Wang (Journal of Plant Biology, 2021)

Impact of genetic variants in IL-2RA and IL-2RB on breast cancer risk in Chinese Han women - Lingge He; Wenjie Zhang; Shuangyu Yang; Wenting Meng; Xia Dou; Jianfeng Liu; Yuanwei Liu; Haiyue Li; Tianbo Jin (Biochemical Genetics, 2021)

Impacts of metallic nanoparticles and transformed products on soil health - Wenjie Sun; Fugen Dou; Cong Li; Xingmao Ma; Lena Q. Ma (Critical Reviews in Environmental Science and Technology, 2021)

The resurgent landscape of xenotransplantation of pig organs in nonhuman primates - Xuan Zhang; Quancheng Wang; Jingjun Zhao; Xiao Li; Wei Peng; Zhaoxu Yang; Zhibin Lin; Long Yang; Rui Ding; Kaishan Tao; Kefeng Dou (Science China Life Sciences, 2021)

A Xanthene Dye‐based Sensor for Viscosity and Cell Imaging - Bo Yu; Ying Zhou; Lihua Dou; Yunyun Li; Zhengwen Huang (Journal of Fluorescence, 2021)

Effects of hydrological change on the risk of riverine algal blooms: case study in the mid-downstream of the Han River in China - Lisha Shen; Ming Dou; Rui Xia; Guiqiu Li; Baiheng Yang (Environmental Science and Pollution Research, 2021)

A Preliminary Investigation of Arctic Sea Ice Negative Freeboard from in-situ Observations and Radar Altimetry - Shutong Li; Tingfeng Dou; Cunde Xiao (Journal of Ocean University of China, 2021)

Assessing the Influence of Aerosol on Radiation and Its Roles in Planetary Boundary Layer Development - Zhigang Cheng; Yubing Pan; Ju Li; Xingcan Jia; Xinyu Zhang; Pengkun Ma; Qianqian Wang; Junxia Dou; Jingjiang Zhang; Jiannong Quan (Journal of Meteorological Research, 2021)

DBSCAN-based point cloud extraction for Tomographic synthetic aperture radar (TomoSAR) three-dimensional (3D) building reconstruction - Ziye Guo; Hui Liu; Lei Pang; Li Fang; Wenna Dou (International Journal of Remote Sensing, 2021)

Short-term effects of ambient temperature on preterm birth: a time-series analysis in Xuzhou, China - Peng Cheng; Lei Peng; Jingwen Hao; Sha Li; Chao Zhang; Lianjie Dou; Weinan Fu; Fan Yang; Jiahu Hao (Environmental Science and Pollution Research, 2021)

Study on the Triaxial Unloading Creep Mechanical Properties and Damage Constitutive Model of Red Sandstone Containing a Single Ice-Filled Flaw - Ren-liang Shan; Yao Bai; Yang Ju; Tian-yu Han; Hao-yu Dou; Zhao-long Li (Rock Mechanics and Rock Engineering, 2021)

Modeling the role of riverine organic matter in hypoxia formation within the coastal transition zone off the Pearl River Estuary - Liuqian Yu; Jianping Gan; Minhan Dai; Chiwing Rex Hui; Zhongming Lu; Dou Li (Limnology and Oceanography, 2021)
Globally expanding hypoxia in estuaries and coastal oceans has largely been attributed to the elevated river nutrient inputs, whereas the role of river‐delivered terrestrial organic matter (OM terr ) in hypoxia formation has been less investigated. This study uses a coupled physical‐biogeochemical model and observations to investigate how OM terr directly (via remineralization) and indirectly (via the nutrients released from OM terr remineralization) promotes hypoxia development in the coastal transition zone off the Pearl River Estuary. Results show that direct contribution of OM terr remineralization to total oxygen consumption by terrestrial and marine organic matter negatively correlates with salinity, decreasing from over 60% in the upper estuary to nearly 0% in the far reaches of the river plume, and is higher in the upstream (average 30%) than the downstream region (average 18%). Nevertheless, the nutrients released from OM terr remineralization greatly sustain an indirect contribution to oxygen depletion and hypoxia formation downstream. The increasing relative importance of indirect over the direct effect of OM terr to hypoxia along the plume path is a combined result of the wind‐driven eastward shelf current and the OM terr ‐released nutrients being advected farther downstream than the sinking OM terr . This highlights that without including the indirect effect of OM terr may underestimate the role of OM terr in hypoxia formation in aquatic systems. Examinations of the hypoxia response to varying riverine loads further suggest that reducing the nutrient and OM terr loads is required for hypoxia mitigation in the upstream region while reducing the nutrient load alone is more effective in mitigating hypoxia in the downstream.

Potential Effect of Bioturbation by Burrowing Crabs on Sediment Parameters in Coastal Salt Marshes - Tian Xie; Peng Dou; Shanze Li; Baoshan Cui; Junhong Bai; Qing Wang; Zhonghua Ning (Wetlands, 2020)

A Network Perspective to Evaluate Hydrological Connectivity Effects on Macroinvertebrate Assemblages - Peng Dou; Tian Xie; Shanze Li; Junhong Bai; Baoshan Cui (Wetlands, 2020)

Genomewide analysis of the CIII peroxidase family in sweet orange (Citrus sinensis) and expression profiles induced by Xanthomonas citri subsp. citri and hormones - Qiang Li; Wanfu Dou; Jingjing Qi; Xiujuan Qin; Shanchun Chen; Yongrui He (Journal of Genetics, 2020)

Biological characteristic and biocontrol mechanism of Trichoderma harzianum T-A66 against bitter gourd wilt caused by Fusarium oxysporum - Fuli Zhang; Chang Liu; Yunhua Wang; Kai Dou; Faju Chen; Li Pang; Xiangxiang Kong; Changrui Shang; Yan Li (Journal of Plant Pathology, 2020)

Constant-head and variable-head injection tests for determining the hydraulic parameters of an aquitard - Yawen Xin; Zhifang Zhou; Zhi Dou; Mingwei Li; Jun Ma (Hydrogeology Journal, 2020)

Toxicological interactions of cadmium and four pesticides on early life stage of rare minnow (Gobiocypris rarus) - Yanhua Wang; Xinfang Li; Chao Xu; Guiling Yang; Dou Wang; Xinquan Wang; Qiang Wang (Ecotoxicology, 2020)

Genetic Structure of Amphioctopus ovulum (Mollusca: Cephalopoda: Octopodidae) as Revealed by Mitochondrial and Nuclear DNA - Faiz Muhammad; Canfeng Dou; Liqin Liu; Gong Li; Punhal Lashari; Zhen-ming Lü (Thalassas: An International Journal of Marine Sciences, 2020)

Patterns of presence-absence variants in Upland cotton - Junfang Liu; Xianliang Zhang; Lingling Dou; Wei Li; Xiaojian Zhou; Yangai Liu; Xiaoyu Pei; Zhongying Ren; Wensheng Zhang; Huaizhu Li; Wenbo Wang; Changsong Zou; et al. (Science China Life Sciences, 2020)

Dexmedetomidine Alleviates CCI-Induced Neuropathic Pain via Inhibiting HMGB1-Mediated Astrocyte Activation and the TLR4/NF-κB Signaling Pathway in Rats - Erxian Zhao; Liying Bai; Shurong Li; Li Li; Zhongci Dou; Yunli Huang; Yan Li; Yunqi Lv (Neurotoxicity Research, 2020)

Abundance and removal characteristics of microplastics at a wastewater treatment plant in Zhengzhou - PengJu Ren; Ming Dou; Cai Wang; GuiQiu Li; Ruipeng Jia (Environmental Science and Pollution Research, 2020)

Mapping the susceptibility to landslides based on the deep belief network: a case study in Sichuan Province, China - Weidong Wang; Zhuolei He; Zheng Han; Yange Li; Jie Dou; Jianling Huang (Natural Hazards, 2020)

Retraction Note to: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-qian Guo; Yu Chen; Bai-bing Mi; Shao-nong Dang; Dou-dou Zhao; Rong Liu; Hong-li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2020)

Detection of stress redistribution in a complex isolated coal pillar with active SVT technology - Xuwei Li; Siyuan Gong; Linming Dou; Yanjiang Chai (Arabian Journal of Geosciences, 2020)

Correction to: Organic Matter Pollution During the Spring Thaw in Hulun Lake Basin: Contribution of Multiform Human Activities - Wenlin Wang; Wenjing Li; Yan Yan; Bo Liu; Tanjing Wang; Sichen Mao; Ninghui Song; Huashan Dou; Wen Ao; Changxin Zou (Bulletin of Environmental Contamination and Toxicology, 2020)

Organic Matter Pollution During the Spring Thaw in Hulun Lake Basin: Contribution of Multiform Human Activities - Wenlin Wang; Wenjing Li; Yan Yan; Bo Liu; Tanjing Wang; Sichen Mao; Linhui Song; Huashan Dou; Wen Ao; Changxin Zou (Bulletin of Environmental Contamination and Toxicology, 2020)

Examining Health of Wetlands with Multiple Ecosystem Services as Targets in China’s Coastal Regions - Yangming Zhou; Yuehan Dou; Xiubo Yu; Li Zhang; Chong Huang; Yuyu Wang; Xiaowei Li; He Li; Yifei Jia; Martha Bakker; Gerrit Jan Carsjens; Yan Zhou; et al. (Chinese Geographical Science, 2020)

Experimental investigation for dynamic instability of coal-rock masses in horizontal section mining of steeply inclined coal seams - Zheng-yi Wang; Lin-ming Dou; Jiang He; An-ye Cao; Xiong-wei Li; Peng-bo Li; Chang-sheng Wu (Arabian Journal of Geosciences, 2020)

Temperature-dependent variations in toxicity of diamide insecticides against three lepidopteran insects - Yaofa Li; Ya’nan Dou; Jingjie An; Xuewei Tu; Haiying Lv; Wenliang Pan; Zhihong Dang; Zhanlin Gao (Ecotoxicology, 2020)

Impact of Elevated Nitrate and Perchlorate in Irrigation Water on the Uptake, Speciation, and Accumulation of Arsenic in Rice (Oryza sativa L.) - Xingmao Ma; Kevin Y. Sun; Fugen Dou; Xiufen Li; Xiaoxuan Wang; Wenjie Sun (Water, Air, & Soil Pollution, 2020)

Molecular cloning and functional analysis of the BplSPL1 gene from Betula platyphylla Suk. - Jing Tian; Xiaoqing Hu; Yong Zhang; Qiqi Xin; Dou Li; Lihong Zhao; Xuemei Liu (Trees, 2020)

Shear Strength of Rock Fractures Under Dry, Surface Wet and Saturated Conditions - Bo Li; Xinna Ye; Zihao Dou; Zhihong Zhao; Yingchun Li; Qiang Yang (Rock Mechanics and Rock Engineering, 2020)

Genetic characterization of bovine ephemeral fever virus in southern China, 2013–2017 - Jia Kun; Jia Rongrong; Wang Xiangbin; Zhao Yan; Dou Yiping; Lu Gang; Zhou Pei; Li Shoujun (Virus Genes, 2020)

The relationship between vascular endothelial growth factor and spermatogenesis disturbance in an experimentally-induced unilateral cryptorchidism murine model - Pan Gao; Jingjing Gao; Xianming Dou; Dangwei Peng; Yao Zhang; Hu Li; Tianle Zhu; Hui Jiang; Xiansheng Zhang (Molecular Biology Reports, 2020)

Expression pattern analysis of key genes related to anther development in a mutant of male-sterile Betula platyphylla Suk. - Qiqi Xin; Xiaoqing Hu; Yong Zhang; Dou Li; Bohan Xu; Xuemei Liu (Tree Genetics & Genomes, 2020)

Characterization of a G9 group A rotavirus reassortant strain detected in Jinzhou, China, in 2018–2019 - Ying Lu; Hui Li; Weiwei Li; Xiaofang Wang; Xiaoli Tao; Lili Dou; Ying Dong; Nan Wu; Yong Gang Li (Archives of Virology, 2020)

Preliminary analyses of a catastrophic landslide occurred on July 23, 2019, in Guizhou Province, China - Hai-bo Li; Yue-ren Xu; Jia-wen Zhou; Xie-kang Wang; Hiromitsu Yamagishi; Jie Dou (Landslides, 2020)

Identification, molecular characterization, and expression analysis of the SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) gene family in Betula platyphylla Suk. - Xiaoqing Hu; Chuang Liu; Jing Tian; Yong Zhang; Qiqi Xin; Aihua Chen; Dou Li; Xuemei Liu (Trees, 2020)

Cloning and functional characterization of a novel BpSEP4 gene from Betula platyphylla Suk. - Xiaoqing Hu; Jing Tian; Qiqi Xin; Dou Li; Lianmei Yao; Yong Zhang; Xuemei Liu (Tree Genetics & Genomes, 2020)

The strengthened relationship between the Yangtze River Valley summer rainfall and the Southern Hemisphere annular mode in recent decades - Juan Dou; Zhiwei Wu; Jianping Li (Climate Dynamics, 2020)

The Role of Biochar in Reducing the Bioavailability and Migration of Persistent Organic Pollutants in Soil–Plant Systems: A Review - Ni Ni; Deyang Kong; Wenzhu Wu; Jian He; Zhengjun Shan; Juying Li; Yezhi Dou; Yueqing Zhang; Yang Song; Xin Jiang (Bulletin of Environmental Contamination and Toxicology, 2020)

Population diversity of Cistopus indicus inferred from mitochondrial DNA (Cytochrome b) variation from China and Vietnam - Canfeng Dou; Faiz Muhammad; Liqin Liu; Li Gong; Yongjiu Chen; Baoying Guo; Zhenming Lü (Molluscan Research, 2020)

The application of the ‘Gene-deletor’ technology in banana - Chun-hua Hu; Qiao-song Yang; Xiu-hong Shao; Tao Dong; Fang-cheng Bi; Chun-yu Li; Gui-ming Deng; Yi Li; Gan-jun Yi; Tong-xin Dou (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Banana ( Musa spp.) is an important tropical crop. Banana industry is under biotic and abiotic stresses such as Fusarium wilt, typhoon, cold stress. Genetic engineering offers a powerful strategy to create germplasm of banana with enhanced resistance. The safety of genetically modified organisms has become a bottleneck restricting the popularization and application of genetically modified technology. In this study, a candidate promoter, LEAFY (LFY) for expression and flower initiation in Arabidopsis , was cloned and constructed to ‘Gene-deletor’ vector. Histochemical β-glucuronidase (GUS) staining results showed that the ‘Gene-deletor’ vector driven by LFY promoter could lead to 88.5% excision efficiency from Arabidopsis seeds based on more than 200 T 3 progeny examined per event. GUS staining was found to be partially negative in transgenic bananas, however, polymerase chain reaction could still detect the presence of large fragments of the vector. These results suggest that although LFY promoter could not completely drive the ‘Gene-deletor’ vector to achieve the effect of complete elimination of exogenous gene in bananas, its efficiency of eliminating exogenous gene laid a theoretical foundation for cloning banana fruit-specific promoters, that is, ‘non-transgenic’ GM bananas.

Effects of different 2A peptides on transgene expression mediated by tricistronic vectors in transfected CHO cells - Yan-mei Li; Meng Wang; Tian-yun Wang; Yong-ge Wei; Xiao Guo; Chun-liu Mi; Chun-peng Zhao; Xiang-xiang Cao; Yuan-yuan Dou (Molecular Biology Reports, 2020)

Nitrogen fertilizer enhances zinc and cadmium uptake by hyperaccumulator Sedum alfredii Hance - Ziwen Lin; Chunying Dou; Yongfu Li; Hailong Wang; Nabeel Khan Niazi; Shaobo Zhang; Dan Liu; Keli Zhao; Weijun Fu; Yongchun Li; Zhengqian Ye (Journal of Soils and Sediments, 2020)

An optimization model of sewage discharge in an urban wetland based on the multi-objective wolf pack algorithm - Ming Dou; Ruipeng Jia; Guiqiu Li (Environmental Monitoring and Assessment, 2019)

Development and characterization of 29 SNP markers for the Tibetan macaque (Macaca thibetana) - Xinshang Zhang; Lihong Niu; Liang Zhou; Zhifeng Yan; Fan Yang; Aiming Wu; Shaokun Min; Xiao Li; Kaishan Tao; Kefeng Dou; Hui Chen (Conservation Genetics Resources, 2019)

Genetic mapping and development of molecular markers for a candidate gene locus controlling rind color in watermelon - Bingbing Li; Shengjie Zhao; Junling Dou; Aslam Ali; Haileslassie Gebremeskel; Lei Gao; Nan He; Xuqiang Lu; Wenge Liu (Theoretical and Applied Genetics, 2019)

Food access inequalities in Chinese urban neighborhoods: a case study of the Dalian development zone - Jiaojiao Li; Guobao Song; Henry Musoke Semakula; Yijie Dou; Shushen Zhang (Food Security, 2019)

Transcriptomic analysis of Chinese wild Vitis pseudoreticulata in response to Plasmopara viticola - Ruiqi Liu; Kai Weng; Mengru Dou; Tingting Chen; Xiao Yin; Zhiqian Li; Tiemei Li; Chen Zhang; Gaoqing Xiang; Guotian Liu; Yan Xu (Protoplasma, 2019)

SSeCKS/Gravin/AKAP12 Inhibits PKCζ-Mediated Reduction of ERK5 Transactivation to Prevent Endotoxin-Induced Vascular dysfunction - Zilin Li; Jing Hu; Jian Guo; Li Fan; Shaowei Wang; Ning Dou; Jian Zuo; Shiqiang Yu (Cardiovascular Toxicology, 2019)

Growth inhibition and oxidative stress in two species of marine diatoms exposed to 1-phenylethanol - Xiang Dou; Fanping Meng; Weiyan Duan; Qunqun Liu; Hao Li; Shuhao Du; Xiaoling Peng (Journal of Oceanology and Limnology, 2019)

Expression dynamics of key ecdysteroid and juvenile hormone biosynthesis genes imply a coordinated regulation pattern in the molting process of a spider mite, Tetranychus urticae - Gang Li; Qin-Zhe Sun; Xun-Yan Liu; Jun Zhang; Wei Dou; Jin-Zhi Niu; Jin-Jun Wang (Experimental and Applied Acarology, 2019)

Shikimic Acid Promotes Oligodendrocyte Precursor Cell Differentiation and Accelerates Remyelination in Mice - Fengfeng Lu; Dou Yin; Yingyan Pu; Weili Liu; Zhenghao Li; Qi Shao; Cheng He; Li Cao (Neuroscience Bulletin, 2019)

Establishment of a rescue system for porcine parvovirus using a seamless cloning method - Lingling Zhang; Dou Gao; Yongle Yu; Yebing Liu; Weiquan Liu; Jinxiang Li; Shangjin Cui (Archives of Virology, 2019)

Genome-wide identification, characterization, and expression analysis of the expansin gene family in Chinese jujube (Ziziphus jujuba Mill.) - Lu Hou; Zhiyong Zhang; Suhan Dou; Yadong Zhang; Xiaoming Pang; Yingyue Li (Planta, 2019)

Overexpressed TTC3 Protein Tends to be Cleaved into Fragments and Form Aggregates in the Nucleus - Yueqing Gong; Kun Wang; Sheng-Ping Xiao; Panying Mi; Wanjie Li; Yu Shang; Fei Dou (NeuroMolecular Medicine, 2019)

RETRACTED ARTICLE: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-Qian Guo; Yu Chen; Bai-Bing Mi; Shao-Nong Dang; Dou-Dou Zhao; Rong Liu; Hong-Li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2019)

Estimation of above-ground biomass of reed (Phragmites communis) based on in situ hyperspectral data in Beijing Hanshiqiao Wetland, China - Wei Li; Zhiguo Dou; Yan Wang; Gaojie Wu; Manyin Zhang; Yinru Lei; Yunmei Ping; Jiachen Wang; Lijuan Cui; Wu Ma (Wetlands Ecology and Management, 2019)

Relationship Between Fine-Particle Pollution and the Urban Heat Island in Beijing, China: Observational Evidence - Zuofang Zheng; Guoyu Ren; Hong Wang; Junxia Dou; Zhiqiu Gao; Chunfeng Duan; Yubin Li; Jean Paul Ngarukiyimana; Chun Zhao; Chang Cao; Mei Jiang; Yuanjian Yang (Boundary-Layer Meteorology, 2018)

A fine-granularity scheduling algorithm for parallel XDraw viewshed analysis - Wanfeng Dou; Yanan Li; Yanli Wang (Earth Science Informatics, 2018)

Regulation of myostatin expression is associated with growth and muscle development in commercial broiler and DMC muscle - Tengfei Dou; Zhengtian Li; Kun Wang; Lixian Liu; Hua Rong; Zhiqiang Xu; Ying Huang; Dahai Gu; Xiaobo Chen; Wenyuan Hu; Jiarong Zhang; Sumei Zhao; et al. (Molecular Biology Reports, 2018)

Middle Holocene Organic Carbon and Biomarker Records from the South Yellow Sea: Relationship to the East Asian Monsoon - Liang Zou; Bangqi Hu; Jun Li; Yanguang Dou; Luhua Xie; Liang Dong (Journal of Ocean University of China, 2018)

Rockburst occurrences and microseismicity in a longwall panel experiencing frequent rockbursts - Zhen-lei Li; Xue-qiu He; Lin-ming Dou; Gui-feng Wang (Geosciences Journal, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Targeting Chaperone-Mediated Autophagy for Disease Therapy - Wenming Li; Juan Dou; Jing Yang; Haidong Xu; Hua She (Current Pharmacology Reports, 2018)

Comparison of the Trace Elements and Active Components of Lonicera japonica flos and Lonicera flos Using ICP-MS and HPLC-PDA - Yueran Zhao; Deqiang Dou; Yueqiu Guo; Yue Qi; Jun Li; Dong Jia (Biological Trace Element Research, 2018)

Characterization of Chiton Ischnochiton hakodadensis Foot Based on Transcriptome Sequencing - Huaiqian Dou; Yan Miao; Yuli Li; Yangping Li; Xiaoting Dai; Xiaokang Zhang; Pengyu Liang; Weizhi Liu; Shi Wang; Zhenmin Bao (Journal of Ocean University of China, 2018)

Insights into the redox components of dissolved organic matters during stabilization process - Ying Yuan; Bei-Dou Xi; Xiao-Song He; Yan Ma; Hui Zhang; Dan Li; Xin-Yu Zhao (Environmental Science and Pollution Research, 2018)

Detection of autophagy processes during the development of nonarticulated laticifers in Euphorbia kansui Liou - Qing Zhang; Dou Wang; Hao Zhang; Meng Wang; Peng Li; Xiaoai Fang; Xia Cai (Planta, 2018)

Multi-phase transformation model of water quality in the sluice-controlled river reaches of Shayinghe River in China - Ming Dou; Yaxin Cao; Qingbin Mi; Guiqiu Li; Yanyan Wang (Environmental Science and Pollution Research, 2018)

Male Populus cathayana than female shows higher photosynthesis and less cellular injury through ABA-induced manganese transporting inhibition under high manganese condition - Fugui Chen; Juan Shen; Dou Min; Lixia Ke; Xin Tian; Helena Korpelainen; Chunyang Li (Trees, 2018)

Melatonin Alleviates Intracerebral Hemorrhage-Induced Secondary Brain Injury in Rats via Suppressing Apoptosis, Inflammation, Oxidative Stress, DNA Damage, and Mitochondria Injury - Zhong Wang; Feng Zhou; Yang Dou; Xiaodi Tian; Chenglin Liu; Haiying Li; Haitao Shen; Gang Chen (Translational Stroke Research, 2018)

Sumoylation of SUVR2 contributes to its role in transcriptional gene silencing - Yu-Xi Luo; Yong-Feng Han; Qiu-Yuan Zhao; Jin-Lu Du; Kun Dou; Lin Li; She Chen; Xin-Jian He (Science China Life Sciences, 2018)

Enhanced‐efficiency fertilizers are not a panacea for resolving the nitrogen problem - Tingyu Li; Weifeng Zhang; Jiao Yin; David Chadwick; David Norse; Yuelai Lu; Xuejun Liu; Xinping Chen; Fusuo Zhang; David Powlson; Zhengxia Dou (Global Change Biology, 2018)
Improving nitrogen (N) management for greater agricultural output while minimizing unintended environmental consequences is critical in the endeavor of feeding the growing population sustainably amid climate change. Enhanced‐efficiency fertilizers ( EEF s) have been developed to better synchronize fertilizer N release with crop uptake, offering the potential for enhanced N use efficiency ( NUE ) and reduced losses. Can EEF s play a significant role in helping address the N management challenge? Here we present a comprehensive analysis of worldwide studies published in 1980–2016 evaluating four major types of EEF s (polymer‐coated fertilizers PCF , nitrification inhibitors NI , urease inhibitors UI , and double inhibitors DI , i.e. urease and nitrification inhibitors combined) regarding their effectiveness in increasing yield and NUE and reducing N losses. Overall productivity and environmental efficacy depended on the combination of EEF type and cropping systems, further affected by biophysical conditions. Best scenarios include: (i) DI used in grassland ( n = 133), averaging 11% yield increase, 33% NUE improvement, and 47% decrease in aggregated N loss (sum of NO 3 ‐ , NH 3 , and N 2 O, totaling 84 kg N/ha); (ii) UI in rice‐paddy systems ( n = 100), with 9% yield increase, 29% NUE improvement, and 41% N‐loss reduction (16 kg N/ha). EEF efficacies in wheat and maize systems were more complicated and generally less effective. In‐depth analysis indicated that the potential benefits of EEF s might be best achieved when a need is created, for example, by downward adjusting N application from conventional rate. We conclude that EEF s can play a significant role in sustainable agricultural production but their prudent use requires firstly eliminating any fertilizer mismanagement plus the implementation of knowledge‐based N management practices.

Effects of metal oxide nanoparticles on soil enzyme activities and bacterial communities in two different soil types - Tingting You; Dandan Liu; Jing Chen; Zhongzhou Yang; Runzhi Dou; Xiang Gao; Li Wang (Journal of Soils and Sediments, 2018)

Numerical investigation of the evolution of overlying strata and distribution of static and dynamic loads in a deep island coal panel - Guang-an Zhu; Lin-ming Dou; Chang-bin Wang; Jing Li; Wu Cai; Zi-wei Ding (Arabian Journal of Geosciences, 2017)

A new compound, methylbergenin along with eight known compounds with cytotoxicity and anti-inflammatory activity from Ardisia japonica - Ke-Yun Yu; Wei Wu; Shang-Zhen Li; Li-Li Dou; Le-Le Liu; Ping Li; E-Hu Liu (Natural Product Research, 2017)

Long noncoding RNA expression profiles in chondrogenic and hypertrophic differentiation of mouse mesenchymal stem cells - Zhen Cao; Song Huang; Jianmei Li; Yun Bai; Ce Dou; Chuan Liu; Fei Kang; Xiaoshan Gong; Haibin Ding; Tianyong Hou; Shiwu Dong (Functional & Integrative Genomics, 2017)

Development of a loop-mediated isothermal amplification method for the rapid detection of Pythium ultimum - Danyu Shen; Qingling Li; Jia Yu; Yuanyuan Zhao; Ye Zhu; Heng Xu; Daolong Dou (Australasian Plant Pathology, 2017)

The aflatoxin-detoxifizyme specific expression in the parotid gland of transgenic pigs - An-gang Lou; Jin-shun Cai; Xue-mei Zhang; Cheng-dou Cui; Ying-shu Piao; Li-zeng Guan (Transgenic Research, 2017)

A method for alpine wetland delineation and features of border: Zoigê Plateau, China - Yaomin Zheng; Zhenguo Niu; Peng Gong; Mengna Li; Lile Hu; Lei Wang; Yuxiang Yang; Haijun Gu; Jinrong Mu; Gejia Dou; Hui Xue; Lin Wang; et al. (Chinese Geographical Science, 2017)

Sorting nexin (MoVps17) is required for fungal development and plant infection by regulating endosome dynamics in the rice blast fungus - Huawei Zheng; Zhongkun Guo; Yang Xi; Mingyue Yuan; Yahong Lin; Congxian Wu; Yakubu Saddeeq Abubakar; Xianying Dou; Guangpu Li; Zonghua Wang; Wenhui Zheng; Jie Zhou (Environmental Microbiology, 2017)
Summary Vps17 is a sorting nexin (SNX) and a component of the retromer, a protein complex mediating retrograde vesicle transport between endosomes and the trans‐Golgi network. However, its role in the development and pathogenicity of filamentous fungi such as the rice blast fungus ( Magnaporthe oryzae ) remains unclear. We investigate the functional relationship between the SNX and the cargo‐selective complex (CSC) of the fungal retromer by genetic analysis, live cell imaging and immunological assay. Our data show that the MoVps17 null mutation causes defects in growth, development and pathogenicity in M. oryzae . MoVps17 is localized to endosomes depending on the activity of phosphatidylinositol 3‐kinase (PI3K), a key enzyme for fungal development and infection. Both PX and BAR domains of MoVps17 are essential for its endosomal localization and function. Furthermore, our yeast two‐hybrid assays show that MoVps17 and MoVps5 can interact. Lastly, live cell imaging suggests that MoVps17 can regulate early endosome fusion and budding as well as endocytosis. Taken together, our results suggest that MoVps17 specifically functions as a retromer component with CSC and also plays a distinct role in the regulation of endosome dynamics during fungal development and plant infection.

Thermospheric mass density derived from CHAMP satellite precise orbit determination data based on energy balance method - RuoXi Li; JiuHou Lei; XiJing Wang; XianKang Dou; ShuangGen Jin (Science China Earth Sciences, 2017)

Investigating spatial variability of vertical water fluxes through the streambed in distinctive stream morphologies using temperature and head data - Liping Wang; Weiwei Jiang; Jinxi Song; Xinyi Dou; Hongtao Guo; Shaofeng Xu; Guotao Zhang; Ming Wen; Yongqing Long; Qi Li (Hydrogeology Journal, 2017)

Development of a multimetric index based on benthic macroinvertebrates for the assessment of urban stream health in Jinan City, China - Linfei Liu; Zongxue Xu; Xuwang Yin; Fulin Li; Tongwen Dou (Environmental Monitoring and Assessment, 2017)

Synthesis and pharmacokinetic property improvement of deuterated plinabulin 9 - Jianchun Zhao; Hejuan Cheng; Tianwen Sun; Shixiao Wang; Zhongpeng Ding; Guifang Dou; Zhiyun Meng; Huashi Guan; Wenbao Li (Journal of Ocean University of China, 2017)

Erratum to: Hydrochemistry of Fluoride in Groundwaters from the Permo–Triassic Aquifer System of Central Shaanxi Province, Northwest China - Yan Dou; Ken Howard; Liwei Yang; Dong Wang; Li Guo (Exposure and Health, 2017)

Health risk assessment of cadmium pollution emergency for urban populations in Foshan City, China - Ming Dou; Peipei Zhao; Yanyan Wang; Guiqiu Li (Environmental Science and Pollution Research, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Characterization of a soybean mosaic virus variant causing different diseases in Glycine max and Nicotiana benthamiana - Hua Jiang; Kai Li; Daolong Dou; Junyi Gai (Archives of Virology, 2017)

Case Study of Passive Seismic Velocity Tomography in Rock Burst Hazard Assessment During Underground Coal Entry Excavation - Guang-an Zhu; Lin-ming Dou; Wu Cai; Zhen-lei Li; Min Zhang; Yong Kong; Wei Shen (Rock Mechanics and Rock Engineering, 2016)

Parallel viewshed analysis on a PC cluster system using triple-based irregular partition scheme - Xiao-Dong Song; Guo-An Tang; Xue-Jun Liu; Wan-Feng Dou; Fa-Yuan Li (Earth Science Informatics, 2016)

Rational Improvement of Peptide Affinity to Human Pregnancy-Related Serine Protease HtrA3 PDZ Domain by Introducing a Halogen Bond to the Domain–Peptide Complex Interface - Hong Liu; Shuo-Fen Dou; Xue Zhang; Yan Wang; Qing-Li Wen; Ya-Nan Mu (International Journal of Peptide Research and Therapeutics, 2016)

Characterization of Chromium Waste Form Based on Biocementation by Microbacterium sp. GM-1 - Limei Lun; Dongwei Li; Yajie Yin; Dou Li; Guojing Xu; Ziqiang Zhao; Shan Li (Indian Journal of Microbiology, 2016)

Hydrochemistry of Fluoride in Groundwaters from the Permo–Triassic Aquifer System of Central Shaanxi Province, Northwest China - You Dou; Ken Howard; Liwei Yang; Dong Wang; Li Guo (Exposure and Health, 2016)

Temporal and spatial characteristics of the water pollutant concentration in Huaihe River Basin from 2003 to 2012, China - Ming Dou; Yan Zhang; Guiqiu Li (Environmental Monitoring and Assessment, 2016)

Evolution of Stress Concentration and Energy Release Before Rock Bursts: Two Case Studies from Xingan Coal mine, Hegang, China - Gui-feng Wang; Si-yuan Gong; Zhen-lei Li; Lin-ming Dou; Wu Cai; Yong Mao (Rock Mechanics and Rock Engineering, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Solar-, monsoon- and Kuroshio-influenced thermocline depth and sea surface salinity in the southern Okinawa Trough during the past 17,300 years - Libo Wang; Jun Li; Jingtao Zhao; Helong Wei; Bangqi Hu; Yanguang Dou; Zhilei Sun; Liang Zou; Fenglong Bai (Geo-Marine Letters, 2016)

Phosphatidylinositol 3-phosphate, an essential lipid in Phytophthora sojae, enriches in the haustoria during infection - Linlin Chen; Wen Wang; Ying Hou; Yuren Wu; Honglian Li; Daolong Dou (Australasian Plant Pathology, 2016)

Treatment of cauda equina syndrome caused by lumbar disc herniation with percutaneous endoscopic lumbar discectomy - Xiaolong Li; Qingyu Dou; Shuai Hu; Jiaxiang Liu; Qingquan Kong; Jiancheng Zeng; Yueming Song (Acta Neurologica Belgica, 2016)

Genetic variation in APE1 gene promoter is associated with noise-induced hearing loss in a Chinese population - Huanxi Shen; Jianrui Dou; Lei Han; Ying Bai; Qian Li; Zhiqiang Hong; Jian Shi; Hengdong Zhang; Feng Zhang; Cheng Du; Zhimin Tong; Baoli Zhu (International Archives of Occupational and Environmental Health, 2016)

Mining-induced stress changes and rock burst control in a variable-thickness coal seam - Guang-an Zhu; Lin-ming Dou; Zhen-lei Li; Wu Cai; Yong Kong; Jing Li (Arabian Journal of Geosciences, 2016)

MpMYBS3 as a crucial transcription factor of cold signaling confers the cold tolerance of banana - Tong-xin Dou; Chun-hua Hu; Xiao-xuan Sun; Xiu-hong Shao; Jun-hua Wu; Li-jie Ding; Jie Gao; Wei-di He; Manosh-Kumar Biswas; Qiao-song Yang; Gan-jun Yi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Simulation and control of the linked systems of water quantity–water quality–socio-economics in the Huaihe River basin - Ming Dou; Qiting Zuo; Junxia Ma; Guiqiu Li (Hydrological Sciences Journal, 2016)

Mechanical Analysis of Static Stress Within Fault-Pillars Based on a Voussoir Beam Structure - Zhen-lei Li; Lin-ming Dou; Wu Cai; Gui-feng Wang; Yan-lu Ding; Yong Kong (Rock Mechanics and Rock Engineering, 2016)

Population structure of Japanese Spanish mackerel Scomberomorus niphonius in the Bohai Sea, the Yellow Sea and the East China Sea: evidence from random forests based on otolith features - Chi Zhang; Zhenjiang Ye; Zengguang Li; Rong Wan; Yiping Ren; Shuozeng Dou (Fisheries Science, 2016)

Development and materials characteristics of fly ash- slag-based grout for use in sulfate-rich environments - Yang Yuyou; Cui Zengdi; Li Xiangqian; Dou Haijun (Clean Technologies and Environmental Policy, 2016)

The substrate promiscuity of a phosphopantetheinyl transferase SchPPT for coenzyme A derivatives and acyl carrier proteins - Yue-Yue Wang; Hong-Dou Luo; Xiao-Sheng Zhang; Tao Lin; Hui Jiang; Yong-Quan Li (Archives of Microbiology, 2016)

Roadway Stagger Layout for Effective Control of Gob-Side Rock Bursts in the Longwall Mining of a Thick Coal Seam - Zhen-lei Li; Lin-ming Dou; Wu Cai; Gui-feng Wang; Yan-lu Ding; Yong Kong (Rock Mechanics and Rock Engineering, 2016)

Alternative pathway is involved in the tolerance of highland barley to the low-nitrogen stress by maintaining the cellular redox homeostasis - Feng Wang; Xiaomin Wang; Chengzhou Zhao; Jianfeng Wang; Ping Li; Yanqin Dou; Yurong Bi (Plant Cell Reports, 2016)

Fatal pneumonia cases caused by human adenovirus 55 in immunocompetent adults - Shu-Yan Zhang; Yan-Ping Luo; Dou-Dou Huang; Hang Fan; Qing-Bin Lu; Ying Wo; Gang Chen; Xiao-Ai Zhang; Yan Li; Yi-Gang Tong; Wu-Chun Cao; Wei Liu (Infectious Diseases, 2016)

Paeoniflorin exerts analgesic and hypnotic effects via adenosine A1 receptors in a mouse neuropathic pain model - Dou Yin; Yuan-Yuan Liu; Tian-Xiao Wang; Zhen-Zhen Hu; Wei-Min Qu; Jiang-Fan Chen; Neng-Neng Cheng; Zhi-Li Huang (Psychopharmacology, 2016)

What caused the changes in the usage of Atractylodis Macrocephalae Rhizoma from ancient to current times? - Xiaotong Wang; Linghui Li; Xiaoku Ran; Deqiang Dou; Bin Li; Bingyou Yang; Wei Li; Kazuo Koike; Haixue Kuang (Journal of Natural Medicines, 2016)

Transgenic Wuzhishan minipigs designed to express a dominant-negative porcine growth hormone receptor display small stature and a perturbed insulin/IGF-1 pathway - Feida Li; Yong Li; Huan Liu; Xingju Zhang; Chuxin Liu; Kai Tian; Lars Bolund; Hongwei Dou; Wenxian Yang; Huanming Yang; Nicklas Heine Staunstrup; Yutao Du (Transgenic Research, 2015)

Rapid cloning and bioinformatic analysis of spinach Y chromosome-specific EST sequences - CHUAN-LIANG DENG; WEI-LI ZHANG; YING CAO; SHAO-JING WANG; SHU-FEN LI; WU-JUN GAO; LONG-DOU LU (Journal of Genetics, 2015)

Impact of diethylhexyl phthalate on gene expression and development of mammary glands of pregnant mouse - Lan Li; Jing-Cai Liu; Yong Zhao; Fang-Nong Lai; Fan Yang; Wei Ge; Cheng-Li Dou; Wei Shen; Xi-Feng Zhang; Hong Chen (Histochemistry and Cell Biology, 2015)

Mechanical Initiation and Propagation Mechanism of a Thrust Fault: A Case Study of the Yima Section of the Xiashi-Yima Thrust (North Side of the Eastern Qinling Orogen, China) - Wu Cai; Linming Dou; Zhenlei Li; Jiang He; Hu He; Yanlu Ding (Rock Mechanics and Rock Engineering, 2015)

Automatic detection of sinkhole collapses at finer resolutions using a multi-component remote sensing approach - Jie Dou; Xia Li; Ali P. Yunus; Uttam Paudel; Kuan-Tsung Chang; Zhongfan Zhu; Hamid Reza Pourghasemi (Natural Hazards, 2015)

Enzymatic hydrolysis of 7-xylosyltaxanes by an extracellular xylosidase from Cellulosimicrobium cellulans - Tong-Yi Dou; Hong-Wei Luan; Xing-Bao Liu; Shi-Yang Li; Xun-Fu Du; Ling Yang (Biotechnology Letters, 2015)

Isolation of differentially expressed sex genes in garden asparagus using suppression subtractive hybridization - Chuan-liang Deng; Ning-na Wang; Shu-fen Li; Tian-yu Dong; Xin-peng Zhao; Shao-jing Wang; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2015)

Characterisation of oligosaccharides from Baizhu by HILIC-MS - Zhe Lin; Yan-Fang Liu; Yang Qu; Li-Ying Shi; De-Qiang Dou; Hai-Xue Kuang (Natural Product Research, 2015)

Experimental analysis of the impact of sluice regulation on water quality in the highly polluted Huai River Basin, China - Qiting Zuo; Hao Chen; Ming Dou; Yongyong Zhang; Dongfeng Li (Environmental Monitoring and Assessment, 2015)

Influence of dietary taurine and housing density on oviduct function in laying hens - Bin Dai; Yuan-shu Zhang; Zi-li Ma; Liu-hai Zheng; Shuang-jie Li; Xin-hong Dou; Jian-sen Gong; Jin-feng Miao (Journal of Zhejiang University-SCIENCE B, 2015)

Endothelial cells-targeted soluble human Delta-like 4 suppresses both physiological and pathological ocular angiogenesis - XianChun Yan; ZiYan Yang; Yan Chen; Na Li; Li Wang; GuoRui Dou; Yuan Liu; JuanLi Duan; Lei Feng; SanMing Deng; Hua Han; Ping Zhang (Science China Life Sciences, 2015)

A Correlation Between Diet and Longevity Characterization by Means of Element Profiles in Healthy People over 80 Years from a Chinese Longevous Region - Da Cai; Danlei Li; Shancang Zhao; Xiaowei Dou; Fang Wang; Guohong Huang; Mouming Zhao; Quanyang Li (Biological Trace Element Research, 2015)

Molecular epidemiology of Cryptococcus neoformans and Cryptococcus gattii in China between 2007 and 2013 using multilocus sequence typing and the DiversiLab system - H.-T. Dou; Y.-C. Xu; H.-Z. Wang; T.-S. Li (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Epidemical features of HAdV-3 and HAdV-7 in pediatric pneumonia in Chongqing, China - Ying Wo; Qing-Bin Lu; Dou-Dou Huang; Xiao-Kun Li; Chen-Tao Guo; Hong-Yu Wang; Xiao-Ai Zhang; Wei Liu; Wu-Chun Cao (Archives of Virology, 2015)

Quasi-stationary planetary waves in the middle atmosphere of Mars - NingNing Wang; Tao Li; XianKang Dou (Science China Earth Sciences, 2015)

Quantitative analysis of seismic velocity tomography in rock burst hazard assessment - Wu Cai; Linming Dou; Siyuan Gong; Zhenlei Li; Shasha Yuan (Natural Hazards, 2015)

The C-Terminus of Tau Protein Plays an Important Role in Its Stability and Toxicity - Junhua Geng; Lu Xia; Wanjie Li; Fei Dou (Journal of Molecular Neuroscience, 2015)

Quantitative relations between chemical oxygen demand concentration and its influence factors in the sluice-controlled river reaches of Shaying River, China - Ming Dou; Guiqiu Li; Congying Li (Environmental Monitoring and Assessment, 2015)

Development and characterization of 53 polymorphic genomic-SSR markers in Siberian wildrye (Elymus sibiricus L.) - Yunting Lei; Yanyan Zhao; Feng Yu; Yuan Li; Quanwen Dou (Conservation Genetics Resources, 2014)

Piromelatine exerts antinociceptive effect via melatonin, opioid, and 5HT1A receptors and hypnotic effect via melatonin receptors in a mouse model of neuropathic pain - Yuan-Yuan Liu; Dou Yin; Li Chen; Wei-Min Qu; Chang-Rui Chen; Moshe Laudon; Neng-Neng Cheng; Yoshihiro Urade; Zhi-Li Huang (Psychopharmacology, 2014)

Analysis of structural deformation in the North Dabashan thrust belt, South Qinling, central China - Wangpeng Li; Shaofeng Liu; Tao Qian; Guoxing Dou; Tangjun Gao (International Geology Review, 2014)

Characterizing the heavy metal-complexing potential of fluorescent water-extractable organic matter from composted municipal solid wastes using fluorescence excitation–emission matrix spectra coupled with parallel factor analysis - Xiao-Song He; Bei-Dou Xi; Hong-Wei Pan; Xiang Li; Dan Li; Dong-Yu Cui; Wen-Bin Tang; Ying Yuan (Environmental Science and Pollution Research, 2014)

Influence of the composition and removal characteristics of organic matter on heavy metal distribution in compost leachates - Xiao-Song He; Bei-Dou Xi; Dan Li; Xu-Jing Guo; Dong-Yu Cui; Hong-Wei Pan; Yan Ma (Environmental Science and Pollution Research, 2014)

Three homologous genes encoding functional ∆8-sphingolipid desaturase in Populus tomentosa - Shu-Fen Li; Guo-Jun Zhang; Ying-Chun Yuan; Cong-Hui Wang; Wu-Jun Gao; Chuan-Liang Deng; Long-Dou Lu; Zan-Min Hu (Genes & Genomics, 2014)

A fracture enhancement method based on the histogram equalization of eigenstructure-based coherence - Xi-Ying Dou; Li-Guo Han; En-Li Wang; Xue-Hua Dong; Qing Yang; Gao-Han Yan (Applied Geophysics, 2014)

Notch Signaling Activation Promotes Seizure Activity in Temporal Lobe Epilepsy - Longze Sha; Xiaofeng Wu; Yuan Yao; Bo Wen; Jing Feng; Zhiqiang Sha; Xueqin Wang; Xiaoliang Xing; Wanchen Dou; Liri Jin; Wenting Li; Naili Wang; et al. (Molecular Neurobiology, 2014)

( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

MicroRNA-142-3p inhibits cell proliferation in human acute lymphoblastic leukemia by targeting the MLL-AF4 oncogene - Liping Dou; Jingxin Li; Dehua Zheng; Yonghui Li; Xiaoning Gao; Chengwang Xu; Li Gao; Lili Wang; Li Yu (Molecular Biology Reports, 2013)

Petrophysical characteristics of rocks and sulfides from the SWIR hydrothermal field - Chunhui Tao; Tao Wu; Xiaobing Jin; Bingjun Dou; Huaiming Li; Jianping Zhou (Acta Oceanologica Sinica, 2013)

Characteristics of root boron nutrition confer high boron efficiency in Brassica napus cultivars - Lu Yang; Quan Zhang; Jina Dou; Ling Li; Longfei Guo; Lei Shi; Fangsen Xu (Plant and Soil, 2013)

Psychological Stress-Induced Lower Serum Zinc and Zinc Redistribution in Rats - Liping Tao; Yuanyuan Zheng; Zhilei Shen; Yingjie Li; Xue Tian; Xiao Dou; Jianxin Qian; Hui Shen (Biological Trace Element Research, 2013)

Influence of changes in hydrodynamic conditions on cadmium transport in tidal river network of the Pearl River Delta, China - Ming Dou; Qiting Zuo; Jinping Zhang; Congying Li; Guiqiu Li (Environmental Monitoring and Assessment, 2013)

Two new dammarane-type saponins from leaves of Panax quinquefolium - Zheng Xiang; Jia Lv; Zhixun Zhou; Yingying Li; Deqiang Dou; Jinming Zhao (Natural Product Research, 2013)

Cloning and characterization of chromosomal markers in alfalfa (Medicago sativa L.) - Feng Yu; Yunting Lei; Yuan Li; Quanwen Dou; Haiqing Wang; Zhiguo Chen (Theoretical and Applied Genetics, 2013)

Microdissection and painting of the Y chromosome in spinach (Spinacia oleracea) - Chuan-liang Deng; Rui-yun Qin; Ying Cao; Jun Gao; Shu-fen Li; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2013)

Phylogenetic analysis of two Chinese orf virus isolates based on sequences of B2L and VIR genes - Huixia Li; Xueliang Zhu; Yadong Zheng; Shuai Wang; Zhenyong Liu; Yongxi Dou; Hui Li; Xuepeng Cai; Xuenong Luo (Archives of Virology, 2013)

Protection against peroxynitrite-induced DNA damage by mesalamine: implications for anti-inflammation and anti-cancer activity - Paul M. Graham; Jason Z. Li; Xueging Dou; Hong Zhu; Hara P. Misra; Zhenquan Jia; Yunbo Li (Molecular and Cellular Biochemistry, 2013)

Heavy metal in surface sediments of the Liaodong Bay, Bohai Sea: distribution, contamination, and sources - Bangqi Hu; Jun Li; Jingtao Zhao; John Yang; Fenglong Bai; Yanguang Dou (Environmental Monitoring and Assessment, 2013)

The impact of agricultural land use changes on soil organic carbon dynamics in the Danjiangkou Reservoir area of China - Xiaoli Cheng; Yuanhe Yang; Ming Li; Xiaolin Dou; Quanfa Zhang (Plant and Soil, 2013)

Comparative study of the interactions between ovalbumin and three alkaloids by spectrofluorimetry - Rui-qiang Wang; Yu-jing Yin; Hua Li; Yi Wang; Juan-Juan Pu; Rui Wang; Huan-jing Dou; Chuan-jun Song; Rui-yong Wang (Molecular Biology Reports, 2013)

Impact of the earthworm Aporrectodea trapezoides and the arbuscular mycorrhizal fungus Glomus intraradices on 15N uptake by maize from wheat straw - Huan Li; Chong Wang; Xiaolin Li; Peter Christie; Zhengxia Dou; Junling Zhang; Dan Xiang (Biology and Fertility of Soils, 2013)

Two new oleanane-type saponins from the husks of Xanthoceras sorbifolia Bunge - Ying-Ying Li; Zheng Xiang; Hao Cui; Hang Xiao; Ting-Guo Kang; De-Qiang Dou; Hai-Xue Kuang (Natural Product Research, 2013)

Analysis of observations on the urban surface energy balance in Beijing - ShiGuang Miao; JunXia Dou; Fei Chen; Ju Li; AiGuo Li (Science China Earth Sciences, 2012)

NADPH oxidase 2 plays a critical role in dysfunction and apoptosis of pancreatic β-cells induced by very low-density lipoprotein - Juan Jiao; Lin Dou; Miao Li; Yonggang Lu; Han-Bang Guo; Yong Man; Shu Wang; Jian Li (Molecular and Cellular Biochemistry, 2012)

Evaluation of suitable reference genes for quantitative RT-PCR during development and abiotic stress in Panonychus citri (McGregor) (Acari: Tetranychidae) - Jin-Zhi Niu; Wei Dou; Tian-Bo Ding; Li-Hong Yang; Guang-Mao Shen; Jin-Jun Wang (Molecular Biology Reports, 2012)

Relative bioavailability and pharmacokinetic comparison of two different enteric formulations of omeprazole - Jian Liu; Jian-zhong Shentu; Li-hua Wu; Jing Dou; Qi-yang Xu; Hui-li Zhou; Guo-lan Wu; Ming-zhu Huang; Xing-jiang Hu; Jun-chun Chen (Journal of Zhejiang University-SCIENCE B, 2012)

Molecular characterization of three heat shock protein 70 genes and their expression profiles under thermal stress in the citrus red mite - Li-Hong Yang; Hong-Bo Jiang; Yong-Hua Liu; Wei Dou; Jin-Jun Wang (Molecular Biology Reports, 2012)

An intronic polymorphism rs2237062 in the CXCL14 gene influences HBV-related HCC progression in Chinese population - Xing Gu; Hao Wang; Aihua Wang; Tonghai Dou; Peng Qi; Qiang Ji; Hui Li; Chunfang Gao (Molecular Biology Reports, 2012)

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

Earthworm (Aporrectodea trapezoides)–mycorrhiza (Glomus intraradices) interaction and nitrogen and phosphorus uptake by maize - Huan Ll; Xiaolin Li; Zhengxia Dou; Junling Zhang; Chong Wang (Biology and Fertility of Soils, 2012)

Protective effect of ginsenoside Rb1 against myocardial ischemia/reperfusion injury in streptozotocin-induced diabetic rats - Yang Wu; Zhong-yuan Xia; Juan Dou; Li Zhang; Jin-jin Xu; Bo Zhao; Shaoqing Lei; Hui-min Liu (Molecular Biology Reports, 2011)

Tissue distribution and expression of signaling lymphocyte activation molecule receptor to peste des petits ruminant virus in goats detected by real-time PCR - Xuelian Meng; Yongxi Dou; Junjun Zhai; Hairui Zhang; Fengchao Yan; Xiaoni Shi; Xuelong Luo; Hui Li; Xuepeng Cai (Journal of Molecular Histology, 2011)

Unusual CT Hyperattenuating Dermoid Cyst of Cerebellum: A New Case Report and Literature Review - Zhao-Jian Li; Yuan-Xin Miao; Peng Sun; Yu-Jun Li; Yi-He Dou; Jian Xu; Xin Chen; Yun-Xia Jiang (The Cerebellum, 2011)

Arbuscular mycorrhiza regulate inter-specific competition between a poisonous plant, Ligularia virgaurea, and a co-existing grazing grass, Elymus nutans, in Tibetan Plateau Alpine meadow ecosystem - Liang Jin; Guiqi Zhang; Xiaojuan Wang; Cunyan Dou; Mu Chen; Shuangshuang Lin; Yuanyuan Li (Symbiosis, 2011)

Loss of heterozygosity of the tumor suppressor gene Tg737 in the side population cells of hepatocellular carcinomas is associated with poor prognosis - Zhi Song; Ren Li; Nan You; Kaishan Tao; Kefeng Dou (Molecular Biology Reports, 2010)

A new hexenol glycoside from leaves of Smallanthus sonchifolius - Xiang Zheng; Gai Kuo; Dou De-Qiang; Chen Gui-Rong; Kang Ting-Guo; Shi Yu-Yuan; Li Xing-Tai; Dong Feng (Natural Product Research, 2010)

The influence of ADAR1’s regulation on lymphocyte cell function during rejection - Lei Cai; Yan Li; Feng Liu; Wei Zhang; Binliang Huo; Wei Zheng; Rui Ding; Jiyuan Guo; Qingchuan Zhao; Kefeng Dou (Molecular Biology Reports, 2010)

A novel role of ammonia in appressorium formation of Alternaria alternata (Fries) Keissler, a tobacco pathogenic fungus - W. J. Duan; X. Q. Zhang; T. Z. Yang; X. W. Dou; T. G. Chen; S. J. Li; S. J. Jiang; Y. J. Huang; Q. Y. Yin (Journal of Plant Diseases and Protection, 2010)

Isolation of high quality RNA and construction of a suppression subtractive hybridization library from ramie (Boehmeria nivea L. Gaud.) - Xu-xia Wang; Bo Wang; Li-jun Liu; Xiao-ping Cui; Jin-yu Yang; Hui Wang; Hui Jiang; Bei-bei Luo; Zhu Long; Wen-xiang Dou; Na Zhang; Ding-xiang Peng (Molecular Biology Reports, 2010)

A new angeloylated triterpenoid saponin from the husks of Xanthoceras sorbifolia Bunge - Hongwei Fu; Ying Guo; Wei Li; Deqiang Dou; Tingguo Kang; Kazuo Koike (Journal of Natural Medicines, 2010)

Proteomic studies of phytopathogenic fungi, oomycetes and their interactions with hosts - Vijai Bhadauria; Sabine Banniza; Li-Xia Wang; Yang-Dou Wei; You-Liang Peng (European Journal of Plant Pathology, 2010)

Fluorocurcumins as Cyclooxygenase-2 Inhibitor: Molecular Docking, Pharmacokinetics and Tissue Distribution in Mice - Subhash Padhye; Sanjeev Banerjee; Deepak Chavan; Shubhangini Pandye; K.Venkateswara Swamy; Shadan Ali; Jing Li; Q. Ping Dou; Fazlul H. Sarkar (Pharmaceutical Research, 2009)

The effect of root exudates from two transgenic insect-resistant cotton lines on the growth of Fusarium oxysporum - Xiao-gang Li; Biao Liu; Sondre Heia; Dou-dou Liu; Zheng-min Han; Ke-xin Zhou; Jin-jie Cui; Jun-yu Luo; Yang-ping Zheng (Transgenic Research, 2009)

The challenge of developing green tea polyphenols as therapeutic agents - C. Huo; S. B. Wan; W. H. Lam; L. Li; Z. Wang; K. R. Landis-Piwowar; D. Chen; Q. P. Dou; T. H. Chan (Inflammopharmacology, 2008)

Engineering characteristics of near-fault vertical ground motions and their effect on the seismic response of bridges - Xinle Li; Huijuan Dou; Xi Zhu (Earthquake Engineering and Engineering Vibration, 2007)

Measurements of nighttime nitrate radical concentrations in the atmosphere by long-path differential optical absorption spectroscopy - Suwen Li; Wenqing Liu; Pinhua Xie; Ang Li; Min Qin; Ke Dou (Advances in Atmospheric Sciences, 2007)

Remediation of pentachlorophenol-contaminated soil by composting with immobilized Phanerochaete chrysosporium - Xiao-yun Jiang; Guang-ming Zeng; Dan-lian Huang; Yang Chen; Fang Liu; Guo-he Huang; Jian-bing Li; Bei-dou Xi; Hong-liang Liu (World Journal of Microbiology and Biotechnology, 2006)

Isolation and Characterization of Ubiquitin-activating Enzyme E1-domain Containing 1, UBE1DC1 - Tonghai Dou; Shaohua Gu; Jianping Liu; Fei Chen; Li Zeng; Lingchen Guo; Yi Xie; Yumin Mao (Molecular Biology Reports, 2005)

Thermal effects of building’s external surfaces in city - Yi-ping Zhang; Yun-ling He; Yu-hong Liu; You-xin Ma; You-rong Li; Jun-xia Dou (Chinese Geographical Science, 2004)

Note: Isolation and Characterization of a Jerky and JRK/JH8 Like Gene, Tigger Transposable Element Derived 7, TIGD7 - Tonghai Dou; Shaohua Gu; Zongxiang Zhou; Chaoneng Ji; Li Zeng; Xin Ye; Jian Xu; Kang Ying; Yi Xie; Yumin Mao (Biochemical Genetics, 2004)

Urban competitive pattern and its changes in China - Wen-zhang Dou; Guo-ping Li; Ying-jin Gan; Li-ming Wang; Kai-zhong Yang (Chinese Geographical Science, 2000)